Lithium ion secondary battery

By using lithium cobalt oxide and graphite silicon materials of specific particle sizes, as well as fluorocarbonate electrolytes, the problem of small discharge capacity of lithium ion secondary batteries in low temperature environments is solved, and the low temperature is achieved High discharge characteristics and large energy density under conditions.

CN119301786APending Publication Date: 2025-01-10SEMICON ENERGY LAB CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380043432.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-05
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing lithium-ion secondary batteries have small discharge capacity under low temperature environments and are difficult to maintain excellent discharge characteristics under low temperature conditions. It is necessary to develop positive electrodes, negative electrodes and electrolytes suitable for low temperature environments.

Method used

Lithium cobalt oxide with a median particle size of 1 μm or more and 12 μm or less is used as the positive electrode material, the surface layer contains magnesium, the negative electrode contains graphite and silicon particles, and a mixed solvent of fluorocyclic carbonate and fluorochain carbonate is used as the electrolysis. to ensure high discharge capacity and energy density under low temperature environments.

Benefits of technology

The excellent discharge characteristics and large discharge capacity of lithium-ion secondary batteries in low temperature environments are achieved, and the battery performance under low temperature conditions is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301786A_ABST
    Figure CN119301786A_ABST
Patent Text Reader

Abstract

Provided is a lithium ion secondary battery having excellent discharge characteristics even in a low-temperature environment. The lithium ion secondary battery includes a positive electrode, a negative electrode, and an electrolyte solution, the positive electrode contains lithium cobalt oxide having a median diameter (D50) of 1-12 [mu] m, the lithium cobalt oxide contains magnesium in a surface layer portion, the negative electrode contains graphite particles, silicon particles, and a polymer having a carboxyl group, and the electrolyte solution contains a mixed solvent of a fluorinated cyclic carbonate and a fluorinated chain carbonate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] One embodiment of the present invention relates to a lithium ion secondary battery. In addition, the present invention is not limited to the above-mentioned fields, and relates to a semiconductor device, a display device, a light emitting device, a power storage device, a lighting device, an electronic device, a vehicle, and a method for manufacturing the same. The semiconductor device, display device, light emitting device, power storage device, lighting device, electronic device, and vehicle can use a lithium ion secondary battery of one embodiment of the present invention as a required power source. For example, the electronic device includes an information terminal device equipped with a lithium ion secondary battery, etc. Furthermore, the power storage device includes a fixed power storage device, etc. Background Art

[0002] In recent years, research on various storage batteries such as lithium-ion secondary batteries, lithium-ion capacitors, air batteries and all-solid-state batteries has become increasingly popular. In particular, with the development of the semiconductor industry, the demand for high-output, high-capacity lithium-ion secondary batteries has increased dramatically, and as a rechargeable energy supply source, it has become a necessity in the modern information society.

[0003] It is known that the discharge capacity of a lithium ion secondary battery changes depending on the temperature during discharge. Therefore, there is a need for a lithium ion secondary battery having good battery characteristics even in a low temperature environment (for example, see Patent Document 1).

[0004] Furthermore, in order to realize the high capacity and improved charge-discharge cycle characteristics of lithium ion secondary batteries at room temperature, various research and development are carried out on both the positive electrode and the negative electrode. As a positive electrode active material, lithium cobalt oxide having a stable crystal structure has been studied (for example, refer to Patent Document 2).

[0005] Fluorides such as fluorite (calcium fluoride) have been used as fluxes in ironmaking and the like since ancient times, and their physical properties have been studied (for example, Non-Patent Document 1).

[0006] Furthermore, as negative electrode active materials, silicon-based materials are known to have a higher capacity than graphite-based materials, and negative electrodes using silicon-based materials have been studied (for example, Patent Document 3). [Prior technical literature] [Patent Document]

[0007] [Patent Document 1] Japanese Patent Application Publication No. 2015-026608 [Patent Document 2] WO2020 / 026078 Pamphlet [Patent Document 3] Japanese Patent Application Publication No. 2019-165005 [Non-patent literature]

[0008] [Non-patent document 1] WE Counts, R. Roy, and EFOsborn, "Fluoride Model Systems: II, The Binary Systems CaF2-BeF2, MgF2-BeF2, and LiF-MgF2", Journal of the AmericanCeramic Society, 36[1]12-17 (1953). Summary of the invention Technical problem to be solved by the invention

[0009] Patent document 1 records that a lithium ion secondary battery that can operate even in a low temperature environment (e.g., below 0° C.) can be realized by using the electrolyte described in patent document 1. However, at the stage of applying for the present invention, even for the lithium ion secondary battery described in patent document 1, it is difficult to say that its discharge capacity is large when discharged in a low temperature environment, so further improvement is expected.

[0010] Furthermore, in order to realize a lithium ion secondary battery having excellent discharge characteristics even in a low temperature environment, it is necessary to develop not only an electrolyte but also a positive electrode and a negative electrode suitable for a lithium ion secondary battery that can operate even in a low temperature environment.

[0011] One of the purposes of one embodiment of the present invention is to provide a lithium ion secondary battery having excellent discharge characteristics even in a low temperature environment. Specifically, one of the purposes of one embodiment of the present invention is to provide a positive electrode, a negative electrode, an electrolyte, etc. that can be used for a lithium ion secondary battery with a large discharge capacity even when discharged in a low temperature environment.

[0012] Note that the description of these purposes does not prevent the existence of other purposes. Note that one embodiment of the present invention does not necessarily achieve all of the above purposes. In addition, purposes other than the above purposes can be extracted from the description of this specification, drawings, claims, etc. Solutions to technical problems

[0013] One embodiment of the present invention is a lithium-ion secondary battery comprising: a positive electrode; a negative electrode; and an electrolyte, wherein the positive electrode comprises lithium cobalt oxide having a median particle size (D50) of greater than 1 μm and less than 12 μm, the lithium cobalt oxide containing magnesium in the surface portion, the negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group, and the electrolyte comprises a mixed solvent of a fluorinated cyclic carbonate and a fluorinated chain carbonate.

[0014] In one embodiment of the present invention, the average particle size of the silicon particles is preferably less than 1 μm.

[0015] In one embodiment of the present invention, the average particle size of the graphite particles is preferably 5 μm or more.

[0016] In one embodiment of the present invention, the average particle size of the silicon particles is preferably smaller than the average particle size of the graphite particles.

[0017] In one embodiment of the present invention, the weight ratio of the silicon particles is preferably smaller than the weight ratio of the graphite particles.

[0018] In one embodiment of the present invention, the polymer having a carboxyl group is preferably polyglutamic acid.

[0019] In one embodiment of the present invention, lithium cobalt oxide has a layered rock salt type crystal structure belonging to space group R-3m, and the surface portion includes a base region having a surface parallel to the (001) plane of the crystal structure and an end region having a surface parallel to a plane other than the (001) plane, and when performing EDX line analysis in the depth direction, the magnesium concentration in the base region in the lithium cobalt oxide is preferably higher than the magnesium concentration in the end region.

[0020] Another embodiment of the present invention is a lithium-ion secondary battery, comprising: a positive electrode; a negative electrode; and an electrolyte, wherein the positive electrode contains lithium cobalt oxide having a median particle size (D50) of greater than 1 μm and less than 12 μm, and the lithium cobalt oxide contains magnesium and nickel in the surface portion, the negative electrode contains graphite particles, silicon particles, and a polymer having a carboxyl group, the average particle size of the silicon particles is greater than the average particle size of the graphite particles, and the electrolyte contains a mixed solvent of fluorinated cyclic carbonates and fluorinated chain carbonates.

[0021] Another embodiment of the present invention is a lithium-ion secondary battery, comprising: a positive electrode; a negative electrode; and an electrolyte, wherein the positive electrode comprises lithium cobalt oxide having a median particle size (D50) of greater than 1 μm and less than 12 μm, the lithium cobalt oxide containing magnesium and nickel in the surface portion, the negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group, the average particle size of the silicon particles is greater than the average particle size of the graphite particles, and the electrolyte comprises fluoroethylene carbonate and methyl trifluoropropionate, and when the total content of fluoroethylene carbonate and methyl trifluoropropionate is 100 vol%, the volume ratio of fluoroethylene carbonate and methyl trifluoropropionate is x:100-x (note, 5≤x≤30).

[0022] Another embodiment of the present invention is a lithium-ion secondary battery, wherein lithium cobalt oxide has a layered rock salt type crystal structure belonging to space group R-3m, and the surface portion includes a base region having a surface parallel to the (001) plane of the crystal structure and an end region having a surface intersecting the (001) plane, and when performing STEM-EDX line analysis, i.e., EDX line analysis in the depth direction, the lithium cobalt oxide preferably has a region in the end region where the distribution of magnesium overlaps with the distribution of nickel.

[0023] Another embodiment of the present invention is a lithium-ion secondary battery, wherein lithium cobalt oxide has a layered rock salt type crystal structure belonging to the space group R-3m, the surface portion includes a base region having a surface parallel to the (001) plane of the crystal structure and an end region having a surface intersecting the (001) plane, and when performing STEM-EDX line analysis, i.e., EDX line analysis in the depth direction, the lithium cobalt oxide preferably contains substantially no nickel in the base region. Effects of the Invention

[0024] According to one embodiment of the present invention, a lithium ion secondary battery having excellent discharge characteristics even in a low temperature environment can be provided. Specifically, a positive electrode, a negative electrode, an electrolyte, etc. of a lithium ion secondary battery that can be used for discharge even in a low temperature environment and has a large discharge capacity and / or a large discharge energy density can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1A is a cross-sectional view illustrating the internal structure of a lithium-ion secondary battery, Figure 1B It is a cross-sectional view for explaining a positive electrode active material, an electrolyte solution, etc. of a lithium ion secondary battery. Figure 2A and Figure 2B It is a cross-sectional view illustrating a positive electrode active material. Figures 3A1 to 3B3 It is a cross-sectional view illustrating a positive electrode active material. Figure 4 It is a diagram illustrating the crystal structure of the positive electrode active material. Figure 5 This is a diagram illustrating the crystal structure of a conventional positive electrode active material. Figure 6 It is a figure which shows the XRD pattern calculated from the crystal structure. Figure 7 It is a figure which shows the XRD pattern calculated from the crystal structure. FIG. 8A to FIG. 8D It is a diagram for explaining a method for producing a positive electrode active material. Fig. 9 It is a diagram for explaining a method for producing a positive electrode active material. FIG. 10A to FIG. 10C It is a diagram for explaining a method for producing a positive electrode active material. Fig.11 This is a phase diagram showing the relationship between the composition of lithium fluoride and magnesium fluoride and the temperature. Fig.12 It is a graph which shows the results of DSC analysis. Fig.13 It is a diagram for explaining a method for producing a negative electrode active material. Fig.14A This is an exploded perspective view of a coin-type secondary battery. Fig. 14Bis a perspective view of a coin-type secondary battery. Fig. 14C It is a cross-sectional stereogram. Fig.15A An example of a cylindrical secondary battery is shown. Fig. 15B An example of a cylindrical secondary battery is shown. Fig. 15C A plurality of examples of cylindrical secondary batteries are shown. Fig.15D An example of a power storage system including a plurality of cylindrical secondary batteries is shown. Fig.16A and Fig. 16B is a diagram illustrating an example of a secondary battery, Fig. 16C It is a diagram showing the internal state of a secondary battery. 17A to 17C It is a diagram for explaining an example of a secondary battery. Fig.18A and Fig.18B A diagram showing the appearance of a secondary battery. FIG. 19A to FIG. 19C It is a diagram for explaining a method for manufacturing a secondary battery. Fig. 20A is a perspective view showing a battery pack according to one embodiment of the present invention. Fig. 20B is the block diagram of the battery pack, Fig. 20C is a block diagram of a vehicle including a battery pack. FIG. 21A to FIG. 21D It is a diagram illustrating an example of a transport vehicle. Fig.21E This is a diagram illustrating an example of an artificial satellite. Fig.22A and Fig. 22B It is a diagram for explaining a power storage device according to one embodiment of the present invention. Fig.23A is a diagram showing an electric bicycle, Fig. 23B is a diagram showing a secondary battery of an electric bicycle, Fig.23C It is a figure explaining a small motorcycle. FIG. 24A to FIG. 24D It is a diagram for explaining an example of an electronic device. Fig.25A is an example showing a wearable device, Fig.25B is a three-dimensional diagram of a watch-type device, Fig.25C It is a diagram illustrating the side view of a wristwatch-type device. Fig.26A is the SEM image of sample 1, Fig.26B It is a schematic diagram. Fig.27A and Fig.27B is a graph showing the results of the cycle test at low temperature described in the examples. FIG. 28A to FIG. 28C : is a graph showing the XRD analysis of the high voltage charging state described in the examples. Fig.29A and Fig.29B It is a graph showing the STEM-EDX analysis described in the examples. FIG. 30A to FIG. 30C It is a graph showing the STEM-EDX analysis described in the examples. FIG. 31A to FIG. 31C It is a graph showing the STEM-EDX analysis described in the examples. Fig.32 is a graph showing the results of the cycle test at low temperature described in the examples. Fig.33 is the SEM image of sample 2. Modes for Carrying Out the Invention

[0026] The present embodiment is described with appropriate reference to the accompanying drawings. Note that the present invention is not limited to the following description. It is readily understood by those skilled in the art that the modes and details of the present invention can be changed in various ways without departing from the spirit and scope of the present invention. Therefore, in the embodiments shown below, the reference numerals representing the same components of the present invention are common in different drawings.

[0027] Note that, unless otherwise specified, the following embodiment modes and examples can be implemented in combination with the embodiment modes and examples described in this specification and the like as appropriate.

[0028] In this specification, etc., a low temperature environment refers to 0°C or less, and 0°C or less is described as below the freezing point. In addition, in this specification, etc., when it is described as a low temperature environment, any temperature below 0°C can be selected. For example, in this specification, etc., when it is described as a low temperature environment, one of 0°C or less, -10°C or less, -20°C or less, -30°C or less, -40°C or less, -50°C or less, -60°C or less, -80°C or less, and -100°C or less can be selected.

[0029] In this specification, etc., the space group is represented by a short notation using the international symbol (or Hermann-Mauguin symbol). In addition, the Miller index is used to represent the crystal plane and the crystal direction. In crystallography, the space group, crystal plane and crystal direction are represented by a superscript bar attached to the number. Each face representing the crystal plane is represented by "()". (minus sign) is used to represent the space group, crystal plane and crystal direction, instead of attaching a superscript bar to the number. In addition, "[]" is used to represent the individual orientation of the orientation within the crystal, "<>" is used to represent the collective orientation of all equivalent orientations, "()" is used to represent the individual face of the crystal plane, and "{}" is used to represent the collective face with equivalent symmetry. In addition, in general, in order to facilitate the understanding of the structure, the trigonal system represented by the space group R-3m is represented by a composite hexagonal lattice of the hexagonal lattice, and sometimes (hkil) is used as the Miller index in addition to (hkl). Here, i is -(h+k).

[0030] In addition, characters such as h, k, i, and l may be used to represent any integer greater than 1. For example, (001) includes (001), (003), and (006).

[0031] In addition, the space group of the crystal structure is identified by XRD, electron diffraction, neutron diffraction, etc. Therefore, in this specification, etc., belonging to a certain space group or a space group means being identified as a certain space group.

[0032] In this specification, etc., the theoretical capacity of the positive electrode active material refers to the amount of electricity when all the lithium that can be embedded and detached in the positive electrode active material is detached. For example, the theoretical capacity of LiCoO2 is 274mAh / g, the theoretical capacity per unit weight of LiNiO2 is 275mAh / g, and the theoretical capacity of LiMn2O4 is 148mAh / g.

[0033] In addition, x in the composition formula can be, for example, Li x x in CoO2 (the occupancy rate of Li in the lithium position) represents the amount of lithium remaining in the positive electrode active material that can be inserted and removed. In the case of the positive electrode active material in a lithium ion secondary battery, x = (theoretical capacity - charging capacity) / theoretical capacity. For example, when a lithium ion secondary battery using LiCoO2 as the positive electrode active material is charged to a unit weight of 219.2 mAh / g of the positive electrode active material, it can be said that Li 0.2 CoO2 or x = 0.2. Li x The state where x in CoO2 is small is, for example, x≤0.24. When considering the actual range when used as a lithium ion secondary battery, for example, it is 0.1 <x≤0.24。

[0034] When lithium cobalt oxide roughly satisfies the stoichiometric ratio, it is LiCoO2 and x=1. In addition, a lithium-ion secondary battery at the end of discharge can also be said to be LiCoO2 and x=1. In addition, in general, the discharge voltage of a lithium-ion secondary battery using LiCoO2 drops sharply before reaching 2.5V. Therefore, in this specification, for example, a state in which a current of less than 100mA / g per unit weight of the positive electrode active material reaches a voltage of 2.5V (the electrode is lithium) is regarded as a state in which discharge is completed, and x=1. Therefore, for example, in order to obtain lithium cobalt oxide when x=0.2, it is sufficient to charge the positive electrode active material to a unit weight of 219.2mAh / g from the state in which discharge is completed.

[0035] To calculate Li x The charge capacity and / or discharge capacity of x in CoO2 is preferably measured under conditions without or with little effect of short circuit and / or electrolyte decomposition. For example, data of lithium-ion secondary batteries that experience a sudden change in voltage that may cause a short circuit are preferably not used to calculate x.

[0036] In this specification, "carbonate" refers to a compound containing at least one carbonate in its molecular structure, and includes "cyclic carbonate" and "chain carbonate" unless otherwise specified. The category of "chain" includes straight chain and branched chain.

[0037] In this specification and the like, “including A and / or B” may be described, which means “including A”, “including B”, or “including A and B”.

[0038] In this specification, a full cell refers to a battery unit assembled in a manner including different electrodes such as a positive electrode / negative electrode unit cell. In this specification, a half cell refers to a battery unit assembled using lithium metal as a negative electrode (counter electrode).

[0039] In this specification, etc., lithium ion secondary battery is sometimes referred to as lithium ion battery, which refers to a battery using lithium ion as a carrier ion, but the carrier ion of the present invention is not limited to lithium ion. For example, alkali metal ions or alkaline earth metal ions can be used as the carrier ion of the present invention, specifically sodium ions can be used. At this time, lithium ions can be referred to as sodium ions to understand the present invention. In addition, when the structure without any restriction on the carrier ion is described, it is sometimes referred to as a secondary battery.

[0040] (Implementation Method 1) In this embodiment, a lithium ion secondary battery having excellent discharge characteristics even in a low-temperature environment is described.

[0041] [Lithium-ion secondary battery] A lithium ion secondary battery of one embodiment of the present invention includes a positive electrode, a negative electrode and an electrolyte. In addition, a separator is included between the positive electrode and the negative electrode. When a solid electrolyte or a semi-solid electrolyte is used instead of the electrolyte, the separator is not required. Furthermore, an outer packaging body containing the positive electrode, the negative electrode and the electrolyte may also be included.

[0042] In this embodiment, the structure of the lithium ion secondary battery is focused on for description, and the structure is to realize a lithium ion secondary battery having excellent discharge characteristics even in a low temperature environment (for example, below 0°C, below -20°C, preferably below -30°C, more preferably below -40°C, further preferably below -50°C, and most preferably below -60°C). Specifically, the description is centered on the positive electrode active material contained in the positive electrode, the negative electrode active material layer, and the electrolyte.

[0043] In this specification, etc., excellent discharge characteristics in a low temperature environment sometimes means that the discharge capacity in a low temperature environment (for example, below 0°C, below -20°C, preferably below -30°C, more preferably below -40°C, further preferably below -50°C, most preferably below -60°C) decreases less than the discharge capacity at 25°C.

[0044] Figure 1A 1 is a cross-sectional schematic diagram illustrating the internal structure of a lithium-ion secondary battery 10. The lithium-ion secondary battery 10 includes a positive electrode 11, a negative electrode 12, and a separator 13. The positive electrode 11 includes a positive electrode current collector 21 and a positive electrode active material layer 22 on the positive electrode current collector 21, and the negative electrode 12 includes a negative electrode current collector 31 and a negative electrode active material layer 32. As shown in the figure, the positive electrode active material layer 22 and the negative electrode active material layer 32 are opposite to each other through the separator 13. In addition, although Figure 1A Although not shown in the figure, the gaps in the positive electrode active material layer 22 , the gaps in the separator, and the gaps in the negative electrode active material layer 32 are impregnated with an electrolyte.

[0045] Figure 1B Show Figure 1A An enlarged view of portion A surrounded by a dotted line in FIG.

[0046] The positive electrode active material layer 22 includes a positive electrode active material 100 and a conductive material 41. Although not shown in the figure, a binder may be included in addition to the positive electrode active material 100 and the conductive material 41.

[0047] In addition, as shown in the figure, the gaps included in the positive electrode active material layer 22 are preferably filled with the electrolyte 51. For example, preferably more than 60% of the gaps included in the positive electrode active material layer 22 are filled with the electrolyte 51, more preferably more than 70% of the gaps are filled, more preferably more than 70% of the gaps are filled, more preferably more than 80% of the gaps are filled, more preferably more than 90% of the gaps are filled, more preferably more than 95% of the gaps are filled, and most preferably more than 99% of the gaps are filled. Note that the gaps included in the positive electrode active material layer 22 refer to the area other than the solid components (positive electrode active material, conductive material, etc.) in the positive electrode active material layer 22.

[0048] In addition, although detailed description is omitted, similar to the description of the positive electrode active material layer 22, it is preferred that the voids included in the negative electrode active material layer 32 are also filled with the electrolyte 51. For example, it is preferred that more than 60% of the voids included in the negative electrode active material layer 32 are filled with the electrolyte 51, more preferably more than 70% of the voids are filled, more preferably more than 80% of the voids are filled, more preferably more than 90% of the voids are filled, more preferably more than 95% of the voids are filled, and most preferably more than 99% of the voids are filled. Note that the voids included in the negative electrode active material layer 32 refer to the region other than the solid components (negative electrode active material, conductive material, etc.) in the negative electrode active material layer 32.

[0049] Thus, by filling the positive electrode active material layer 22 and the negative electrode active material layer 32 with the electrolyte 51, the area where the positive electrode active material and the negative electrode active material are in contact with the electrolyte can be expanded. That is, a lithium ion secondary battery with good charging and discharging characteristics in a low temperature environment can be realized.

[0050] In addition, during charging in a low temperature environment, the potential barrier when lithium ions are separated from the positive electrode active material tends to become higher. That is, it can be said that the lower the temperature of the charging environment, the greater the overvoltage required to separate lithium ions from the positive electrode active material. In other words, during charging in a low temperature environment, the positive electrode active material may be exposed to a high voltage (a high potential relative to the lithium potential). In other words, during charging in a low temperature environment, the charging capacity may decrease when the positive electrode active material is not exposed to a high voltage.

[0051] Therefore, as a positive electrode active material included in a lithium ion secondary battery having excellent charging and discharging characteristics even in a low temperature environment, it is preferable to use a positive electrode active material that can withstand a high voltage and obtain a high charge capacity during charging in a low temperature environment.

[0052] In addition, as an electrolyte contained in a lithium ion secondary battery having excellent charging and discharging characteristics even in a low temperature environment, it is preferred to use a material that has excellent lithium ion conductivity when charging and / or discharging (charging and discharging) is performed in a low temperature environment (for example, 0°C, -20°C, preferably -30°C, and more preferably -40°C).

[0053] A positive electrode active material and an electrolyte that are preferred as a lithium ion secondary battery having excellent charging and discharging characteristics even in a low-temperature environment are described in detail below.

[0054] [positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and may further contain at least one of a conductive material and a binder.

[0055] <Positive Electrode Active Material> The positive electrode active material has the function of absorbing and releasing lithium ions with charge and discharge. The positive electrode active material used as one embodiment of the present invention can also use a material with less degradation (or less resistance increase) accompanying charging and / or discharging (hereinafter also referred to as "charge and discharge") in a low temperature environment even at a high charging voltage (the voltage value based on lithium metal is shown without special instructions, and it is also recorded as "high charging voltage"). Specifically, a positive electrode active material (composite oxide) having a particle size (to be precise, a median particle size (D50)) of less than 12 μm (preferably less than 10.5 μm, more preferably less than 8 μm) obtained by the manufacturing method described in Embodiment 2 can be used. Of course, a positive electrode active material having a particle size greater than 12 μm and less than 20 μm can also be used. The positive electrode active material contains any one or more of the added element X, the added element Y and the added element Z. The added element X, the added element Y and the added element Z will be described in detail in <Containing Elements>.

[0056] The particle size can be measured by a particle size distribution analyzer using a laser diffraction and scattering method. The median particle size (D50) refers to the particle size when the cumulative amount of the cumulative particle amount curve in the particle size distribution measurement result accounts for 50%. The measurement of particle size is not limited to laser diffraction particle size distribution measurement, and the major diameter of the particle cross section can also be measured by analysis using a scanning electron microscope (hereinafter referred to as SEM) or a transmission electron microscope (hereinafter referred to as TEM). In addition, as a method for measuring the median particle size (D50) by analysis using SEM or TEM, for example, more than 20 particles are measured and a cumulative particle amount curve is prepared, and the particle size when the cumulative amount accounts for 50% is defined as the median particle size (D50).

[0057] As one of the evaluations of low temperature characteristics, the discharge capacity value under a low temperature environment (e.g., 0°C, -20°C, preferably -30°C, more preferably -40°C) is 50% or more (preferably 60% or more, more preferably 70% or more, further preferably 80% or more, and most preferably 90% or more) compared to the discharge capacity value at 20°C. Note that the above values ​​are preferably calculated under the same measurement conditions except for the ambient temperature.

[0058] Alternatively, even at a high charge voltage, by using a material that degrades less with charge and discharge (or a material that increases less in resistance) as a positive electrode active material, the discharge capacity can be increased at a low temperature environment (e.g., 0°C, -20°C, preferably -30°C, more preferably -40°C).

[0059] More specifically, the discharge capacity when charging and discharging at -40°C is preferably 60% or more, more preferably 65% ​​or more, further preferably 70% or more, and further preferably 75% or more, relative to the discharge capacity when charging and discharging at 25°C. Note that although it is set to -40°C, the temperature can be any low temperature and can be replaced by other low temperatures such as -20°C, -30°C, etc. As the above-mentioned discharge condition, for example, discharge can be performed at a current rate of 0.1C (note, 1C = 200mA / g (unit weight of the positive electrode active material)). In the evaluation of the above-mentioned low-temperature characteristics, as long as the measurement conditions other than the ambient temperature are made consistent, evaluation can also be performed at a low rate.

[0060] As one of the evaluations of other low-temperature characteristics, the discharge energy density value in a low-temperature environment (for example, 0°C, -20°C, preferably -30°C, and more preferably -40°C) is 50% or more (preferably 60% or more, more preferably 70% or more, further preferably 80% or more, and most preferably 90% or more) compared to the discharge energy density value at 25°C.

[0061] The ambient temperature described in this specification and the like refers to the temperature of the lithium-ion secondary battery. In the measurement of battery characteristics using a thermostatic bath, the ambient temperature can be regarded as the set temperature of the thermostatic bath. Therefore, it is preferred to set the battery (e.g., a test battery or a half-battery) of the measurement object in the thermostatic bath, and then start the test after sufficient time (e.g., more than 1 hour) until the test unit becomes the same temperature as the thermostatic bath, but is not limited to this method.

[0062] A positive electrode active material 100 of one embodiment of the present invention is described with reference to FIG2 and FIG3. The positive electrode active material 100 has little degradation caused by repeated high-voltage charging and discharging based on lithium metal, so it can provide sufficient battery characteristics even in a low temperature environment. In this embodiment, the high voltage refers to 4.6V based on lithium metal, preferably 4.65V, and more preferably 4.7V.

[0063] Figure 2A and Figure 2B This is a cross-sectional view of a positive electrode active material 100 according to one embodiment of the present invention. Figures 3A1 to 3A3 Show enlarged Figure 2B In addition, Figure 3B1 to Figure 3B3 Show enlarged Figure 2B Figure near the CD in .

[0064] like Figure 2A As shown in FIG. 1 , the positive electrode active material 100 includes a surface portion 100 a and an inner portion 100 b. Although the boundary between the surface portion 100 a and the inner portion 100 b is shown by a dotted line in these drawings, there is no clear boundary.

[0065] The surface portion 100a of the positive electrode active material 100 refers to, for example, within 50nm from the surface to the inside, preferably within 35nm from the surface to the inside, more preferably within 20nm from the surface to the inside, and most preferably within 10nm from the surface in a vertical or approximately vertical direction to the inside. The narrow width area from the surface to the inside, specifically the area within 20nm is called a shell. Note that approximately vertical includes vertical, specifically, 80° or more and 100° or less. The surface generated by cracks and / or cracks can also be referred to as a surface. The surface portion 100a is synonymous with the vicinity of the surface or the area near the surface.

[0066] In addition, a region deeper than the surface layer portion 100a in the positive electrode active material is referred to as an inner portion 100b. The inner portion 100b is synonymous with an inner region or a core.

[0067] In addition, when the positive electrode active material 100 has a layered rock salt type crystal structure of the space group R-3m, as Figure 2B As shown, the surface layer portion 100a includes an end region 100a1 and a base region 100a2.

[0068] Note that Figure 2A and Figure 2BIn the figure, the straight line with (001) indicates the (001) plane. The base region 100a2 has a plane parallel to or substantially parallel to the (001) plane. The (001) plane is referred to as the base plane, and the region having the (001) plane is referred to as the base region 100a2. When lithium cobalt oxide is used as the positive electrode active material 100, lithium ions can be embedded in and released from the base plane. In addition, the plane other than the (001) plane is referred to as the end plane, and the region other than the (001) plane is referred to as the end region 100a1.

[0069] The surface of the positive electrode active material 100 refers to the surface of the composite oxide including the surface layer 100a and the inner part 100b. Therefore, the positive electrode active material 100 does not include: a material attached with a metal oxide such as aluminum oxide (Al2O3) that does not contain a lithium position that contributes to charging and discharging; carbonates, hydroxyl groups, etc. that are chemically adsorbed after the positive electrode active material is manufactured. In addition, the attached metal oxide refers to, for example, a metal oxide whose crystal orientation is different from the crystal structure of the inner part 100b.

[0070] TEM (Transmission Electron Microscope: Transmission Electron Microscope) images, STEM (Scanning Transmission Electron Microscope: Scanning Transmission Electron Microscope) images, HAADF-STEM (High-angle Annular Dark Field Scanning TEM: High-angle annular dark field) images, ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope: Annular Bright Field Scanning Transmission Electron Microscope) images, electron diffraction patterns, etc. can be used to determine whether the crystal orientation of the two regions is roughly the same. In addition, it can also be determined by the FFT pattern of the TEM image and the FFT pattern of the STEM image. In addition, XRD (X-ray Diffraction: X-ray diffraction), neutron diffraction, etc. can be used as a basis for judgment.

[0071] In addition, the electrolyte, electrolyte decomposition products, organic solvents, binders, conductive materials, or compounds derived therefrom that adhere to the positive electrode active material 100 are not contained in the positive electrode active material. That is, the electrolyte, electrolyte decomposition products, organic solvents, binders, conductive materials, or compounds derived therefrom that adhere to the surface of the positive electrode active material are removed.

[0072] The positive electrode active material 100 is a compound containing transition metals and oxygen in which lithium can be embedded and detached, so the interface between the region where there is a transition metal M (for example, Co, Ni, Mn, Fe, etc.) and oxygen that is oxidized and reduced as lithium is embedded and detached and the region where there is no transition metal M and oxygen is called the surface of the positive electrode active material. Therefore, the surface caused by sliding, cracks and / or cracks can also be included in the surface of the positive electrode active material. When analyzing the positive electrode active material, the surface is sometimes covered with a protective film, but the protective film is not included in the positive electrode active material. As a protective film, a single layer or multilayer film of carbon, metal, oxide, resin, etc. is sometimes used.

[0073] <Contains elements> The positive electrode active material 100 includes lithium, cobalt, oxygen, and an additive element. Alternatively, the positive electrode active material 100 may include lithium cobalt oxide (LiCoO2) to which the additive element is added. Note that the positive electrode active material 100 of one embodiment of the present invention may have a crystal structure described later. Therefore, the composition of lithium cobalt oxide is not strictly limited to Li:Co:O=1:1:2.

[0074] As the additive element contained in the positive electrode active material 100, one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, barium, bromine and beryllium are preferably used.

[0075] The additional element is preferably dissolved in the positive electrode active material 100. As described later, the crystal structure of the positive electrode active material 100 is further stabilized by the additional element.

[0076] As the additive elements, magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, barium, bromine and beryllium are not necessarily contained.

[0077] For example, by manufacturing a positive electrode active material 100 that does not substantially contain manganese, the above advantages such as easier synthesis, easier handling, and good cycle characteristics can be improved. The weight of manganese contained in the positive electrode active material 100 is preferably 600 ppm or less, and more preferably 100 ppm or less.

[0078] The surface part 100a, especially the end area with end faces, is the area where lithium ions are first separated during charging, and is also the area where the lithium concentration is easily lower than that of the inner part 100b. In addition, it can be said that in the surface part 100a where lithium ions are separated, especially in the end area, the bonding of some atoms on the surface of the positive electrode active material 100 is cut. Therefore, the surface part 100a is likely to become an unstable area where crystal structure degradation is likely to begin. On the other hand, as long as the surface part 100a, especially the end area, can be made sufficiently stable, in the Li xWhen x in CoO2 is small, for example, when x is less than 0.24, the layered structure composed of cobalt and oxygen octahedra in the inner part 100b can be prevented from collapsing. Furthermore, as long as the surface part 100a, especially the end area, can be sufficiently stabilized, the deviation of the layer composed of cobalt and oxygen octahedra in the inner part 100b can be suppressed.

[0079] In order to make the surface part 100a have a stable composition and crystal structure, the surface part 100a preferably contains the above-mentioned additive elements, and more preferably contains a plurality of additive elements. In addition, the concentration of one or more selected from the additive elements in the surface part 100a is preferably higher than that in the inner part 100b. In addition, the concentration of one or more selected from the additive elements in the end region 100a1 is preferably higher than that in the base region 100a2.

[0080] Describe the distribution of added elements. FIG. 3A1 to FIG. 3A3 Is magnification Figure 2B The figure near AB in FIG. 1 is a figure for explaining the end region 100a1 of the positive electrode active material 100. Figure 3B1 to Figure 3B3 Is magnification Figure 2B The diagram near CD in FIG. 1 is a diagram for explaining the base region 100 a 2 of the positive electrode active material 100 .

[0081] For example, a portion of the added elements such as magnesium, fluorine, titanium, etc. preferably has a concentration gradient increasing from the inner portion 100b toward the surface. Figure 3A1 and Figure 3B1 In FIG. 1 , the concept of the above-mentioned concentration gradient is expressed by using the shaded concentration. The additive element having such a concentration gradient is referred to as additive element X. Note that the concentration of magnesium, fluorine, titanium, etc. in the terminal region 100a1 may also be higher than that in the base region 100a2.

[0082] Other added elements such as aluminum preferably have a concentration gradient and are more Figure 3A2 and Figure 3B2 The darker area of ​​the added element X shown has a concentration peak. Figure 3A2 and Figure 3B2 In the figure, the concentration gradient and peak region are indicated by the shaded concentration. The concentration peak may exist in the surface portion 100a or in a region deeper than the surface portion 100a. For example, it is preferred that a peak exists in a region of 5 nm or more and 30 nm or less from the surface to the inside. The additive element having such a concentration gradient is referred to as additive element Y. Note that the concentration of aluminum or the like in the end region 100a1 may also be higher than that in the base region 100a2.

[0083] like Figure 3A3 and Figure 3B3As shown by the presence or absence of shadows and the concentration of shadows, sometimes other additive elements such as nickel are clearly present in the end region 100a1, but are not substantially present in the base region 100a2. The concentration of nickel in the end region 100a1 is higher than that in the base region 100a2. Note that "clearly present" here means that the characteristic X-ray energy spectrum of the element is detected in the cross-sectional STEM-EDX analysis of the positive electrode active material 100. The additive element having the above distribution is called additive element Z.

[0084] In addition, "substantially absent" means that the characteristic X-ray spectrum of the element cannot be detected in the cross-sectional STEM-EDX analysis of the positive electrode active material 100. It can also be said that the element is below the detection limit in the STEM-EDX analysis. In this case, it can also be said that the element is below the detection limit in the analysis using STEM-EDX.

[0085] Magnesium, which is one of the added elements X, is divalent. In the layered rock salt type crystal structure, magnesium is more stable when it is present at the lithium position than at the cobalt position in the layered rock salt type crystal structure, and thus it is easy to enter the lithium position. When magnesium is present at the lithium position of the surface portion 100a at an appropriate concentration, the layered rock salt type crystal structure can be easily maintained. This is because magnesium present at the lithium position is used as a support between the CoO2 layers. In addition, when magnesium is present, for example, in the Li x When x in CoO2 is 0.24 or less, the release of oxygen around magnesium can be suppressed.

[0086] If magnesium has an appropriate concentration, it has no negative impact on the insertion and removal of lithium accompanying charge and discharge, so the above advantages can be achieved. However, excess magnesium may have a negative impact on the insertion and removal of lithium. In addition, the effect of contributing to the stabilization of the crystal structure is sometimes reduced. This is because magnesium not only enters the lithium position but also the cobalt position. In addition, there is also the following concern: excessive magnesium compounds (for example, oxides or fluorides, etc.) that are not substituted at the lithium position or the cobalt position are segregated on the surface of the positive electrode active material and become the resistance component of the lithium ion secondary battery. In addition, the increase in the magnesium concentration of the positive electrode active material sometimes reduces the discharge capacity of the positive electrode active material. This is because the excess magnesium enters the lithium position and the amount of lithium contributing to charge and discharge is reduced.

[0087] Therefore, it is preferred that an appropriate amount of magnesium is included in the positive electrode active material 100 as a whole. For example, the number of magnesium atoms is preferably greater than 0.001 times and less than 0.1 times the number of cobalt atoms, more preferably greater than 0.01 times and less than 0.04 times, and further preferably about 0.02 times. Here, the amount of magnesium in the positive electrode active material 100 as a whole can be, for example, a value obtained by analyzing all elements of the positive electrode active material 100 using GD-MS, ICP-MS, etc., or a value based on the coordination value of the raw materials in the manufacturing process of the positive electrode active material 100.

[0088] In addition, aluminum, one of the added elements Y, may exist in the cobalt position in the layered rock salt type crystal structure. Aluminum is a typical trivalent element and its valence does not change, so the lithium around aluminum is not easy to move during charging and discharging. Therefore, aluminum and the lithium around it are used as pillars to suppress changes in the crystal structure. In addition, aluminum has the effect of suppressing the dissolution of surrounding cobalt and improving continuous charging tolerance. In addition, the Al-O bond is stronger than the Co-O bond, so the oxygen around aluminum can be suppressed from leaving. Through the above effects, thermal stability is improved. Therefore, when aluminum is included as an added element, the safety of the positive electrode active material 100 when used in a lithium ion secondary battery can be improved. In addition, a positive electrode active material 100 that is not prone to collapse of the crystal structure even after repeated charging and discharging can be realized. On the other hand, when the amount of aluminum is too much, it may have a negative impact on the insertion and removal of lithium.

[0089] Therefore, it is preferred that an appropriate amount of aluminum is included in the positive electrode active material 100 as a whole. For example, the number of aluminum atoms in the positive electrode active material 100 as a whole is preferably greater than 0.05% and less than 4% of the number of cobalt atoms, more preferably greater than 0.1% and less than 2%, and further preferably greater than 0.3% and less than 1.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount in the positive electrode active material 100 as a whole shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material 100 as a whole using GD-MS, ICP-MS, etc., or a value obtained based on the mixing of raw materials in the manufacturing process of the positive electrode active material 100.

[0090] In addition, nickel, which is one of the added elements Z, may be present at the cobalt site or the lithium site. When nickel is present at the cobalt site, the redox potential is lower than that of cobalt, and the discharge capacity is increased, which is preferable.

[0091] In addition, when nickel is present at the lithium position, the deviation of the layered structure composed of octahedrons of cobalt and oxygen is suppressed. In addition, the volume change caused by charging and discharging is also suppressed. In addition, the elastic modulus is improved, that is, it becomes hard. This is because the nickel present at the lithium position is also used as a support between the CoO2 layers. Therefore, it can be expected that the crystal structure is more stable, especially when charged at a high temperature of 45°C or above, so it is preferred.

[0092] On the other hand, when the amount of nickel is too large, the influence of distortion due to the Jan-Teller effect increases, which is not preferable. In addition, when the amount of nickel is too large, it may have a negative impact on the insertion and extraction of lithium.

[0093] Therefore, it is preferred that an appropriate amount of nickel is included in the positive electrode active material 100 as a whole. For example, the number of nickel atoms contained in the positive electrode active material 100 is preferably higher than 0% of the number of cobalt atoms and less than 7.5%, more preferably greater than 0.05% and less than 4%, further preferably greater than 0.1% and less than 2%, and further preferably greater than 0.2% and less than 1%. Alternatively, it is preferably higher than 0% and less than 4%. Alternatively, it is preferably higher than 0% and less than 2%. Alternatively, it is preferably greater than 0.05% and less than 7.5%. Alternatively, it is preferably greater than 0.05% and less than 2%. Alternatively, it is preferably greater than 0.1% and less than 7.5%. Alternatively, it is preferably greater than 0.1% and less than 4%. The amount of nickel shown here can be, for example, a value obtained by elemental analysis of the positive electrode active material as a whole using GD-MS, ICP-MS, etc., or a value obtained by mixing raw materials in the manufacturing process of the positive electrode active material.

[0094] In addition, fluorine, one of the added elements X, is a monovalent anion, and when part of the oxygen in the surface portion 100a is replaced by fluorine, the lithium detachment energy is reduced. This is because the valence change of the cobalt ion accompanying the detachment of lithium varies according to the presence or absence of fluorine, for example, from trivalent to tetravalent in the absence of fluorine, and from divalent to trivalent in the presence of fluorine, and the redox potential is different. Therefore, when part of the oxygen in the surface portion 100a of the positive electrode active material 100 is replaced by fluorine, it can be said that the detachment and embedding of lithium ions near fluorine occur smoothly. Therefore, when the positive electrode active material 100 is used in a lithium ion secondary battery, the charge and discharge characteristics, high current characteristics, etc. can be improved. In addition, by having fluorine in the surface portion 100a of the surface including the portion in contact with the electrolyte, the corrosion resistance to hydrofluoric acid can be effectively improved. In addition, as shown in the following embodiment, when the melting point of fluorides such as lithium fluoride is lower than the melting point of other added element sources, it can be used as a flux (also known as a solubility aid) to reduce the melting point of other added element sources.

[0095] In addition, it is known that titanium oxide, one of the added elements X, has super hydrophilicity. Therefore, by manufacturing the positive electrode active material 100 containing titanium oxide in the surface layer 100a, it sometimes has good wettability to solvents with high polarity. When manufacturing a secondary battery, the positive electrode active material 100 has good contact with the interface of the electrolyte with high polarity, and sometimes the increase of internal resistance can be suppressed.

[0096] Furthermore, in Figure 3A1 The surface layer portion 100a shown contains magnesium and Figure 3A3 When the surface layer 100a shown in FIG. 1 includes nickel, that is, when it includes both magnesium and nickel, the divalent nickel may be more stably present near the divalent magnesium. x When x in CoO 2 is small, the dissolution of magnesium is also suppressed. Thus, magnesium and nickel contribute to the stabilization of the surface layer portion 100 a.

[0097] In addition, if Figure 3A3 and Figure 3B3 As shown, the end region 100a1 only needs to contain (also referred to as preferentially containing, selectively containing, etc.) a large amount of the additive element Z, and the stability of the crystal structure of the end region 100a1 of the positive electrode active material 100 during the charging and discharging of the lithium ion secondary battery is improved. Therefore, it is preferred. In addition, when the additive element Z has the above distribution, for example, when the positive electrode active material 100 is lithium cobalt oxide, the effects of the decrease in discharge voltage or the decrease in discharge capacity caused by the addition of the additive element Z can be suppressed as much as possible, so it is preferred.

[0098] When multiple additive elements are included as described above, each additive element plays a synergistic role and contributes to further stabilization of the surface portion 100a. In particular, when magnesium, nickel and aluminum are included, the effect of achieving a stable composition and crystal structure is high, so it is preferred. Among them, in the surface portion 100a of the positive electrode active material 100, it is preferred to have a region where magnesium is distributed closer to the surface than aluminum. In addition, it is most preferred that, in addition to the above-mentioned magnesium and aluminum distribution areas, there is also an area where nickel distribution and magnesium distribution overlap in the end area 100a1 in the surface portion 100a of the positive electrode active material 100.

[0099] <Crystal Structure> One embodiment of the present invention is to provide a lithium ion secondary battery having improved battery characteristics in a low temperature environment, wherein XRD measurement or the like for specifying a crystal structure or the like is performed at room temperature.

[0100] <Li x When x in CoO2 is 1> Preferably, the positive electrode active material 100 of one embodiment of the present invention is in a discharged state, that is, in a Li x When x=1 in CoO2, it has a layered rock salt type crystal structure belonging to the space group R-3m. The layered rock salt type composite oxide has a high discharge capacity and a two-dimensional lithium ion diffusion path, which is suitable for the insertion / extraction reaction of lithium ions and is excellent as a positive electrode active material for lithium ion secondary batteries. Therefore, the inner part 100b that occupies most of the volume of the positive electrode active material 100 preferably has a layered rock salt type crystal structure.

[0101] On the other hand, the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably strengthens the layered structure composed of cobalt and oxygen octahedrons in the inner portion 100b to prevent the layered structure from collapsing even if lithium is separated from the positive electrode active material 100 due to charging. Alternatively, the surface portion 100a is preferably used as a barrier film of the positive electrode active material 100. Alternatively, the surface portion 100a of the outer peripheral portion of the positive electrode active material 100 preferably strengthens the positive electrode active material 100. Here, strengthening refers to suppressing the structural changes of the surface portion 100a and the inner portion 100b of the positive electrode active material 100 such as the separation of oxygen and / or suppressing the oxidative decomposition of the electrolyte on the surface of the positive electrode active material 100.

[0102] In order to have a reinforcing function, the surface portion 100a may also have a crystal structure different from that of the inner portion 100b. For example, the composition and crystal structure of the surface portion 100a at room temperature (25°C) are preferably more stable than those of the inner portion 100b. For example, at least a portion of the surface portion 100a of the positive electrode active material 100 of one embodiment of the present invention preferably has a rock salt type crystal structure. Alternatively, the surface portion 100a may also have both a layered rock salt type crystal structure and a rock salt type crystal structure. Alternatively, the surface portion 100a may also have the characteristics of both a layered rock salt type crystal structure and a rock salt type crystal structure.

[0103] In addition, whether or not the crystal has the characteristics of both the layered rock salt type crystal structure and the rock salt type crystal structure can be determined by electron diffraction, TEM images, cross-sectional STEM images, and the like.

[0104] In addition, the concentration of a part of the added elements, especially magnesium, in the surface portion 100a is preferably higher than that in the inner portion 100b, and they are preferably also present irregularly and in small amounts in the inner portion 100b. When aluminum is present at an appropriate concentration at the lithium position in the inner portion 100b, it has the same effect as described above, such as easily maintaining a layered rock salt type crystal structure. In addition, when nickel is present at an appropriate concentration in the inner portion 100b, the deviation of the layered structure composed of octahedra of cobalt and oxygen is suppressed, as described above. In addition, in the case of simultaneously containing magnesium and nickel, divalent magnesium may also be more stably present near divalent nickel, so a synergistic effect of suppressing the dissolution of magnesium can be expected.

[0105] In addition, it is preferred that the crystal structure changes continuously from the inner portion 100b to the surface due to the magnesium concentration gradient. Alternatively, it is preferred that the crystal orientations of the surface portion 100a and the inner portion 100b are substantially identical.

[0106] In addition, in this specification, etc., the layered rock salt type crystal structure belonging to the space group R-3m possessed by the composite oxide containing transition metals such as lithium and cobalt refers to the following crystal structure: a rock salt type ion arrangement having alternating arrangements of cations and anions, and transition metals and lithium are regularly arranged to form a two-dimensional plane, so that lithium can diffuse in two dimensions. In addition, defects such as vacancies of cations or anions may also be included. Strictly speaking, the layered rock salt type crystal structure is sometimes a structure formed by lattice deformation of the rock salt type crystal structure, and sometimes its crystal orientation is roughly the same.

[0107] In addition, the rock salt type crystal structure has a cubic crystal structure such as space group Fm-3m, in which cations and anions are arranged alternately. In addition, vacancies of cations or anions may also be included.

[0108] The position of cations in the rock salt type crystal structure is the same, but in the layered rock salt type crystal structure, there are two types of cation positions, one where lithium occupies most of the position and the other where transition metal M occupies the position. Both the rock salt type and the layered rock salt type have a stacked structure in which two-dimensional planes of cations and two-dimensional planes of anions are alternately arranged.

[0109] The layered rock salt type crystal structure and the anions of the rock salt type crystal structure form a cubic closest packing structure (face-centered cubic lattice structure) respectively. It can be considered that the anions of the O3' type crystal described later also form a cubic closest packing structure. Therefore, when the layered rock salt type crystal structure contacts the rock salt type crystal structure, there are crystal planes with consistent orientation of the cubic closest packing structure formed by the anions.

[0110] In addition, it can be explained as follows. The anions on the {111} plane of the cubic crystal structure have a triangular lattice. The layered rock salt type has a rhombus structure belonging to the space group R-3m, but in order to facilitate the understanding of the structure, it is usually expressed as a composite hexagonal lattice, and the (0001) plane of the layered rock salt type has a hexagonal lattice. The triangular lattice of the {111} plane of the cubic crystal has the same atomic arrangement as the hexagonal lattice of the (0001) plane of the layered rock salt type. The state in which the lattices of the two are integrated can be said to be a state in which the orientation of the cubic closest packing structure is consistent.

[0111] Note that the space group of the layered rock salt type crystal structure and the O3' type crystal structure described later is R-3m, which is different from the space group Fm-3m (the space group of a general rock salt type crystal) of the rock salt type crystal structure, so the Miller index of the crystal plane that satisfies the above conditions is different between the layered rock salt type crystal structure and the O3' type crystal structure and the rock salt type crystal structure. In this specification, sometimes the state in which the orientation of the cubic closest packing structure formed by anions in the layered rock salt type crystal structure, the O3' type crystal structure and the rock salt type crystal structure is consistent refers to the state in which the crystal orientation is roughly consistent.

[0112] <Li x The state where x is small in LiCoO2> The positive electrode active material 100 of one embodiment of the present invention has the above-described magnesium distribution and / or crystal structure, and thus the crystal structure in the discharged state (Li x The state where x is small in CoO2) is different from that of the conventional positive electrode active material. Note that here, a small x means the case where 0.1 < x ≤ 0.24.

[0113] Use Figures 4 to 7 To compare the conventional positive electrode active material and the positive electrode active material 100 of one embodiment of the present invention to illustrate the change in the crystal structure accompanying the change in x in Li x CoO2.

[0114] Figure 5 Show the change in the crystal structure of the conventional positive electrode active material. Figure 5 The conventional positive electrode active material shown does not contain magnesium lithium cobaltate (LiCoO2).

[0115] In Figure 5 Attached with R-3m O3 represents the crystal structure of lithium cobaltate with x = 1 in Li x CoO2. In this crystal structure, lithium occupies the octahedral position and the unit cell includes three CoO2 layers. Therefore, this crystal structure is sometimes referred to as the O3-type crystal structure. Note that the CoO2 layer refers to a structure in which octahedral structures in which cobalt is coordinated to six oxygens are continuously shared by edges on a plane. Sometimes this structure is referred to as a layer composed of octahedrons of cobalt and oxygen.

[0116] In addition, it is known that: the symmetry of lithium in the conventional lithium cobaltate increases at around x = 0.5 and has a crystal structure belonging to the space group P2 / m of the monoclinic system. In this structure, the unit cell includes one CoO2 layer. Therefore, it is sometimes referred to as the O1-type structure or the monoclinic O1-type structure.

[0117] The positive electrode active material at x = 0 has a crystal structure belonging to the trigonal system of the space group P-3m1, and the unit cell also includes one CoO2 layer. Thus, this crystal structure is sometimes referred to as the O1-type structure or the trigonal O1-type structure. In addition, sometimes the trigonal system is transformed into a composite hexagonal lattice and referred to as the hexagonal O1-type.

[0118] In addition, the existing lithium cobalt oxide has a crystal structure belonging to the space group R-3m when x=0.12. It can also be said that this structure is a structure in which a CoO2 structure such as a trigonal O1 structure and a LiCoO2 structure such as an R-3m O3 structure are alternately stacked. Therefore, this crystal structure is sometimes called an H1-3 type crystal structure. In addition, in fact, the number of cobalt atoms in each unit cell of the H1-3 type crystal structure is twice that of other structures. However, in Figure 5 In this specification, in order to facilitate comparison with other crystal structures, the c-axis of the H1-3 type crystal structure is 1 / 2 of the unit cell.

[0119] As an example of an H1-3 type crystal structure, the coordinates of cobalt and oxygen in the unit cell can be represented by Co (0, 0, 0.42150 ± 0.00016), O1 (0, 0, 0.27671 ± 0.00045), and O2 (0, 0, 0.11535 ± 0.00045). O1 and O2 are both oxygen atoms. For example, by performing Rietveld analysis on the XRD pattern, it can be determined which unit cell is used to represent the crystal structure of the positive electrode active material. At this time, a unit cell with a small GOF (goodness of fit) value is used, specifically a unit cell with a GOF value close to 1.

[0120] When repeated Li x During charge and discharge when x in CoO2 is 0.24 or less, the crystal structure of conventional lithium cobalt oxide changes repeatedly between the H1-3 type crystal structure and the structure belonging to R-3m O3 in the discharged state (ie, non-equilibrium phase transition).

[0121] However, the CoO2 layers of the above two crystal structures deviate greatly. Figure 5 As shown by the dotted line and arrows, in the H1-3 type crystal structure, the CoO2 layer deviates significantly from the R-3m O3 structure in the discharge state. Such dynamic structural changes will have an adverse effect on the stability of the crystal structure.

[0122] Furthermore, the volume difference between the two crystal structures is also large. When comparing the same number of cobalt atoms, the volume difference between the H1-3 type crystal structure and the R-3m O3 type crystal structure in the discharge state exceeds 3.5%, typically 3.9% or more.

[0123] In addition to the above, the structure of the H1-3 type crystal structure having a continuous CoO2 layer like that of the trigonal O1 type is likely to be unstable.

[0124] Therefore, when charging and discharging are repeated until x becomes less than 0.24, the crystal structure of the existing lithium cobalt oxide collapses. The collapse of the crystal structure will cause the deterioration of the cycle characteristics. This is because the collapse of the crystal structure reduces the number of sites where lithium can exist stably, and the insertion and removal of lithium become difficult.

[0125] On the other hand, Figure 4 In the positive electrode active material 100 of one embodiment of the present invention shown in FIG. x The change in crystal structure between the discharge state where x is 1 and the state where x is less than 0.24, specifically, the state where x is 0.2 (sometimes recorded as 0% probability of Li existence) in CoO2 is less than that of existing positive electrode active materials. More specifically, the deviation of the CoO2 layer between the state where x is 1 and the state where x is less than 0.24 can be reduced. In addition, the volume change when comparing each cobalt atom can be reduced. Therefore, even if the positive electrode active material 100 of one embodiment of the present invention is repeatedly charged and discharged with x being less than 0.24, it is not easy to cause crystal structure collapse and good cycle characteristics can be achieved. In addition, the positive electrode active material 100 of one embodiment of the present invention is Li x When x in CoO2 is 0.24 or less, it can have a more stable crystal structure than the existing positive electrode active material. x When x in CoO2 is 0.24 or less, short circuit is less likely to occur. In this case, the safety of the lithium ion secondary battery is further improved, which is preferred.

[0126] Figure 4 Shown in Li x The crystal structure of the inner portion 100b of the positive electrode active material 100 when x in CoO2 is about 1 and about 0.2. The inner portion 100b occupies most of the volume of the positive electrode active material 100 and has a great influence on charge and discharge, so it can be said that it is the part with the greatest influence caused by the deviation of the CoO2 layer and the change in volume.

[0127] When x=1, the positive electrode active material 100 has the same R-3m O3 type crystal structure as that of conventional lithium cobalt oxide.

[0128] However, when the conventional lithium cobalt oxide has an H1-3 type crystal structure and x is 0.24 or less, for example, about 0.2 or about 0.12, the positive electrode active material 100 has a crystal having a structure different from the above structure.

[0129] When x=0.2 or so, the positive electrode active material 100 of one embodiment of the present invention has a crystal structure belonging to the space group R-3m of the trigonal system. The symmetry of the CoO2 layer of this structure is the same as that of O3. Therefore, this crystal structure is called an O3'-type crystal structure. In addition, although the positive electrode active material 100 of one embodiment of the present invention when x=0.2 or so is not a spinel structure, sometimes a pattern similar to a spinel structure appears in the XRD pattern, and this crystal structure is sometimes called a pseudo-spinel structure. Figure 4 The crystal structure is indicated by R-3m O3'.

[0130] The coordinates of cobalt and oxygen in the unit cell of the O3' type crystal structure can be represented by Co(0, 0, 0.5) and O(0, 0, x) (0.20≤x≤0.25), respectively. In addition, the lattice constants of the unit cell are as follows: the a-axis is preferably 2.797≤a≤2.837(×10 - 1 nm), more preferably 2.807≤a≤2.827(×10 -1 nm), typically a=2.817(×10 -1 The c-axis is preferably 13.681≤c≤13.881(×10 -1 nm), more preferably 13.751≤c≤13.811, typically c=13.781(×10 - 1 nm).

[0131] In the O3' type crystal structure, ions of cobalt, magnesium, etc. occupy the positions coordinated to six oxygen atoms. In addition, light elements such as lithium sometimes occupy the positions coordinated to four oxygen atoms.

[0132] like Figure 4 The dotted line in the figure shows that there is almost no deviation between the CoO2 layers in the R-3m(O3) and O3' type crystal structures in the discharged state.

[0133] In addition, the difference in volume of the same number of cobalt atoms between the R-3m (O3) and O3' type crystal structures in the discharged state is 2.5% or less, more specifically 2.2% or less, and typically 1.8%.

[0134] Thus, in the positive electrode active material 100 of one embodiment of the present invention, Li xWhen x in CoO2 is small, that is, when more lithium is detached, the change in the crystal structure is suppressed compared with the existing positive active material. In addition, the change in volume when compared by the same number of cobalt atoms is also suppressed. Therefore, the crystal structure of the positive active material 100 is not easy to collapse even if x is repeatedly charged and discharged to be less than 0.24. Therefore, the decrease in the charge and discharge capacity of the positive active material 100 caused by the charge and discharge cycle is suppressed. In addition, a larger amount of lithium can be stably used than the existing positive active material, so the discharge capacity per unit weight and unit volume of the positive active material 100 is larger. Therefore, by using the positive active material 100, a lithium-ion secondary battery with a higher discharge capacity per unit weight and unit volume can be manufactured.

[0135] In addition, it was confirmed that the positive electrode active material 100 x When x in CoO2 is 0.15 or more and 0.24 or less, it sometimes has an O3' type crystal structure, and it is also considered to have an O3' type crystal structure when x is higher than 0.24 and 0.27 or less. x In addition to x in CoO2, it is also affected by the number of charge and discharge cycles, charge and discharge current, temperature, electrolyte, etc., and is therefore not limited to the above range of x.

[0136] Therefore, the positive electrode active material 100 in Li x When x in CoO2 is greater than 0.1 and less than 0.24, the entire interior 100b of the positive electrode active material 100 does not need to have an O3' type crystal structure, but may have other crystal structures or may be partially amorphous.

[0137] In addition, in order to achieve Li x In the case of CoO2 with a small x value, a high charging voltage is generally required for charging. x The state in which x in CoO2 is small is referred to as a state in which charging is performed at a high charging voltage.

[0138] It can also be said that the positive electrode active material 100 of one embodiment of the present invention can maintain a crystal structure having R-3m O3 symmetry when charged at a high charging voltage of 4.6V or higher at 25°C, so it is preferred. In addition, it can also be said that it can have an O3' type crystal structure when charged at a voltage of 4.65V or higher and 4.7V or lower at 25°C, so it is preferred.

[0139] The positive electrode active material 100 sometimes has H1-3 type crystals only when the charging voltage is further increased. In addition, as described above, the crystal structure is affected by the number of charge and discharge cycles, the charge and discharge current, the electrolyte, etc., so when the charging voltage is lower, for example, even at 25°C and the charging voltage is 4.5V or more and less than 4.6V, the positive electrode active material 100 of one embodiment of the present invention sometimes has an O3' type crystal structure.

[0140] In addition, for example, when graphite is used as the negative electrode active material of the lithium ion secondary battery, the voltage drop of the above-mentioned lithium ion secondary battery is equivalent to the potential of the graphite. The potential of graphite is about 0.05V to 0.2V based on the potential of lithium metal. Therefore, the lithium ion secondary battery using graphite as the negative electrode active material has the same crystal structure as the case where the voltage is obtained by subtracting the potential of graphite from the above voltage.

[0141] In addition, Figure 4 In the O3' type, lithium exists at all lithium positions with equal probability, but it is not limited to this. In addition, lithium may exist concentratedly at a part of the lithium positions. For example, it may also have a Figure 5 The monoclinic O1 structure (Li 0.5 The distribution of lithium can be analyzed, for example, by neutron diffraction.

[0142] In order to have an O3'-type crystal structure, the concentration gradient of magnesium preferably has the same gradient in multiple parts of the surface portion 100a of the positive electrode active material 100. That is, the reinforcing elements derived from magnesium are preferably present homogeneously in the surface portion 100a. Even if a part of the surface portion 100a is reinforced, if there is a part that is not reinforced, stress may be concentrated in this part. When stress is concentrated in a part of the positive electrode active material 100, defects such as cracks may occur from this part, thereby causing the positive electrode active material to rupture and reduce the discharge capacity. Note that it is not necessary for the magnesium in the surface portion 100a of the positive electrode active material 100 to have the same concentration gradient.

[0143] In the layered rock salt type crystal structure belonging to R-3m, cations are arranged parallel to the (001) plane. It can be said that this is a structure in which CoO2 layers and lithium layers are stacked parallel to the (001) plane and alternately. Therefore, the diffusion path of lithium ions is also parallel to the (001) plane. As mentioned above, the (001) plane is called the basal plane, and the plane other than the (001) plane where the diffusion path of lithium ions is exposed is called the end face.

[0144] The CoO2 layer is relatively stable, so the CoO2 layer is relatively stable on the (001) surface. The main diffusion path of lithium ions during charge and discharge is not exposed on the (001) surface.

[0145] On the other hand, on the surface other than the (001) surface, the diffusion path of lithium ions is exposed. Therefore, the surface other than the (001) surface and the surface portion 100a having the surface are very important areas for maintaining the diffusion path of lithium ions, and are the areas where lithium ions first leave, so they tend to be unstable. Therefore, in order to maintain the overall crystal structure of the positive electrode active material 100, it is very important to strengthen the surface other than the (001) surface and the surface portion 100a having the surface.

[0146] <Analysis Method> In order to determine whether a positive electrode active material is in Li x The positive electrode active material 100 of one embodiment of the present invention, which has an O3' type crystal structure when x in CoO2 is small, can contain Li x The positive electrode of the positive electrode active material with a smaller x in CoO2 is judged by using XRD, electron diffraction, neutron diffraction, electron spin resonance (ESR), nuclear magnetic resonance (NMR) and other analyses. By XRD, especially powder XRD, a diffraction peak reflecting the crystal structure of the positive electrode active material 100b inside 100 that occupies most of the volume of the positive electrode active material 100 can be obtained, so it is preferred.

[0147] In addition, when x is too small such as 0.1 or less or when the charging voltage exceeds 4.9 V, an H1-3 type or trigonal O1 type crystal structure is also generated in the positive electrode active material 100 of one embodiment of the present invention. Therefore, in order to determine whether it is a positive electrode active material 100 of one embodiment of the present invention, analysis of the crystal structure such as XRD and information such as the charging capacity or the charging voltage are required.

[0148] In addition, the positive electrode active material in a state where x is small may change its crystal structure when exposed to air. For example, it may change from an O3' type crystal structure to an H1-3 type crystal structure. Therefore, all samples used in analyzing the crystal structure are preferably treated in an inert atmosphere such as an argon atmosphere.

[0149] In addition, by analyzing by XPS, Energy Dispersive X-ray Spectroscopy (EDX), EPMA (Electron Probe Microanalysis), or the like, it can be determined whether the distribution of the additive element contained in the positive electrode active material is in the above-mentioned state.

[0150] The crystal structure of the surface layer portion 100 a , grain boundaries, and the like can be analyzed by performing electron diffraction or the like on a cross section of the positive electrode active material 100 .

[0151] <<Charging Method>> As charging for determining whether the composite oxide is the positive electrode active material 100 of one embodiment of the present invention, for example, a coin battery (CR2032 type, 20 mm in diameter, 3.2 mm in height) of a lithium counter electrode can be manufactured and charged.

[0152] More specifically, as the positive electrode, a positive electrode obtained by applying a slurry obtained by mixing a positive electrode active material, a conductive material, and a binder to a positive electrode current collector of an aluminum foil can be used.

[0153] Lithium metal can be used as the counter electrode.

[0154] 1 mol / L lithium hexafluorophosphate (LiPF6) was used as the lithium salt, a mixed solvent obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a ratio of EC:DEC=3:7 (volume ratio) was used as the electrolyte, and an additive prepared by mixing 2 wt% of vinylene carbonate (VC) relative to the mixed solvent was used as the additive.

[0155] As the separator, a polypropylene porous film having a thickness of 25 μm can be used.

[0156] The positive electrode can and the negative electrode can may be formed of stainless steel (SUS).

[0157] The coin cell manufactured under the above conditions is charged at any voltage (for example, 4.5V, 4.55V, 4.6V, 4.65V, 4.7V, 4.75V or 4.8V). There is no limitation on the charging method as long as it can be charged at any voltage and for a sufficient time. For example, when charging with CCCV, the current per unit weight of the positive electrode active material in CC charging can be set to be greater than 20mA / g and less than 100mA / g. CV charging can be performed until the unit weight of the positive electrode active material is greater than 2mA / g and less than 10mA / g. In order to observe the phase change of the positive electrode active material, it is preferred to charge at the above-mentioned smaller current value. The temperature is set to 25°C. After charging in this manner, the coin cell is disassembled in a glove box in an argon atmosphere and the positive electrode is taken out, thereby obtaining a positive electrode active material of any charging capacity. In order to prevent reaction with external components when various analyses are performed later, it is preferably sealed under an argon atmosphere. For example, XRD can be performed under the condition of a sealed container sealed in an argon atmosphere. In addition, it is preferred to take out the positive electrode immediately after charging for analysis. Specifically, it is preferably performed within 1 hour after charging, and more preferably within 30 minutes after charging.

[0158] In addition, when analyzing the crystal structure of the charged state after multiple charge and discharge, the multiple charge and discharge conditions may also be different from the above-mentioned charging conditions. For example, charging can be performed at a current value of 20 mA / g or more and 100 mA / g or less to perform constant current charging to any voltage (for example, 4.6 V, 4.65 V, 4.7 V, 4.75 V or 4.8 V), and then constant voltage charging can be performed at a current value of 2 mA / g or more and 10 mA / g or less, and discharging can be performed at a constant current discharge to 2.5 V at a current value of 20 mA / g or more and 100 mA / g or less.

[0159] Furthermore, when analyzing the crystal structure in a discharged state after multiple charge and discharge, for example, constant current discharge to 2.5 V may be performed at a current value of 20 mA / g or more and 100 mA / g or less.

[0160] <xrd> There is no limitation on the apparatus and conditions for XRD measurement as long as there is appropriate adjustment and calibration. For example, the measurement can be performed with the following apparatus and conditions. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: Cu Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 90° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm As a standard sample for adjustment and calibration, for example, a standard sintered alumina plate SRM 1976 of NIST (National Institute of Standards and Technology) or the like can be used.

[0161] When the sample to be measured is a powder sample, the sample can be installed by placing it in a glass sample holder; or sprinkling the sample on a silicon non-reflective plate coated with grease; etc. When the sample to be measured is a positive electrode, the positive electrode active material layer can be installed according to the measurement surface required by the device by attaching the positive electrode to the substrate with double-sided tape.

[0162] The monochromatization of characteristic X-rays can be performed using a filter or the like, or using XRD data analysis software after obtaining the XRD pattern. For example, DEFFRAC.EVA (XRD data analysis software manufactured by Bruker) can be used to remove the peaks passing through CuKα2 rays and extract only the peaks passing through CuKα1 rays. In addition, the software can also be used to perform background removal, etc.

[0163] In this specification, etc., when the value of 2θ of a certain diffraction peak is mentioned, it means the value of 2θ of the peak top of the diffraction peak that appears in the XRD pattern after fitting the calculation model. There is no particular limitation on the crystal structure analysis software used for fitting, for example, TOPASver.3 (crystal structure analysis software manufactured by Bruker Corporation) can be used.

[0164] Figure 6 and Figure 7 The ideal powder XRD patterns calculated by CuKα1 radiation from the models of O3' type crystal structure and H1-3 type crystal structure are shown. In addition, for comparison, the XRD patterns calculated from Li x Ideal XRD patterns calculated for the crystal structures of LiCoO2 O3 where x is 1 and trigonal O1 where x is 0 in CoO2. The patterns of LiCoO2(O3) and CoO2(O1) were made using Reflex Powder Diffraction, one of the modules of Materials Studio (BIOVIA), based on the crystal structure information obtained from ICSD (Inorganic Crystal Structure Database). The range of 2θ was set to 15° to 75°, Step size = 0.01, and wavelength λ1 = 1.540562×10 -10 m, λ2 are not set, and Monochromator is set to single. The XRD pattern of the H1-3 type crystal structure is based on Figure 7 The information of the H1-3 type crystal structure shown was prepared in the same manner as described above. The XRD pattern of the O3' type crystal structure was prepared by the following method: the crystal structure was inferred from the XRD pattern of the positive electrode active material of one embodiment of the present invention and fitted using TOPAS ver.3 (crystal structure analysis software manufactured by Bruker), and the XRD pattern was prepared in the same manner as other structures.

[0165] like Figure 6 As shown, in the O3'-type crystal structure, diffraction peaks appear at 2θ of 19.25±0.12° (19.13° or more and 19.37° or less) and 2θ of 45.47±0.10° (45.37° or more and 45.57° or less).

[0166] However, if Figure 7 As shown, in the H1-3 type crystal structure and the trigonal crystal O1, the peak does not appear at the above position. x The appearance of diffraction peaks at 2θ=19.25±0.12° (above 19.13° and below 19.37°) and 2θ=45.47±0.10° (above 45.37° and below 45.57°) when x in CoO2 is small is a characteristic of the positive electrode active material 100 of one embodiment of the present invention.

[0167] This also indicates that: the position of the XRD diffraction peak appearing in the crystal structure when x=1 is close to the position of the XRD diffraction peak appearing in the crystal structure when x≤0.24; more specifically, regarding the peaks in the main diffraction peaks of the crystal structure when x=1 and the crystal structure when x≤0.24, the 2θ difference between the peaks appearing at 42° or more and 46° or less is less than 0.7°, preferably less than 0.5°.

[0168] In addition, the positive electrode active material 100 of one embodiment of the present invention is Li x When x in CoO2 is small, it has an O3' type crystal structure, but it is not necessary for the entire CoO2 to have an O3' type crystal structure. It can have other crystal structures, and it can also be partially amorphous. Note that when performing Rietveld analysis on the XRD pattern, the O3' type crystal structure is preferably 50% or more, more preferably 60% or more, and further preferably 66% or more. When the O3' type crystal structure is 50% or more, more preferably 60% or more, and further preferably 66% or more, a positive electrode active material with sufficiently excellent cycle characteristics can be achieved.

[0169] In addition, the sharpness of the diffraction peak in the XRD pattern indicates the height of crystallinity. Therefore, each diffraction peak after charging is preferably sharp, that is, the half-width is preferably narrow. The half-width of the peak of the same crystalline phase varies according to the measurement conditions of XRD and / or the value of 2θ. When adopting the above-mentioned measurement conditions, for example, the half-width of the peak observed at 2θ of more than 43° and less than 46° is preferably less than 0.2°, more preferably less than 0.15°, and further preferably less than 0.12°. The characteristics of narrow half-width and high crystallinity contribute to the stabilization of the crystal structure after charging. On the other hand, even if a part of the existing LiCoO2 may have a structure similar to the O3'-type crystal structure, the grain size will become smaller, and its peak will also become wider and smaller.

[0170] <xps> X-ray photoelectron spectroscopy (XPS) can analyze the depth range of about 2nm to 8nm (generally less than 5nm) from the surface when analyzing inorganic oxides and using monochromated aluminum Kα line as the X-ray source, so the concentration of each element in about half of the depth direction of the surface part 100a can be quantitatively analyzed. In addition, by performing narrow scan analysis, the bonding state of the elements can be analyzed. The measurement accuracy of XPS is about ±1 atomic% in many cases. Although it depends on the element, the detection limit is about 1 atomic%.

[0171] In addition, the concentration of the added element can also be compared with the ratio of cobalt. By using the ratio with cobalt, the influence of carbonates chemically adsorbed after manufacturing the positive electrode active material can be reduced for comparison, so it is preferred. For example, the ratio of the number of atoms of magnesium to cobalt obtained by XPS analysis Mg / Co is preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, more preferably 0.700 or more, more preferably 0.800 or more, more preferably 0.900 or more, and more preferably 1.000 or more. In addition, Mg / Co is preferably less than 2.000, preferably less than 1.500, preferably less than 1.400, preferably less than 1.300, or preferably less than 1.200.

[0172] In addition, for example, the ratio of the number of atoms of nickel and cobalt obtained by XPS analysis, Ni / Co, is preferably 0.05 or more, more preferably 0.06 or more, more preferably 0.07 or more, more preferably 0.08 or more, and more preferably 0.09 or more. In addition, Ni / Co is preferably 0.200 or less, preferably 0.150 or less, preferably 0.140 or less, preferably 0.130 or less, preferably 0.120 or less, or preferably 0.110 or less.

[0173] In addition, for example, the ratio of the number of fluorine atoms to the number of cobalt atoms F / Co obtained by XPS analysis is preferably 0.100 or more, more preferably 0.200 or more, more preferably 0.300 or more, more preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, and more preferably 0.700 or more. In addition, F / Co is preferably 1.500 or less, preferably 1.200 or less, preferably 1.100 or less, preferably 1.000 or less, and preferably 0.900 or less.

[0174] It can also be said that the above range means that the above added element is not attached to a narrow range on the surface of the positive electrode active material 100, but is widely distributed in the surface layer 100a of the positive electrode active material 100 at a preferred concentration. In other words, the result of the XPS analysis of the positive electrode active material 100 in the above range indicates that even if charging and discharging are repeated with x being less than 0.24, the crystal structure is not easily collapsed, and excellent cycle characteristics can be achieved.

[0175] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, it is preferred that the peak of the bonding energy between fluorine and other elements is 682 eV or more and less than 685 eV, more preferably about 684.3 eV. This value is different from the bonding energy of lithium fluoride of 685 eV and the bonding energy of magnesium fluoride of 686 eV.

[0176] In addition, when the positive electrode active material 100 of one embodiment of the present invention is analyzed by XPS, it is preferred that the peak of the bonding energy between magnesium and other elements is 1302 eV or more and less than 1304 eV, and more preferably about 1303 eV. This value is different from the bonding energy of magnesium fluoride of 1305 eV, and is close to the bonding energy value of magnesium oxide.

[0177] <edx> One or two of the selected added elements contained in the positive electrode active material 100 preferably have a concentration gradient. In addition, the positive electrode active material 100 is more preferably different in depth from the surface according to the added element concentration peak. The concentration gradient of the added element can be evaluated by, for example, exposing the cross section of the positive electrode active material 100 by FIB (Focused Ion Beam) or the like and analyzing the cross section by energy dispersive X-ray spectroscopy (EDX: Energy Dispersive X-ray Spectroscopy), EPMA (Electron Probe Microanalysis), or the like.

[0178] In EDX measurement, the method of measuring while scanning in the region for two-dimensional evaluation is called EDX surface analysis. In addition, the method of evaluating the atomic concentration distribution in the positive electrode active material by linear scanning and measurement is called line analysis. Sometimes the method of extracting the data of the linear region from the surface analysis of EDX is called line analysis. In addition, the method of measuring without scanning is called point analysis.

[0179] By EDX surface analysis (e.g., element mapping), the concentration of added elements in the surface portion 100a, the interior 100b, and the vicinity of the grain boundary of the positive electrode active material 100 can be quantitatively analyzed. In addition, by EDX line analysis, the concentration distribution and maximum value of the added element can be analyzed. In addition, in the analysis after the sample is thinned, such as by FIB, the concentration distribution in the depth direction from the surface of the positive electrode active material in a specific area to the center can be analyzed without being affected by the distribution in the depth direction, so it is preferred.

[0180] Therefore, when the positive electrode active material 100 according to one embodiment of the present invention is subjected to EDX surface analysis or EDX point analysis, it can be confirmed that the concentration of each additional element, especially the additional element X, is higher in the surface layer portion 100 a than in the inner portion 100 b .

[0181] In STEM-EDX analysis, the element distribution does not change dramatically in principle or due to measurement errors, and it is sometimes difficult to strictly determine the surface. Therefore, when the depth direction is involved in STEM-EDX analysis, the value of the detected amount of the transition metal M is equal to the average value M of the detected amount inside. AVE and the background average M BG The point where 50% of the total or the value of oxygen detection is equal to the average value of the internal detection amount O AVE and the background average O BG The point where the total of the transition metal M and oxygen is 50% of the total of the background is taken as the reference point. In addition, it is considered that the fact that the points where the total of the transition metal M and oxygen are different from each other is due to the influence of metal oxides and carbonates containing oxygen attached to the surface, so the average value M of the detected amount inside the transition metal M can be used. AVE and the background average M BG When a positive electrode active material including a plurality of transition metals M is used, the M of the element with the largest count in the inner 100b can be used. AVE and M BG Determine the above reference point.

[0182] The average value of the cobalt background above M BG For example, it can be obtained by averaging the outside of the portion where the amount of cobalt detected begins to increase, that is, the range of 2 nm or more, preferably 3 nm or more. AVE The average value of the background value of oxygen can be obtained by averaging a range of 2 nm or more, preferably 3 nm or more, in a region where the counts of cobalt and oxygen are saturated and stable, such as from a region where the amount of cobalt detected begins to increase to a depth of 30 nm or more, preferably to a depth of 50 nm or more. BG and the average value of the detected amount of oxygen inside AVE It can also be found in the same way.

[0183] In addition, the surface of the positive electrode active material 100 in the cross-sectional STEM (scanning transmission electron microscope) image, etc. refers to: the boundary between the region where the image of the crystal structure derived from the positive electrode active material is observed and the region where the image is not observed, and refers to the outermost side of the region where the atomic column of the nucleus of the metal element having an atomic number greater than lithium in the metal element constituting the positive electrode active material is confirmed. Alternatively, the surface of the positive electrode active material 100 refers to: the intersection of the tangent drawn from the surface to the distribution of the brightness of the bulk in the STEM image and the axis in the depth direction. The surface in the STEM image, etc. can also be judged by referring to an analysis with a higher spatial resolution.

[0184] In addition, the peak in STEM-EDX line analysis refers to the maximum value of the detection intensity in each element distribution or the characteristic X-ray of each element. As noise in STEM-EDX line analysis, the measured value of the half width below the spatial resolution (R), for example, below R / 2, is considered.

[0185] For example, when performing EDX surface analysis or EDX point analysis on a positive electrode active material 100 containing magnesium as an added element, the magnesium concentration of the surface portion 100a is preferably higher than the magnesium concentration of the internal portion 100b. In addition, when performing EDX line analysis, the magnesium concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, the concentration of magnesium is preferably reduced to less than 60% of the peak concentration at a point from the peak top to a depth of 1nm. In addition, it is preferably reduced to less than 30% of the peak concentration at a point from the peak top to a depth of 2nm. The concentration peak described here is the maximum value of the concentration. In addition, due to the influence of the spatial resolution in EDX line analysis, the position of the magnesium concentration peak sometimes takes a negative value as a depth from the surface to the inside.

[0186] In the positive electrode active material 100 containing magnesium and fluorine as additive elements, the distribution of fluorine preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction between the fluorine concentration peak and the magnesium concentration peak is preferably within 10 nm, more preferably within 3 nm, and further preferably within 1 nm.

[0187] In addition, when performing EDX line analysis, the fluorine concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, the fluorine concentration peak is preferably slightly closer to the surface side than the magnesium concentration peak, and the resistance to fluorine is improved at this time, so it is preferred. For example, the fluorine concentration peak is preferably closer to the surface side by more than 0.5nm than the magnesium concentration peak, and more preferably closer to the surface side by more than 1.5nm than the magnesium concentration peak.

[0188] In addition, in the positive electrode active material 100 containing nickel as an added element, the nickel concentration peak of the surface portion 100a preferably appears within a depth range of 3nm from the surface of the positive electrode active material 100 to the center, more preferably within a depth range of 1nm, and further preferably within a depth range of 0.5nm. Alternatively, preferably within ±1nm from the surface. In addition, in the positive electrode active material 100 containing magnesium and nickel, the distribution of nickel preferably overlaps with the distribution of magnesium. For example, the difference in the depth direction of the nickel concentration peak and the magnesium concentration peak is preferably within 10nm, more preferably within 3nm, and further preferably within 1nm.

[0189] In addition, when the positive electrode active material 100 includes aluminum as an additive element, when performing EDX line analysis, the concentration peaks of magnesium, nickel or fluorine are closer to the surface than the aluminum concentration peak of the surface portion 100a. For example, the aluminum concentration peak preferably appears in the range of a depth of 0.5 nm or more and 50 nm or less from the surface of the positive electrode active material 100 to the center, and more preferably appears in the range of a depth of 3 nm or more and 30 nm or less.

[0190] In addition, when the positive electrode active material 100 is subjected to EDX line analysis, surface analysis or point analysis, the ratio of the number of atoms of magnesium Mg to cobalt Co in the magnesium concentration peak (Mg / Co) is preferably 0.05 or more and 0.6 or less, more preferably 0.1 or more and 0.4 or less. The ratio of the number of atoms of aluminum Al to cobalt Co in the aluminum concentration peak (Al / Co) is preferably 0.01 or more and 0.6 or less, more preferably 0.05 or more and 0.45 or less. The ratio of the number of atoms of nickel Ni to cobalt Co in the nickel concentration peak (Ni / Co) is preferably 0 or more and 0.2 or less, more preferably 0.01 or more and 0.1 or less, more preferably 0.05 or more and 0.1 or less. The ratio of the number of atoms of fluorine F to cobalt Co in the fluorine concentration peak (F / Co) is preferably 0 or more and 1.6 or less, more preferably 0.1 or more and 1.4 or less.

[0191] <Washing> In addition, various analyses are described as described above, and the samples of the positive electrode active material and the positive electrode active material layer can also be washed before the analysis to remove the electrolyte, binder, conductive material or compounds derived from them attached to the surface of the positive electrode active material. At this time, sometimes lithium dissolves in the solvent used for washing, but the added element is not easy to dissolve, so it has no effect on the atomic ratio of the added element.

[0192] <Electrolyte> As a mode of electrolyte, an electrolyte comprising a solvent and being dissolved in an electrolyte can be used. As a solvent, it is preferred to use an aprotic solvent, for example, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, vinyl chloride carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, ethylene glycol dimethyl ether (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme (methyl diglyme), acetonitrile, benzonitrile, tetrahydrofuran, cyclopentane sulfone, sultone etc. can be used, or two or more of the above can be used in any combination and ratio. When comprising two or more solvents, sometimes it is recorded as a mixed solvent.

[0193] As other forms of the electrolyte, one or more ionic liquids (room temperature molten salts) with flame retardancy and low volatility can be used as solvents. At this time, even if the internal temperature rises due to internal short circuit or overcharge of the storage device, the rupture and ignition of the storage device can be prevented. The ionic liquid is composed of cations and anions, including organic cations and anions. As organic cations for the electrolyte, aliphatic onium cations such as quaternary ammonium cations, tertiary sulfonium cations and quaternary phosphonium cations or aromatic cations such as imidazolium cations and pyridinium cations can be cited. In addition, as anions for the electrolyte, monovalent amide anions, monovalent methylated anions, fluorosulfonic acid anions, perfluoroalkyl sulfonic acid anions, tetrafluoroborate anions, perfluoroalkyl borate anions, hexafluorophosphate anions or perfluoroalkyl phosphate anions can be cited.

[0194] In addition, as an electrolyte (also referred to as a lithium salt) dissolved in the above solvent, for example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , one or more of the following lithium salts: LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, lithium bis(oxalate borate) (Li(C2O4)2, abbreviated as: LiBOB), etc.

[0195] In addition, additives can also be mixed in the mixed solvent in which the lithium salt is dissolved. As additives, vinylene carbonate, propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or dinitrile compounds such as succinonitrile and adiponitrile can be cited. The concentration of the additive can be set, for example, to occupy more than 0.1wt% and less than 5wt% in the mixed solvent in which the lithium salt is dissolved.

[0196] <Example 1 of Electrolyte Solution> The mixed solvent used in one embodiment of the present invention may be a material having good lithium ion conductivity even when charged and / or discharged (charge and discharge) in a low temperature environment (eg, 0°C, -20°C, preferably -30°C, more preferably -40°C).

[0197] An example of an electrolyte is described below. Note that the electrolyte described in this embodiment is an electrolyte in which a lithium salt is dissolved in a mixed solvent, and the mixed solvent is liquid at room temperature. Note that the mixed solvent is not limited to being liquid at room temperature, and a solid electrolyte that becomes solid at room temperature can also be used. Alternatively, a semi-solid electrolyte containing a liquid and a solid at room temperature can also be used. Semi-solid electrolytes include gel-like ones.

[0198] The mixed solvent of the electrolyte solution according to one embodiment of the present invention preferably contains two or more selected from the group consisting of fluorinated cyclic carbonates and fluorinated chain carbonates.

[0199] As fluorinated cyclic carbonate, fluorinated ethylene carbonate (fluorinated ethylene carbonate, FEC, F1EC), difluoroethylene carbonate (DFEC, F2EC), trifluoroethylene carbonate (F3EC) or tetrafluoroethylene carbonate (F4EC) etc. can be used. In addition, as DFEC, isomers such as cis-4,5, trans-4,5 can be cited. Any fluorinated cyclic carbonate has a substituent that exhibits electron-withdrawing property, so it is considered that the solvation energy of lithium ions is low.

[0200] The following structural formula (H10) is the structural formula of FEC. In FEC, the electron-withdrawing substituent is a F group.

[0201] [Chemical formula 1]

[0202] As a fluorinated chain carbonate, there is methyl 3,3,3-trifluoropropionate. The following structural formula (H22) is the structural formula of methyl 3,3,3-trifluoropropionate. Methyl 3,3,3-trifluoropropionate is abbreviated as "MTFP". In MTFP, the electron-withdrawing substituent is a CF3 group.

[0203] [Chemical formula 2]

[0204] As the fluorinated chain carbonate, there is trifluoromethyl 3,3,3-trifluoropropionate. The following structural formula (H23) is the structural formula of trifluoromethyl 3,3,3-trifluoropropionate. The electron-withdrawing substituent is a CF3 group.

[0205] [Chemical formula 3]

[0206] As a fluorinated chain carbonate, there is trifluoromethyl propionate. The following structural formula (H24) is the structural formula of trifluoromethyl propionate. The electron-withdrawing substituent is a CF3 group.

[0207] [Chemical formula 4]

[0208] As a fluorinated chain carbonate, there is methyl 2,2-difluoropropionate. The following structural formula (H25) is the structural formula of methyl 2,2-difluoropropionate. The electron-withdrawing substituent is the CF2 group.

[0209] [Chemical formula 5]

[0210] <FEC and MTFP> For example, the mixed solvent described in this embodiment preferably contains FEC and MTFP. The reasons are described below.

[0211] FEC is one of the cyclic carbonates. Because it has a high relative dielectric constant, it has the effect of promoting the dissociation of lithium salts when used in a mixed solvent. And, FEC has a substituent that exhibits electron-withdrawing properties, so it easily bonds to lithium ions through Coulomb force. Specifically, it can be said that the solvation energy of FEC is smaller than that of ethylene carbonate (abbreviated as "EC") that does not have a substituent exhibiting electron-withdrawing properties. Therefore, the bond between lithium ions and the solvent is easily broken, that is, it is easily desolvated. Furthermore, the highest occupied molecular orbital (HOMO) energy level of FEC is considered to be deep. When the HOMO energy level is deep, it is not easily oxidized and the oxidation resistance is improved. On the other hand, the viscosity of FEC is high. When only FEC is used as a solvent, it is difficult to use below the freezing point. Thus, the mixed solvent specifically described as one aspect of the present invention contains not only FEC but also MTFP. MTFP is one of the chain carbonates and has the effect of reducing or maintaining the viscosity of the electrolyte. Of course, the solvation energy of MTFP is also smaller than that of methyl propionate (abbreviated as "MP") that does not have a substituent exhibiting electron-withdrawing properties. Therefore, it may sometimes form solvation with lithium ions.

[0212] The following table shows the measured values of HOMO energy level, solvation energy, melting point, etc.

[0213] [Table 1]

[0214] It is preferred that the total content of the two mixed solvents FEC and MTFP having such physical properties is 100 vol%, and they are mixed and used in a volume ratio of x:100-x (note, 5≤x≤30, preferably 10≤x≤20). That is, it is preferred to mix in a way that there is more MTFP than FEC in the mixed solvent. Note that the above volume ratio can also be the volume ratio measured before the mixed solvents are mixed, and the external air when the mixed solvents are mixed can also be room temperature (typically 25°C). The mixed solvent mixed with FEC and MTFP has a viscosity that allows it to work as a lithium-ion secondary battery, and maintains an appropriate viscosity even in a low temperature environment, so it is preferred.

[0215] The general solvent used for lithium ion secondary batteries solidifies at about -20°C, so it is difficult to manufacture a lithium ion secondary battery that can be charged and discharged at -30°C, preferably -40°C. However, the mixed solvent described as an example in this embodiment can achieve a solidification point of below -30°C, preferably below -40°C, so that a lithium ion secondary battery that can be charged and discharged in a low temperature environment can be realized. As a result, a lithium ion secondary battery that can be charged and discharged in a wide temperature range including at least a low temperature environment can be realized.

[0216] In the above description, FEC is used as a representative, but it can be said that any organic compound described as a fluorinated cyclic carbonate has the effect of promoting the dissociation of lithium salts; the solvation energy is small and the bond between lithium ions and the solvent is easily cut; the viscosity is high, and it is difficult to use it below the freezing point when only the organic compound is used.

[0217] In addition, although in the above description, MTFP is described as representative, it can be said that any organic compound described as fluorinated linear carbonate all has the effect of reducing or maintaining the viscosity of the electrolyte of one mode of the present invention.Therefore, as long as the mixed solvent of one mode of the present invention comprises fluorinated cyclic carbonate and fluorinated linear carbonate, the lithium ion secondary battery that can be charged and discharged in the wider temperature range under low temperature environment can be provided.

[0218] <Example 2 of Electrolyte Solution> As a mixed solvent for an electrolyte in other embodiments of the present invention, when containing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC), a mixed solvent with a volume ratio of x:y:100 - x - y (note that 5 ≤ x ≤ 35 and 0 < y < 65) of the above ethylene carbonate, the above ethyl methyl carbonate, and the above dimethyl carbonate can be used in a state where the total content of the above ethylene carbonate, the above ethyl methyl carbonate, and the above dimethyl carbonate is 100 vol%. More specifically, a mixed solvent containing EC, EMC, and DMC in a volume ratio of EC:EMC:DMC = 30:35:35 (volume ratio) can be used. Note that the above volume ratio can also be the volume ratio before mixing the mixed solvent, and the external air when mixing the mixed solvent can also be at room temperature (typically 25°C).

[0219] EC is a cyclic carbonate. Because it has a high relative dielectric constant, it has the effect of promoting the dissociation of lithium salts. On the other hand, EC has a high viscosity and a high freezing point (melting point) of 38°C. Therefore, when using only EC as a solvent, it is difficult to use it in a low-temperature environment. Thus, the solvent specifically described in one embodiment of the present invention contains not only EC but also EMC and DMC. EMC is a chain carbonate, which has the effect of reducing the viscosity of the electrolyte, and its freezing point is -54°C. In addition, DMC is also a chain carbonate, which has the effect of reducing the viscosity of the electrolyte, and its freezing point is -43°C. The mixed solvent is mixed in such a way that the total content of the three mixed solvents of EC, EMC, and DMC with the above physical properties is 100 vol% and the volume ratio is x:y:100 - x - y (note that 5 ≤ x ≤ 35, 0 < y < 65). The electrolyte manufactured using the above mixed solvent has a characteristic that its freezing point is below -40°C.

[0220] The lowest freezing point of a general electrolyte for a lithium-ion secondary battery is about -20°C. Therefore, it is difficult to manufacture a battery that can be charged and discharged at -40°C. The freezing point of the electrolyte illustrated as an example in this embodiment is below -40°C. Thus, a lithium-ion secondary battery that can be charged and discharged even in an extremely low-temperature environment of -40°C can be realized.

[0221] In addition, as the lithium salt dissolved in the above solvent, a lithium salt can be used. For example, LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 、Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2 and lithium bis(oxalate borate) (LiBOB). The lithium salt dissolved in the above-mentioned solvent can be 0.5 mol / L or more and 1.5 mol / L or less, preferably 0.7 mol / L or more and 1.3 mol / L or less, and more preferably 0.8 mol / L or more and 1.2 mol / L or less, relative to the volume of the above-mentioned solvent. As a specific example of use, the volume of LiPF6 relative to the volume of the above-mentioned solvent can be 0.5 mol / L or more and 1.5 mol / L or less, preferably 0.7 mol / L or more and 1.3 mol / L or less, and more preferably 0.8 mol / L or more and 1.2 mol / L or less.

[0222] In addition, as a mixed solvent, it is preferred that the content of granular dust or elements other than the constituent elements of the electrolyte (hereinafter simply referred to as "impurities") is small and highly purified. Specifically, the ratio of impurities to the weight of the electrolyte is preferably 1% or less, more preferably 0.1% or less, and further preferably 0.01% or less.

[0223] In addition, in order to improve safety and other purposes, a film (Solid Electrolyte Interphase Film) is formed at the interface between the electrode (active material layer) and the electrolyte, and an additive such as vinylene carbonate (VC), propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), lithium bis(oxalate borate) (LiBOB) or a dinitrile compound of succinonitrile or adiponitrile may be added to the electrolyte. The concentration of the additive may be set to, for example, 0.1wt% or more and 5wt% or less in the solvent as a whole.

[0224] In the electrolyte example 2, the lithium salt may be the material described in the electrolyte example 1. In addition, the material described in the electrolyte example 1 may also be used as the additive.

[0225] An example of an electrolyte solution that can be used in a lithium ion secondary battery of one embodiment of the present invention is described above, but the electrolyte solution that can be used in a lithium ion secondary battery of one embodiment of the present invention is not limited to this example. Other materials can also be used as long as they are materials that have excellent lithium ion conductivity when charged and discharged in a low temperature environment.

[0226] [negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector, and the negative electrode active material layer contains a negative electrode active material.

[0227] <Adhesive> As a binder for the negative electrode of one embodiment of the present invention, a polymer having a carboxyl group is preferably used. The carboxyl group can also be said to contain two basic oxygens, one acidic hydrogen and one electrophilic carbon. The carboxyl group can also be said to be a polar group having a hydroxyl group OH and a carbonyl group C=O. When the binder has a polar group such as a carboxyl group, it is expected to interact with lithium ions as carrier ions, for example, lithium ions are attracted, so it is possible to contribute to the embedding of lithium ions in the negative electrode active material. In addition, the carboxyl group can be specified by FT-IR and the like.

[0228] As polymers having carboxyl groups, there are polyglutamic acid (sometimes denoted as PGA), polyacrylic acid (sometimes denoted as PAA) and alginic acid (sometimes denoted as polysaccharide). In addition, as polymers having carboxyl groups, polyamino acids may also be used, and specifically, polyornithine and polysarcosine may also be used as binders. Furthermore, as polymers having ketone groups, polyaspartic acid may also be used as binders. In addition, as polymers having ketone groups, binary copolymers (copolymers) may also be used, and copolymers of acrylic acid and maleic acid, and copolymers of acrylic acid and sulfonic acid may also be used as binders. By using these materials as binders for the negative electrode, there is also an effect of reducing the mixing amount of the binder in the negative electrode.

[0229] Among the above polymers, polyglutamic acid or polyacrylic acid is particularly preferred as a binder for the negative electrode. The structural formula of polyglutamic acid is shown below.

[0230] [Chemical formula 6]

[0231] As can be seen from the structural formula, polyglutamic acid contains nitrogen in addition to the carboxyl group, and this nitrogen has an unshared electron pair, so it is expected to interact with lithium ions as carrier ions. For example, it is also possible that this unshared electron pair attracts lithium ions and helps lithium ions to be embedded in the negative electrode active material.

[0232] In addition, as known from the structural formula, polyglutamic acid has C=O of carbonyl group in addition to carbonyl group. When the binder has a polar group such as carbonyl group, it is expected to interact with lithium ions as carrier ions, for example, and may contribute to the insertion and extraction of lithium ions in the negative electrode active material.

[0233] As polyglutamic acid, straight-chain γ-polyglutamic acid or cross-linked γ-polyglutamic acid can be applied to adhesives, and they are collectively referred to as structures with γ-polyglutamic acid as the main body. In addition, from the viewpoint of having a network structure, cross-linked γ-polyglutamic acid is suitable for adhesives. Furthermore, the molecular weight of polyglutamic acid is preferably more than 1,000,000, more preferably more than 3,000,000, and further preferably more than 10,000,000 and less than 50,000,000.

[0234] Depending on the method for producing polyglutamic acid, it can be said that the structure is mainly composed of γ-glutamic acid containing other elements (e.g., Ca, Al, Na, Mg, Fe, Si, S). In other words, polyglutamic acid can be neutralized with alkali metal ions such as lithium ions or sodium ions.

[0235] This polyglutamic acid is hydrophilic, so deionized water can be used as a solvent, which is very suitable when forming a slurry.

[0236] Next, the structural formula of polyacrylic acid is shown below.

[0237] [Chemical formula 7]

[0238] As can be seen from the structural formula, polyacrylic acid has a carboxyl group.

[0239] A material obtained by crosslinking polyacrylic acid may also be used. This is preferred because a crosslinked structure, that is, a network structure, can be formed, and thus the function as an adhesive may be improved.

[0240] <Negative Electrode Active Material> The negative electrode of one embodiment of the present invention comprises carbon particles and silicon particles as negative electrode active materials. As carbon particles, graphite, carbon having a layer structure like graphite, amorphous carbon, hard carbon, and carbon fiber are used. As carbon particles used in this specification, specifically, graphite particles are preferably used.

[0241] The average particle size of the graphite particles in one embodiment of the present invention is preferably 1 μm or more, more preferably 5 μm or more, further preferably 10 μm or more, and further preferably 20 μm or more. The graphite particles are preferably mixed with silicon particles and used for the negative electrode.

[0242] The average particle size of graphite particles can be measured by a particle size distribution instrument using a laser diffraction and scattering method. In this specification, etc., the average particle size of graphite particles can be used to obtain a median particle size (D50). The median particle size (D50) refers to the particle size when the cumulative amount of the cumulative particle amount curve in the particle size distribution measurement result accounts for 50%. The measurement of particle size is not limited to laser diffraction particle size distribution measurement, and the major diameter of the particle cross section can also be measured by analysis using SEM or TEM. In addition, as a method for measuring the median particle size (D50) by analysis using SEM or TEM, for example, more than 20 particles are measured and a cumulative particle amount curve is produced, and the particle size when its cumulative amount accounts for 50% is defined as the median particle size (D50).

[0243] The specific surface area of ​​the graphite particles is preferably 0.5 m 2 / g or more and 3m 2 / g or less. The specific surface area can be measured by the BET method. The specific surface area by the BET method is a value measured by the BET point method using nitrogen gas adsorption, and can be measured using an automatic specific surface area-porosity analyzer tristar II3020 (manufactured by Shimadzu Corporation) as a measuring machine.

[0244] As silicon particles, preferably use silicon particles with an average particle size of 100nm and its vicinity, which are sometimes referred to as nano silicon particles. The capacity of silicon is 4200mAh / g per unit weight, which is more than 10 times the capacity of graphite 372mAh / g (active material per unit weight), but silicon has the problem of rapid cycle degradation due to expansion and contraction during charge and discharge. Therefore, in order to improve cycle degradation, preferably use nano silicon particles that make silicon micronized to the above-mentioned average particle size.

[0245] The average particle size of silicon particles can be measured by a particle size distribution instrument using a laser diffraction and scattering method. In this specification, etc., the average particle size of silicon particles can be used to obtain a median particle size (D50). The median particle size (D50) refers to the particle size when the cumulative amount of the cumulative particle amount curve in the particle size distribution measurement result accounts for 50%. The measurement of particle size is not limited to laser diffraction particle size distribution measurement, and the major diameter of the particle cross section can also be measured by analysis using SEM or TEM. In addition, as a method for measuring the median particle size (D50) by analysis using SEM or TEM, for example, more than 20 particles are measured and a cumulative particle amount curve is prepared, and the particle size when the cumulative amount accounts for 50% is defined as the median particle size (D50).

[0246] The silicon particles are preferably crushed silicon raw materials and adjusted to a uniform particle size. By this adjustment, silicon particles with an average particle size of less than 1 μm can be obtained. Note that when the average particle size is large, the negative electrode active material layer may become thicker, so it can be said that the average particle size is preferably less than 1 μm. The silicon particles can be any silicon-based material, specifically, at least one of silicon, silicon oxide, and silicon alloy.

[0247] The specific surface area of ​​silicon particles is 10m 2 / g or more and 35m 2 / g or less, preferably 10m 2 / g or more and 15m 2 / g or less. The specific surface area can be measured by the BET method. The specific surface area by the BET method is a value measured by the BET point method using nitrogen gas adsorption, and can be measured using an automatic specific surface area-porosity analyzer tristar II3020 (manufactured by Shimadzu Corporation) as a measuring machine.

[0248] In one embodiment of the present invention, the negative electrode active material contains both graphite particles and silicon particles, so a lithium ion secondary battery with high discharge capacity can be realized. In addition, the average particle size of the graphite particles is different from the average particle size of the silicon particles, so by mixing them and using them for the negative electrode, the loading amount of the negative electrode active material can be increased. In this specification, the loading amount means the weight of the negative electrode active material per unit area of ​​the surface of the negative electrode current collector. The loading amount of the negative electrode active material can be calculated based on the capacity of the positive electrode. When the loading amount is small, the output characteristics of the lithium ion secondary battery can be improved, but when the loading amount is small, the discharge capacity is reduced. Therefore, the loading amount of the negative electrode active material is preferably 1.5 mg / cm 2 above.

[0249] In the negative electrode active material layer of one embodiment of the present invention, the weight ratio of the graphite particles is preferably greater than the weight ratio of the silicon particles. For example, the weight ratio of the graphite particles is preferably 5 times or more and 15 times or less than the weight ratio of the silicon particles. In other words, the weight ratio of silicon in the total weight of the powder material constituting the negative electrode active material is preferably set to 7.5wt% or more and 37.5wt% or less.

[0250] Alternatively, a conductive material may be added when the negative electrode active material layer is formed.

[0251] In lithium-ion secondary batteries, the negative electrode active material layer can be formed on one or both surfaces of the negative electrode current collector. The negative electrode active material layer is formed by applying a slurry on the negative electrode current collector and drying it.

[0252] Note that the weight ratio of each raw material in this specification can be regarded as the mixing ratio of each raw material when making the slurry. That is, the weight ratio of the negative electrode active material is the total weight of the negative electrode active material and the binder in the slurry or the mixing ratio (wt%) of the negative electrode active material in the total weight of the negative electrode active material, the binder and the conductive material. The weight ratio and mixing ratio can be understood by using a binder instead of a negative electrode active material.

[0253] The weight ratio of the binder is preferably smaller than the weight ratio of the graphite particles. In order to exert the effect of the binder, the weight ratio of the binder is preferably greater than 5 wt%.

[0254] <Method for producing negative electrode active material layer> Here, the method for manufacturing the negative electrode active material layer is described. The slurry of the negative electrode of one embodiment of the present invention is preferably mixed by adding a solvent after mixing graphite particles, silicon particles and a binder having a carboxyl group. In the slurry of one embodiment of the present invention, graphite particles, silicon particles and a binder having a carboxyl group can be mixed at the same time, so the process can be shortened, so it is preferred. Furthermore, in the manufacture of the slurry, graphite particles, silicon particles, a binder having a carboxyl group and a solvent can also be mixed at the same time. Furthermore, when forming the slurry, a conductive material can be mixed at the same time. Specific examples of conductive materials will be described later, and acetylene black (hereinafter referred to as AB) is preferably used.

[0255] The slurry obtained by the above steps is applied to one or both surfaces of the negative electrode current collector, dried, and pressed to produce a negative electrode active material layer. By using the negative electrode active material layer of one embodiment of the present invention, a lithium ion secondary battery with excellent cycle characteristics can be provided.

[0256] Note that it is preferable not to oxidize the silicon particles. For example, when preparing the slurry, it is also preferable to perform the mixing process so as not to oxidize the silicon particles.

[0257] The contents of this embodiment mode can be freely combined with the contents of other embodiment modes.

[0258] (Implementation Method 2) In this embodiment, a method for producing a positive electrode active material that can be used for a lithium ion secondary battery having excellent discharge characteristics even in a low-temperature environment is described with reference to FIGS. 8 to 10 .

[0259] <Example 1 of Method for Producing Positive Electrode Active Material> Reference FIG. 8A to FIG. 8D An example of a method for producing a positive electrode active material that can be used in one embodiment of the present invention (Example 1 of a method for producing a positive electrode active material) is described. Note that in <Example 1 of a method for producing a positive electrode active material>, the additional elements described as additional element X, additional element Y, and additional element Z in Embodiment 1 are collectively referred to as additional element A.

[0260] First, as step S10, lithium cobalt oxide used as a starting material is prepared. As the starting material, lithium cobalt oxide having a particle size (strictly speaking, a median particle size (D50)) of 12 μm or less (preferably 10 μm or less, more preferably 8 μm or less) can be used. As the lithium cobalt oxide having a median particle size (D50) of 12 μm or less, either known or publicly available (in short, commercially available) lithium cobalt oxide can be used, or lithium cobalt oxide obtained by Figure 8B The lithium cobalt oxide is manufactured by the steps S11 to S14 shown. As a typical example of commercially available lithium cobalt oxide with a median particle size (D50) of less than 12 μm, lithium cobalt oxide manufactured by Nippon Chemical Industry Co., Ltd. (trade name "CELLSEED C-5H") can be cited. The median particle size (D50) of the lithium cobalt oxide manufactured by Nippon Chemical Industry Co., Ltd. (trade name "CELLSEED C-5H") is approximately 7 μm. In addition, the following describes a method for manufacturing lithium cobalt oxide having a median particle size (D50) of less than 12 μm obtained through steps S11 to S14.

[0261] <Step S11> exist Figure 8B In step S11 shown in the figure, a lithium source (Li source) and a cobalt source (Co source) are prepared as starting materials of lithium and transition metal, respectively.

[0262] As the lithium source, a compound containing lithium is preferably used, for example, lithium carbonate, lithium hydroxide, lithium nitrate, lithium fluoride, etc. The purity of the lithium source is preferably high, for example, a material with a purity of 99.99% or more is preferably used.

[0263] As the cobalt source, a compound containing cobalt is preferably used, for example, cobalt tetraoxide, cobalt hydroxide, etc. The purity of the cobalt source is preferably high, for example, it is preferred to use a material with a purity of 3N (99.9%) or more, preferably 4N (99.99%) or more, more preferably 4N5 (99.995%) or more, and further preferably 5N (99.999%) or more. By using a high-purity material, impurities in the positive electrode active material can be controlled. As a result, the capacity of the secondary battery is improved and the reliability of the secondary battery is improved.

[0264] <Step S12> Then, as Figure 8B In step S12 shown, the lithium source and the cobalt source are crushed and mixed to produce a mixed material. The crushing and mixing can be performed by a dry method or a wet method. When the crushing and mixing are performed by a wet method, the powder can be ground smaller, so in order to obtain lithium cobalt oxide with a median particle size (D50) of less than 10 μm as a starting material, a wet method is preferred. When the crushing and mixing are performed by a wet method, a solvent is prepared. As a solvent, ketones such as acetone, alcohols such as ethanol and isopropanol, ether, dioxane, acetonitrile, N-methyl-2-pyrrolidone (NMP), etc. can be used. It is preferred to use a non-protonic solvent that is not easy to react with lithium. In this embodiment, dehydrated acetone with a purity of 99.5% or more is used. Preferably, the dehydrated acetone with a moisture content suppressed to less than 10 ppm and a purity of more than 99.5% is mixed with a lithium source and a transition metal source for crushing and mixing. By using dehydrated acetone of the above purity, impurities that may be mixed can be reduced.

[0265] <Step S13> Then, as Figure 8B In step S13 shown, the mixed material is heated. The heating temperature is preferably 800°C to 1100°C, more preferably 900°C to 1000°C, and further preferably about 950°C to 1000°C. When the temperature is too low, there is a concern that the decomposition and melting of the lithium source and the transition metal source are insufficient. On the other hand, when the temperature is too high, defects may occur due to the following reasons: lithium evaporates from the lithium source; and / or cobalt is excessively reduced; etc. For example, cobalt changes from trivalent to divalent, causing oxygen defects, etc.

[0266] When the heating time is too short, lithium cobalt oxide is not synthesized, but when the heating time is too long, the productivity decreases. Therefore, the heating time can be from 1 hour to 100 hours, preferably from 2 hours to 20 hours, and more preferably from 2 hours to 10 hours.

[0267] Although it varies depending on the temperature to be reached by the heating temperature, the heating rate is preferably 80° C. / h or more and 250° C. / h or less. For example, when heating at 1000° C. for 10 hours, the heating rate is preferably 200° C. / h.

[0268] The heating is preferably performed in an atmosphere with less water such as dry air, for example, preferably in an atmosphere with a dew point of -50°C or less, more preferably in an atmosphere with a dew point of -80°C or less. In the present embodiment, the heating is performed in an atmosphere with a dew point of -93°C. In addition, in order to suppress impurities that may be mixed into the material, the impurity concentrations of CH4, CO, CO2, H2, etc. in the heating atmosphere are preferably all below 5 ppb (parts per billion).

[0269] The heating atmosphere is preferably an oxygen-containing atmosphere. For example, a method of continuously introducing dry air into the reaction chamber can be cited. In this case, the flow rate of the dry air is preferably 10 L / min. A method of continuously introducing oxygen into the reaction chamber so that the oxygen flows through the reaction chamber is called "flowing".

[0270] When an oxygen-containing atmosphere is used as the heating atmosphere, a non-flowing method may also be used. For example, a method of first depressurizing the reaction chamber and then filling it with oxygen to prevent the oxygen from entering or leaving the reaction chamber may be used. This method is called purging. For example, the reaction chamber may be depressurized to -970 hPa, and then continued to be filled with oxygen until the pressure reaches 50 hPa.

[0271] After heating, the mixture may be cooled naturally, and the cooling time from the specified temperature to room temperature is preferably in the range of 10 hours to 50 hours. Note that it is not necessarily necessary to cool to room temperature, but only to a temperature allowed by the next step.

[0272] The heating in this step can be performed using a rotary kiln or a roller hearth kiln. Heating using a continuous or batch-type rotary kiln can be performed while stirring.

[0273] The container used for heating is preferably an alumina crucible or an alumina sagger. The alumina crucible is a material that is almost free of impurities. In this embodiment, an alumina sagger with a purity of 99.9% is used. In addition, heating the crucible or sagger after covering it with a lid can prevent the volatilization of the material, so it is preferred.

[0274] After the heating is completed, the mixture may be ground and screened as needed. In addition, the heating conditions similar to those in step S13 may be adopted in the heating process described later other than step S13.

[0275] <Step S14> Through the above steps, it is possible to synthesize Figure 8B The lithium cobalt oxide (LiCoO2) shown in step S14 is an oxide containing multiple metal elements in its structure, so it can be called a composite oxide. In this specification, "composite oxide" refers to an oxide containing multiple metal elements in its structure. In addition, a grinding process and a classification process can be performed after step S13 to adjust the particle size distribution, and then the lithium cobalt oxide (LiCoO2) shown in step S14 can be obtained.

[0276] As shown in steps S11 to S14, an example of producing the composite oxide by a solid phase method is shown, but the composite oxide may also be produced by a coprecipitation method. Alternatively, the composite oxide may also be produced by a hydrothermal method.

[0277] After step S11 to step S14, lithium cobaltate can be obtained, which is a starting material for obtaining a positive electrode active material for a lithium ion secondary battery that has excellent discharge characteristics even in a low temperature environment. Specifically, the lithium cobaltate used as the starting material can obtain lithium cobaltate with a median particle size (D50) of less than 10 μm.

[0278] <Step S15> Then, as Fig. 8A In step S15 shown, lithium cobalt oxide, which is a starting material, is heated. The heating in step S15 is the first heating of lithium cobalt oxide, so it is sometimes referred to as initial heating in this specification, etc. In addition, this heating is also performed before step S31 shown below, so it is sometimes referred to as preheating treatment or pretreatment.

[0279] The lithium compounds and the like that unintentionally remain on the surface of the lithium cobalt oxide are detached due to the initial heating. In addition, the effect of improving the internal crystallinity can be expected. In addition, the lithium source and / or the cobalt source prepared in step S11 and the like are sometimes mixed with impurities, but by performing the initial heating, the impurities in the lithium cobalt oxide that is the starting material can be reduced. In addition, the effect of improving the internal crystallinity refers to, for example, the effect of alleviating the skewness, deviation, etc. caused by the difference in shrinkage of the lithium cobalt oxide manufactured in step S14.

[0280] After the initial heating, the surface of the lithium cobalt oxide is smoothed. In addition, after the initial heating, the cracks and crystal defects of the lithium cobalt oxide are also alleviated. In this specification, the surface "smooth" means: there are fewer bumps and the composite oxide is curved as a whole, and the corners are curved. Alternatively, the state with fewer foreign matter attached to the surface is also called "smooth". It can be considered that foreign matter is the cause of bumps and bumps, and it is preferred that foreign matter is not attached to the surface.

[0281] Note that when performing this initial heating, it is not necessary to separately prepare materials used as a lithium compound source, an additional element source, or a flux.

[0282] When the heating time of this step is too short, a sufficient effect cannot be obtained, but when the heating time is too long, the productivity decreases. The range of appropriate heating time can be selected from the heating conditions described in step S13 and implemented. In addition, in order to maintain the crystal structure of the composite oxide, the heating temperature of step S15 is preferably lower than the temperature of step S13. In addition, in order to maintain the crystal structure of the composite oxide, the heating time of step S15 is preferably shorter than the heating time of step S13. For example, it is preferred to heat at a temperature of 700°C or more and 1000°C or less (more preferably 800°C or more and 900°C or less) for more than 1 hour and less than 20 hours (more preferably 1 hour or more and less than 5 hours).

[0283] In lithium cobalt oxide, a temperature difference sometimes occurs between the surface and the inside of the lithium cobalt oxide after the heating in step S13. Sometimes the temperature difference causes a shrinkage difference. It can also be considered that the shrinkage difference occurs because the fluidity between the surface and the inside is different according to the temperature difference. Due to the energy related to the shrinkage difference, a difference in internal stress occurs in the lithium cobalt oxide. The difference in internal stress is also called distortion, and this energy is sometimes called distortion energy. It can be considered that the internal stress is removed after the initial heating in step S15, in other words, the distortion energy is uniformized after the initial heating in step S15. When the distortion energy is uniformized, the distortion of the lithium cobalt oxide is alleviated. Therefore, the surface of the lithium cobalt oxide becomes smooth. It can also be said that the surface is improved. In other words, it can be considered that after step S15, the shrinkage difference generated in the lithium cobalt oxide is alleviated, so that the surface of the composite oxide can be smoothed.

[0284] In addition, the shrinkage difference sometimes leads to the generation of small deviations in the lithium cobalt oxide, such as the generation of crystal deviations. In order to reduce the deviation, step S15 is preferably performed. After step S15, the deviation of the composite oxide can be uniformed (relaxing the deviation of crystals etc. generated in the composite oxide or arranging the grains). As a result, the surface of the composite oxide may become smooth.

[0285] In addition, as described above, in step S10, lithium cobalt oxide having a pre-synthesized median particle size (D50) of 12 μm or less, preferably 10 μm or less, and more preferably 8 μm or less may be used. In this case, steps S11 to S13 may be omitted. It is effective to perform step S15 on pre-synthesized lithium cobalt oxide, thereby obtaining lithium cobalt oxide with a smooth surface, so it is a preferred step.

[0286] Note that step S15 is not a structure that must exist in one embodiment of the present invention, so an embodiment in which step S15 is omitted is also included in one embodiment of the present invention.

[0287] <Step S20> Next, refer to Figure 8C and Fig.8D The details of step S20 of preparing to add element A as an A source will be described.

[0288] <Step S21> Figure 8C The step S20 shown includes steps S21 to S23. In step S21, an additive element A is prepared. As specific examples of the additive element A, one or more selected from magnesium, fluorine, nickel, aluminum, titanium, zirconium, vanadium, iron, manganese, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, and boron can be used. In addition, one or more selected from bromine and beryllium can also be used. Figure 8C An example is shown in which a magnesium source (Mg source) and a fluorine source (F source) are prepared. Note that in step S21, in addition to adding the element A, a lithium source may be prepared separately.

[0289] When magnesium is selected as the additive element A, the source of the additive element A may be referred to as a magnesium source. As the magnesium source, magnesium fluoride (MgF2), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), or magnesium carbonate (MgCO3) may be used. A plurality of magnesium sources may also be used.

[0290] When fluorine is selected as the additive element A, the source of the additive element A may be referred to as a fluorine source. As the fluorine source, for example, lithium fluoride (LiF), magnesium fluoride (MgF2), aluminum fluoride (AlF3), titanium fluoride (TiF4), cobalt fluoride (CoF2, CoF3), nickel fluoride (NiF2), zirconium fluoride (ZrF4), vanadium fluoride (VF5), manganese fluoride, iron fluoride, chromium fluoride, niobium fluoride, zinc fluoride (ZnF2), calcium fluoride (CaF2), sodium fluoride (NaF), potassium fluoride (KF), barium fluoride (BaF2), cerium fluoride (CeF3, CeF4), lanthanum fluoride (LaF3) or sodium aluminum hexafluoride (Na3AlF6) may be used. Among them, lithium fluoride has a relatively low melting point of 848°C and is easily melted in the heating step described later, so it is preferred.

[0291] Magnesium fluoride can be used as both a fluorine source and a magnesium source. In addition, lithium fluoride can also be used as a lithium source. As another lithium source used in step S21, lithium carbonate can be cited.

[0292] Alternatively, the fluorine source may be a gas, and fluorine (F2), carbon fluoride, sulfur fluoride, or oxyfluoride (OF2, O2F2, O3F2, O4F2, O5F2, O6F2, O2F) or the like may be mixed in the atmosphere in the heating step described later.

[0293] In this embodiment, lithium fluoride (LiF) is prepared as a fluorine source, and magnesium fluoride (MgF2) is prepared as a fluorine source and a magnesium source. Here, when the melting point of a fluorine compound such as lithium fluoride (sometimes also referred to as a fluoride) is lower than the melting point of other additive element sources, the fluorine compound can be used as a flux (also referred to as a solvent) to lower the melting point of other additive element sources. When the fluorine compound includes LiF and MgF2, such as Fig.11 (Cited and modified from Non-Patent Document 1 Figure 5 ), the eutectic point of LiF and MgF2 is around 742°C (T1), so in the heating process after mixing and adding elements (step S33 described later, etc.), the heating temperature is preferably above 742°C.

[0294] Here, use Fig.12 Differential Scanning Calorimetry (DSC) measurements performed on fluorine compounds and mixtures are described. Fig.12 The mixture is prepared by mixing lithium cobalt oxide as the lithium oxide and LiF and MgF2 as the fluorine compounds, and the mixture is mixed in a ratio of LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio). Fig.12 The fluorine compound in the mixture is a mixture of LiF and MgF2. More specifically, the mixture is mixed in a manner of LiF:MgF2=1:3 (molar ratio).

[0295] like Fig.12 As shown in FIG. 1 , an endothermic peak is observed at around 735°C in the fluorine compound. In addition, an endothermic peak is observed at around 830°C in the mixture. Therefore, the heating temperature after mixing and adding the elements (step S33 described later, etc.) is preferably 742°C or higher, more preferably 830°C or higher. In addition, it can also be 800°C ( Fig.11 T2) or above.

[0296] In addition, when lithium fluoride and magnesium fluoride are mixed at a molar ratio of about LiF:MgF2=65:35, it is most effective in lowering the melting point. In addition, when the ratio of lithium fluoride is too large, lithium becomes excessive and may cause deterioration of the cycle characteristics. For this reason, the molar ratio of lithium fluoride and magnesium fluoride is preferably LiF:MgF2=x:1 (0≤x≤1.9), more preferably LiF:MgF2=x:1 (0.1≤x≤0.5), and further preferably LiF:MgF2=x:1 (x=0.33 or its vicinity). Note that when not specifically stated in this specification, etc., "nearby" refers to a value greater than 0.9 times and less than 1.1 times the value.

[0297] <Step S22> Then, in Figure 8C In step S22 shown in the figure, the magnesium source and the fluorine source are pulverized and mixed. This step can be carried out by selecting the conditions for pulverization and mixing described in step S12.

[0298] <Step S23> Then, in Figure 8C In step S23, the pulverized and mixed materials are collected to obtain a source of the additive element A (source A). The source of the additive element A shown in step S23 includes a plurality of starting materials and can also be called a mixture.

[0299] The median particle size (D50) of the particle size of the above mixture is preferably 100 nm or more and 10 μm or less, more preferably 300 nm or more and 5 μm or less. The median particle size (D50) when using one material as the source of the added element A is also preferably 100 nm or more and 10 μm or less, more preferably 300 nm or more and 5 μm or less.

[0300] When the mixture (including the case where there is only one additive element) that has been micronized in step S22 is mixed with lithium cobalt oxide in a subsequent step, the mixture can be easily uniformly attached to the surface of the lithium cobalt oxide. When the mixture is uniformly attached to the surface of the lithium cobalt oxide, it is easy to uniformly distribute or diffuse the additive element in the surface layer portion 100a of the composite oxide after heating, which is preferred.

[0301] <Step S21> use Fig.8D Description and Figure 8C Different processes. Fig.8D The illustrated step S20 includes steps S21 to S23.

[0302] exist Fig.8D In step S21 shown, four sources of additive elements A are prepared to be added to lithium cobalt oxide. That is, Fig.8D The type of source of added element A and Figure 8C In addition, a lithium source may be prepared separately in addition to the element A source.

[0303] As four sources of additive elements A, a magnesium source (Mg source), a fluorine source (F source), a nickel source (Ni source) and an aluminum source (Al source) are prepared. The magnesium source and the fluorine source can be obtained from Figure 8C As the nickel source, nickel oxide, nickel hydroxide, etc. can be used. As the aluminum source, aluminum oxide, aluminum hydroxide, etc. can be used.

[0304] <Step S22> and <Step S23> then, Fig.8D The steps S22 and S23 shown in FIG. Figure 8C The same applies to step S22 and step S23 described in .

[0305] <Step S31> Then, in Fig. 8A In step S31, the lithium cobalt oxide and the additive element A source (Mg source) that have passed step S15 (initial heating) are mixed. Here, the ratio of the number of atoms Co of cobalt in the lithium cobalt oxide that has passed step S15 to the number of atoms Mg of magnesium in the additive element A is preferably Co:Mg=100:y (0.1≤y≤6), and more preferably Co:Mg=100:y (0.3≤y≤3). When the additive element A is added to the lithium cobalt oxide that has passed the initial heating, the additive element A can be added uniformly. Therefore, it is preferred that the order is not to perform initial heating (step S15) after adding the additive element A, but to add the additive element A after the initial heating (step S15).

[0306] In addition, when nickel is selected as the additive element A, the mixing in step S31 is preferably performed in such a manner that the number of nickel atoms in the nickel source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15. In addition, when aluminum is selected as the additive element A, the mixing in step S31 is preferably performed in such a manner that the number of aluminum atoms in the aluminum source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15.

[0307] In order not to damage the shape of the lithium cobalt oxide particles, the mixing of step S31 is preferably performed under milder conditions than the crushing-mixing of step S12. For example, it is preferred to adopt conditions with fewer rotations or shorter time than the mixing of step S12. In addition, it can be said that the dry method is a milder condition than the wet method. Mixing can be performed using, for example, a ball mill, a sand mill, etc. When a ball mill is used, it is preferred to use, for example, zirconia balls as the medium.

[0308] In the present embodiment, the mixing is performed by a dry method at 150 rpm for 1 hour using a ball mill using zirconia balls having a diameter of 1 mm. The mixing is performed in a dry room having a dew point of -100°C or higher and -10°C or lower.

[0309] <Step S32> Then, in Fig. 8A In step S32, the mixed materials are recovered to obtain a mixture 903. When recovered, the materials may be screened after being crushed as needed.

[0310] <Step S33> Then, in Fig. 8A In step S33 shown, the mixture 903 is heated. The heating of step S33 is preferably performed at a temperature of 800°C to 1100°C, more preferably 800°C to 950°C, and further preferably 850°C to 900°C. In addition, the heating time of step S33 may be 1 hour to 100 hours, preferably 1 hour to 10 hours. The lower limit of the heating temperature of step S33 needs to be above the temperature at which the reaction of lithium cobalt oxide and the source of the additive element A progresses. The temperature at which the reaction progresses may be set to the temperature at which mutual diffusion of the elements contained in the source of the additive element A occurs, and may also be lower than the melting point of the above-mentioned material. Taking the oxide as an example, from the melting point T m 0.757 times (Taman temperature T d ) solid phase diffusion begins to occur, so the heating temperature in step S33 can be set above 500°C.

[0311] Of course, the reaction is more likely to proceed when the temperature is set to be above the temperature at which one or more of the materials selected from the mixture 903 are melted. For example, when LiF and MgF2 are included as the source of the additive element A, the eutectic point of LiF and MgF2 is around 742°C as described above, so the lower limit of the heating temperature in step S33 is preferably set to 742°C or above.

[0312] As described above, in differential scanning calorimetry (DSC measurement), an endothermic peak of the mixture 903 obtained by mixing LiCoO2:LiF:MgF2=100:0.33:1 (molar ratio) was observed at around 830° C. Therefore, the lower limit of the heating temperature is more preferably set to 830° C. or more.

[0313] A higher heating temperature is preferred because the reaction proceeds more easily, the heating time is shortened, and the productivity is improved.

[0314] The upper limit of the heating temperature is set to be lower than the decomposition temperature of lithium cobalt oxide (1130°C). At a temperature near the decomposition temperature, slight decomposition of lithium cobalt oxide may occur. Therefore, the heating temperature is preferably 1000°C or lower, more preferably 950°C or lower, and further preferably 900°C or lower.

[0315] When the mixture 903 is heated, the partial pressure of fluorine or fluoride derived from the fluorine source or the like is preferably controlled within an appropriate range.

[0316] In the manufacturing method described in this embodiment, some materials such as LiF as a fluorine source are sometimes used as a flux. Through the above function, the heating temperature can be reduced to a temperature lower than the decomposition temperature of lithium cobalt oxide, for example, above 742°C and below 950°C, and additive elements such as magnesium can be distributed in the surface layer, thereby manufacturing a positive electrode active material with good characteristics.

[0317] However, the specific gravity of LiF in the gas state is lighter than that of oxygen, so LiF may volatilize by heating, and when LiF volatilizes or sublimates, the LiF in the mixture 903 decreases. In this case, the function of LiF as a flux is reduced. Therefore, it is preferable to heat while suppressing the volatilization or sublimation of LiF.

[0318] Therefore, it is preferable to heat the mixture 903 in an atmosphere containing LiF, that is, to heat the mixture 903 in a state where the partial pressure of LiF in the heating furnace is high. By heating as described above, volatilization or sublimation of LiF in the mixture 903 can be suppressed.

[0319] The heating in this step is preferably performed in a manner that does not cause the mixture 903 to adhere together. When the mixture 903 adheres together during heating, the area of ​​the particles in contact with oxygen in the atmosphere is reduced, and the diffusion path of the added element (such as fluorine) is blocked, so that the added element (such as magnesium and fluorine) may not be easily distributed in the surface layer.

[0320] In addition, when the added element (such as fluorine) is evenly distributed in the surface layer, a smooth and less uneven positive electrode active material can be obtained. Therefore, in order to maintain the smooth state of the surface heated by step S15 or further smoothen it in this process, it is preferred not to make the mixture 903 bonded together.

[0321] When heating is performed using a roller kiln, for example, by covering the container containing the mixture 903 with a lid, the mixture 903 can be heated in a LiF-containing atmosphere.

[0322] <Step S34> Then, in Fig. 8A In step S34 shown, the heated material is recovered to obtain the positive electrode active material 100. At this time, it can also be ground as needed, and it is preferred that the recovered positive electrode active material 100 is also screened. Through the above process, a positive electrode active material 100 (composite oxide) with a median particle size (D50) of 12 μm or less (preferably 10 μm or less, more preferably 8 μm or less) can be manufactured. Note that the positive electrode active material 100 contains the added element A.

[0323] <Example 2 of Method for Producing Positive Electrode Active Material> Reference Fig. 9 FIG. 10 illustrates another example of a method for producing a positive electrode active material that can be used as one embodiment of the present invention (Example 2 of the method for producing a positive electrode active material). In Example 2 of the method for producing a positive electrode active material, the number of times the additional element is added and the mixing method are different from those in Example 1 of the method for producing a positive electrode active material, but other records can refer to the records in Example 1 of the method for producing a positive electrode active material. Note that in <Example 2 of the method for producing a positive electrode active material>, the additional element X described in Implementation Example 1 is represented as additional element A1. In addition, the additional element Y and the additional element Z described in Implementation Example 1 are collectively referred to as additional element A2.

[0324] exist Fig. 9 In, with Fig. 8A Similarly, step S10 and step S15 are performed to prepare lithium cobalt oxide that has been initially heated. Note that step S15 is not an essential structure in one embodiment of the present invention, so an embodiment in which step S15 is omitted is also included in one embodiment of the present invention.

[0325] <Step S20a> Next, as shown in step S20a, a first additional element A1 source (A1 source) is prepared. Fig. 10A The details of step S20a will be described.

[0326] <Step S21> exist Fig. 10A Step S21 shown in the figure is to prepare a first added element A1 source (A1 source). As the A1 source, it can be obtained from Figure 8C The additive element A1 is selected from the additive element A1 described in step S21. For example, any one or more selected from magnesium, fluorine and calcium can be used as the additive element A1. Fig. 10A An example is shown in which a magnesium source (Mg source) and a fluorine source (F source) are used as the additive element A1.

[0327] exist Fig. 10A Steps S21 to S23 shown in FIG. 1 can be performed by Figure 8C The same conditions are applied to steps S21 to S23 as shown. As a result, the added element A1 source (A1 source) can be obtained in step S23.

[0328] in addition, Fig. 9 Steps S31 to S33 shown can be performed with Fig. 8A The same conditions are applied to steps S31 to S33 shown.

[0329] <Step S34a> Next, the material heated in step S33 is recovered to obtain lithium cobalt oxide containing the additive element A1. Here, in order to distinguish it from the lithium cobalt oxide (first composite oxide) after step S15, it is also referred to as a second composite oxide.

[0330] <Step S40> exist Fig. 9 In step S40, a second source of the added element A2 (A2 source) is prepared. Fig. 10B and Fig. 10C Step S40 is described.

[0331] <Step S41> exist Fig. 10B Step S40 shown in the figure is to prepare a second added element A2 source (A2 source). As the A2 source, it can be obtained from Figure 8C The additive element A2 is selected from the additive element A described in step S20. For example, any one or more selected from nickel, titanium, boron, zirconium and aluminum can be suitably used as the additive element A2. Fig. 10B An example is shown in which a nickel source and an aluminum source are used as the additional element A2.

[0332] Fig. 10B Steps S41 to S43 shown in FIG. Figure 8C The same conditions are applied to steps S21 to S23 as shown. As a result, the added element A2 source (A2 source) can be obtained in step S43.

[0333] Fig. 10C Steps S41 to S43 shown are Fig. 10B An example of a deformation of . Fig. 10C In step S41, a nickel source (Ni source) and an aluminum source (Al source) are prepared, and they are crushed independently in step S42a. As a result, a plurality of second additional element A2 sources (A2 sources) are prepared in step S43. Fig. 10C Step S40 and Fig. 10B The difference of step S40 is that the additional element source is pulverized independently in step S42a.

[0334] <Step S51 to Step S53> then, Fig. 9 Steps S51 to S53 shown in FIG. Fig. 8A The conditions of step S53 of the heating process are preferably the same as those of step S31 to step S34. Fig. 9 The temperature of step S33 is lower or / and the time is shorter than that shown in the figure. Specifically, the heating temperature is preferably 800°C to 950°C, more preferably 820°C to 870°C, and further preferably 850°C±10°C. The heating time is, for example, preferably 0.5 hours to 8 hours, more preferably 1 hour to 5 hours.

[0335] Note that when nickel is selected as the additive element A2, the mixing in step S51 is preferably performed in such a manner that the number of nickel atoms in the nickel source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15. In addition, when aluminum is selected as the additive element A2, the mixing in step S51 is preferably performed in such a manner that the number of aluminum atoms in the aluminum source is 0.05% or more and 4% or less of the number of cobalt atoms in the lithium cobalt oxide after step S15.

[0336] <Step S54> Then, in Fig. 9 In step S54 shown, the heated material is recovered to obtain the positive electrode active material 100. The recovered material may also be ground as needed. Through the above process, a positive electrode active material 100 (composite oxide) having a median particle size (D50) of 12 μm or less (preferably 10 μm or less, more preferably 8 μm or less) can be manufactured. In addition, a positive electrode active material 100 that can be used for a lithium ion secondary battery having excellent discharge characteristics even in a low temperature environment can be manufactured. The positive electrode active material 100 contains an additive element A1 and an additive element A2.

[0337] In the manufacturing method example 2 described above, as Fig. 9 As shown in FIG. 10 , the additive elements are divided into a first additive element A1 and a second additive element A2 and introduced into lithium cobalt oxide. By introducing the additive elements separately, the distribution of each additive element can be changed. For example, the first additive element can be distributed in a manner that the concentration in the surface portion is higher than that in the interior, and the second additive element can be distributed in a manner that the concentration in the interior portion is higher than that in the surface portion. Fig. 8A and Fig.8D The positive electrode active material 100 manufactured by the steps of adding multiple additive elements A sources together has the advantage of being able to be manufactured at low cost. Fig. 9 10 manufactures the positive electrode active material 100 by adding a plurality of additive element A sources in a plurality of steps, so the manufacturing cost is relatively high, but the distribution of each additive element A in the depth direction can be more accurately controlled, so it is preferred.

[0338] This embodiment mode can be used in combination with other embodiment modes as desired.

[0339] (Implementation 3) In this embodiment, Fig.13 An example of a production process of a negative electrode active material layer for a lithium ion secondary battery is shown.

[0340] First, graphite particles 200, silicon particles 201, a binder 202, and a conductive material 203 are prepared. A polymer having a carboxyl group is used as the binder.

[0341] <Step S60> Weigh the above raw materials separately and Fig.13 The first mixing of step S60. Specifically, the weight ratio of the silicon particles 201 to the total weight of the powders mixed in the first mixing is in the range of 7.5wt% to 37.5%, and the weight ratio of the binder 202 to the total weight is in the range of 10wt% to 50wt%. In addition, the weight ratio of the conductive material 203 to the total weight is in the range of 0wt% to 20wt%. In addition, as the conductive material 203 satisfying the above weight ratio, AB is preferably used.

[0342] For example, the weight ratio of silicon particles 201, graphite particles 200, binder 202, and conductive material 203 is 3:5:1:1. Alternatively, without using a conductive material, for example, the weight ratio of silicon particles 201, graphite particles 200, and binder 202 is 3:5:1. Alternatively, the weight ratio of graphite particles 200, silicon particles 201, and binder 202 may be 9:1:1.

[0343] <Mixing of mixture 204 and solvent 205> In one embodiment of the present invention, in step S60, the raw materials are all powders, so they are mixed before adding the solvent to obtain the mixture 204. When the powders are mixed with each other, they can be mixed uniformly. Then, preferably, a solvent 205 is added. Deionized water is preferably used as the solvent 205.

[0344] <Step S61> After adding the solvent 205, Fig.13 The second mixing of step S61 is performed to form slurry 206. The second mixing is sometimes also referred to as slurry conditioning.

[0345] The slurry 206 is a material liquid used to form an active material layer on a current collector, and contains at least an active material, a binder, and a solvent, and preferably also contains a conductive material. The slurry is sometimes referred to as an electrode slurry or an active material slurry.

[0346] And, as Fig.13 In step S62, the slurry 206 is applied on the negative electrode current collector 207. Then, as Fig.13 The drying is performed in step S63. Pre-drying and main drying may be performed as drying conditions. That is, two drying steps are performed, and the conditions of the former drying step are milder than those of the latter. For example, drying may be performed in a dryer at a temperature of 40°C to 60°C for 10 minutes to 1 hour, which may be used as pre-drying. Next, as main drying, drying may be performed in a dryer at a temperature of 60°C to 90°C for 30 minutes to 1.5 hours. Pressing may also be performed while drying.

[0347] After drying, as Fig.13 The pressing process is performed in step S64. A roller press can be used for the pressing process, and the temperature of the upper and lower rollers can be above 100° C. and below 150° C. That is, heating can also be performed while the pressing process is performed. The linear pressure during pressing is preferably above 0.3 MPa and below 1 MPa. Of course, even if the pressing process is omitted, it can also be made to work as a lithium ion secondary battery.

[0348] Through the above steps, the negative electrode 208 including the negative electrode active material layer on the negative electrode current collector 207 can be manufactured.

[0349] The lithium ion secondary battery using the negative electrode 208 obtained as described above has a large discharge capacity and excellent cycle characteristics.

[0350] <Attachment to Isolator> When the negative electrode 208 shown in this embodiment is assembled as a lithium-ion secondary battery, the negative electrode 208 and the separator are bonded together. At this time, by dripping solvents such as deionized water on the negative electrode 208 or the separator, the adhesion of the adhesive, specifically the adhesion of PGA, is presented on the bonding surface.

[0351] <Semi-solid battery> The negative electrode 208 described in this embodiment is also expected to be applied to a semi-solid battery. For example, by gelling a mixed solvent for an electrolyte solution using a gelling agent or the like, a semi-solid battery including the binder of one embodiment of the present invention, specifically PGA, can be realized.

[0352] The contents of this embodiment mode can be freely combined with the contents of other embodiment modes.

[0353] (Implementation 4) In this embodiment, elements constituting a lithium ion secondary battery are described.

[0354] [positive electrode] The positive electrode includes a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and may further contain at least one of a conductive material and a binder. As the positive electrode active material, the material described in Embodiment 1 may also be used.

[0355] <Positive Electrode Current Collector> The positive electrode current collector may be, for example, a metal foil. The positive electrode may be formed by applying a slurry on a metal foil and drying it. Alternatively, the slurry may be pressed after drying. In the positive electrode, an active material layer is formed on the positive electrode current collector 21 .

[0356] As the current collector, materials with high conductivity such as stainless steel, gold, platinum, aluminum, titanium and other metals and their alloys can be used. In addition, the material used for the positive electrode current collector is preferably not dissolved due to the potential of the positive electrode. In addition, aluminum alloys to which elements such as silicon, titanium, neodymium, scandium, molybdenum, etc. that improve heat resistance are added can be used. In addition, metal elements that react with silicon to form silicides can also be used. As metal elements that react with silicon to form silicides, there are zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, nickel, etc. As the current collector, shapes such as foil, plate, sheet, mesh, punched metal mesh, and drawn metal mesh can be appropriately used. The thickness of the current collector is preferably 5 μm or more and 30 μm or less.

[0357] [negative electrode] The negative electrode includes a negative electrode active material layer and a negative electrode current collector. In addition, the negative electrode active material layer may also include a negative electrode active material and further include a conductive material and a binder.

[0358] <Negative Electrode Active Material> As the negative electrode active material, for example, an alloy material or a carbon material can be used.

[0359] As the negative electrode active material, an element that can perform a charge and discharge reaction by alloying / de-alloying reaction with lithium can be used. For example, a material containing at least one selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium and indium can be used. The capacity of this element is higher than that of carbon, and in particular the theoretical capacity of silicon is high, with a unit weight of 4200 mAh / g. Therefore, silicon is preferably used for the negative electrode active material. In addition, compounds containing these elements can also be used. For example, SiO, Mg2Si, Mg2Ge, SnO, SnO2, Mg2Sn, SnS2, V2Sn3, FeSn2, CoSn2, Ni3Sn2, Cu6Sn5, Ag3Sn, Ag3Sb, Ni2MnSb, CeSb3, LaSn3, La3Co2Sn7, CoSb3, InSb and SbSn can be cited. Here, an element capable of performing a charge-discharge reaction through an alloying / de-alloying reaction with lithium, a compound containing the element, and the like are sometimes referred to as an alloy-based material.

[0360] In this specification, "SiO" refers to silicon monoxide, for example. Alternatively, SiO may also be represented as SiO x Here, x preferably represents a value of 1 or a value close to 1. For example, x is preferably 0.2 or more and 1.5 or less, and preferably 0.3 or more and 1.2 or less.

[0361] As the carbon material, graphite, easily graphitizable carbon (soft carbon), hardly graphitizable carbon (hard carbon), carbon fiber (carbon nanotube), graphene, carbon black, or the like can be used.

[0362] As graphite, artificial graphite or natural graphite can be cited. As artificial graphite, for example, mesocarbon microbeads (MCMB), coke-based artificial graphite, pitch-based artificial graphite, etc. can be cited. Here, spherical graphite with a spherical shape can be used as artificial graphite. For example, MCMB sometimes has a spherical shape, so it is preferred. In addition, MCMB is relatively easy to reduce its surface area, so it is sometimes preferred. As natural graphite, for example, flaky graphite, spheroidized natural graphite, etc. can be cited.

[0363] When lithium ions are intercalated in graphite (when lithium-graphite intercalation compounds are generated), graphite shows a potential as low as that of lithium metal (0.05 V or more and 0.3 V or less vs. Li / Li + ). As a result, lithium-ion secondary batteries using graphite can show high operating voltages. Graphite also has the following advantages: large capacity per unit volume; relatively small volume expansion; relatively cheap; and higher safety than lithium metal, so it is preferred.

[0364] In addition, as the negative electrode active material, oxides such as titanium dioxide (TiO2), lithium titanium oxide (Li4Ti5O 12 ), lithium-graphite intercalation compound (Li x C6), niobium pentoxide (Nb2O5), tungsten dioxide (WO2), molybdenum dioxide (MoO2), etc.

[0365] In addition, as the negative electrode active material, Li 3N type structure containing lithium and transition metal nitride can be used. 3-x M x N (M = Co, Ni, Cu). For example, Li 2.6 Co 0.4 N shows a large charge and discharge capacity (unit weight is 900mAh / g, 1890mAh / cm 3 ), so it is preferred.

[0366] When a nitride containing lithium and a transition metal is used, lithium ions are contained in the negative electrode active material, so it can be combined with a material that does not contain lithium ions, such as V2O5 and Cr3O8, which is used as a positive electrode active material, and is therefore preferred. Note that when a material containing lithium ions is used as a positive electrode active material, a nitride containing lithium and a transition metal can also be used as a negative electrode active material by previously removing the lithium ions contained in the positive electrode active material.

[0367] In addition, materials that cause conversion reactions can also be used as negative electrode active materials. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), can be used as negative electrode active materials. Materials that cause conversion reactions can also include oxides such as Fe2O3, CuO, Cu2O, RuO2, and Cr2O3, CoS 0.89 , sulfides such as NiS, CuS, nitrides such as Zn3N2, Cu3N, Ge3N4, phosphides such as NiP2, FeP2, CoP3, fluorine compounds such as FeF3, BiF3.

[0368] <Negative Electrode Current Collector> As the negative electrode current collector, copper or the like may be used in addition to the same materials as the positive electrode current collector. Note that metals that alloy with lithium ions, such as aluminum, cannot be used as the negative electrode current collector.

[0369] <Adhesive> The positive electrode and the negative electrode contain a binder. The binder that exerts a specific effect for the negative electrode is as described in Embodiments 1 to 3. Of course, the binder that exerts a specific effect can also be used for the positive electrode.

[0370] As adhesives other than the adhesives described in Embodiments 1 to 3, rubber materials such as styrene-butadiene rubber (SBR), styrene-isoprene-styrenerubber, acrylonitrile-butadiene rubber, butadiene rubber, and ethylene-propylene-diene copolymer are preferably used. Fluororubber can also be used as an adhesive.

[0371] In addition, as an adhesive, it is preferred to use materials such as polystyrene, polymethyl acrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose.

[0372] In addition, it is preferred to use a thickener in addition to the binder. As the thickener, for example, a water-soluble polymer is preferably used. As the water-soluble polymer, for example, polysaccharides can also be used. As the polysaccharide, cellulose derivatives such as carboxymethyl cellulose (CMC), methyl cellulose, ethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, and regenerated cellulose, starch, etc. can be used.

[0373] Note that the above-mentioned adhesive may be a comparative example of the adhesive that exhibits a specific effect described in Embodiments 1 to 3 and the like.

[0374] When the binder covers the surface of the active material or forms a film with the binder in contact with the surface, it can be used as a passivation film, and is expected to exert an effect of inhibiting the decomposition of the electrolyte. Here, "passivation film" is a film that has no conductivity or very low conductivity. For example, when the passivation film is formed on the surface of the active material, it inhibits the decomposition of the electrolyte at the battery reaction potential. More preferably, the passivation film can transmit lithium ions while inhibiting conductivity.

[0375] <Conductive Materials> The conductive material used for the positive electrode and the negative electrode is also called a conductive agent or a conductive material, and a carbon material is used. By attaching the conductive material between multiple active materials, multiple active materials are electrically connected to each other and the conductivity is improved. Note that "attachment" does not mean that the active material and the conductive material are physically in close contact, but refers to a concept that includes the following situations: when a covalent bond occurs; when bonded by van der Waals force; when the conductive material covers a part of the surface of the active material; when the conductive material is inserted into the surface unevenness of the active material; when they are electrically connected without contact, etc.

[0376] As the conductive material, for example, any one or two or more of carbon black such as acetylene black (AB) and furnace black, graphite such as artificial graphite and natural graphite, carbon fiber such as carbon nanofiber and carbon nanotube, graphene and graphene compounds can be used.

[0377] AB is difficult to form surface contact with other active materials, but is easy to form point contact. Therefore, when mixing active materials and AB, more AB is used to reduce contact resistance, but the ratio of active materials is reduced, resulting in a reduction in the discharge capacity of the secondary battery. In addition, AB is a material that is easy to aggregate, and it is preferably uniformly dispersed using a dispersant or the like to form a slurry.

[0378] In view of the above problems, in the negative electrode, the weight ratio of AB is preferably less than or equal to the weight ratio of silicon particles used for the negative electrode active material. In other words, by satisfying this weight ratio, AB can be mixed in a manner that exhibits high dispersibility without reducing the proportion of silicon particles. Thus, the discharge capacity of the secondary battery can be increased.

[0379] As the carbon fiber, for example, mesophase pitch carbon fiber, isotropic pitch carbon fiber, etc. can be used. In addition, as the carbon fiber, carbon nanofibers or carbon nanotubes can be used. For example, carbon nanotubes can be produced by vapor phase growth, etc. VGCF (registered trademark) can also be used as the carbon fiber.

[0380] The above-mentioned graphene includes graphene, multi-layer graphene, multi-graphene, etc. In addition, the above-mentioned graphene compound includes graphene oxide, multi-layer graphene oxide, multi-graphene oxide, reduced graphene oxide, reduced multi-layer graphene oxide, reduced multi-graphene oxide, graphene quantum dots, etc. Graphene refers to a compound containing carbon and having a two-dimensional structure formed by a six-membered ring of carbon atoms in a flat plate, sheet, etc. In addition, the two-dimensional structure formed by the six-membered ring composed of carbon atoms can be called a carbon sheet. In addition, graphene has rigidity and preferably has a curved shape. The graphene compound can have holes in the carbon ring and can have a ring greater than 6, and can also have a functional group. In addition, since the graphene compound is flexible, it can be curled up like a carbon nanofiber, for example.

[0381] Graphene or graphene compounds can form surface contact with active materials, so less than general conductive materials are required. Therefore, the ratio of active materials in the active material layer can be increased. Thus, the discharge capacity of the secondary battery can be increased.

[0382] Carbon fiber forms a surface contact with the active material, but the major axis is longer than the minor axis, so it can play an appropriate electrical path between the active materials separated from each other, so the amount of carbon fiber is less than that of general conductive materials. Therefore, the ratio of the active material in the active material layer can be increased. Thus, the discharge capacity of the secondary battery can be increased.

[0383] [Electrolyte] Both the positive electrode and the negative electrode contain an electrolyte solution. As the electrolyte solution, the electrolyte solution described in Embodiment 1 can be used.

[0384] [Isolated Body] A separator is disposed between the positive electrode and the negative electrode. As the separator, for example, the following materials can be used: a material formed of a fiber containing cellulose such as paper, a nonwoven fabric, glass fiber, ceramic, or a synthetic fiber such as nylon (polyamide), vinylon (polyvinyl alcohol fiber), polyester, acrylic resin, polyolefin, or polyurethane. The separator is preferably processed into a bag shape and disposed so as to surround either the positive electrode or the negative electrode.

[0385] The separator may have a multilayer structure. For example, a ceramic material, a fluorine material, a polyamide material or a mixture thereof may be coated on a thin film of an organic material such as polypropylene or polyethylene. As a ceramic material, for example, aluminum oxide particles or silicon oxide particles may be used. As a fluorine material, for example, PVDF or polytetrafluoroethylene may be used. As a polyamide material, for example, nylon or aromatic polyamide (meta-aramid or para-aramid) may be used.

[0386] By coating ceramic materials, the oxidation resistance is improved, thereby suppressing the degradation of the separator during high voltage charge and discharge, thereby improving the reliability of the secondary battery. By coating fluorine materials, it is easy to make the separator close to the electrode, which can improve the output characteristics. By coating polyamide materials (especially aromatic polyamide), the heat resistance is improved, thereby improving the safety of the secondary battery.

[0387] For example, a mixture of aluminum oxide and aramid may be applied to both sides of a polypropylene film. Alternatively, a mixture of aluminum oxide and aramid may be applied to the surface of the polypropylene film in contact with the positive electrode and a fluorine-based material may be applied to the surface in contact with the negative electrode.

[0388] By adopting a separator with a multi-layer structure, the safety of the secondary battery can be ensured even if the total thickness of the separator is small, and thus the capacity per unit volume of the secondary battery can be increased.

[0389] [Outer packaging] As the outer packaging body included in the secondary battery, for example, a metal material such as aluminum or a resin material can be used. In addition, a film-shaped outer packaging body can also be used. As the film, for example, a three-layer film can be used: a metal film with excellent flexibility such as aluminum, stainless steel, copper, nickel, etc. is arranged on a film composed of materials such as polyethylene, polypropylene, polycarbonate, ionomer, polyamide, etc., and an insulating synthetic resin film such as polyamide resin, polyester resin, etc. can also be arranged on the metal film as the outer surface of the outer packaging body.

[0390] (Implementation 5) In this embodiment, an example of the shape of a secondary battery that can include the above-mentioned positive electrode active material which is one embodiment of the present invention is described.

[0391] [Coin-type secondary battery] An example of a coin-type secondary battery will be described. Fig.14A This is an exploded perspective view of a coin-type (single-layer flat) secondary battery. Fig. 14B This is its appearance picture. Fig. 14C Coin-type secondary batteries are mainly used in small electronic devices.

[0392] In order to easily understand the overlapping relationship (upper and lower relationship and position relationship) of components, Fig.14A A schematic diagram is used. Therefore, Fig.14A Not with Fig. 14B Exactly the same picture.

[0393] exist Fig.14A In the embodiment, the positive electrode 304, the separator 310, the negative electrode 307, the spacer 322, and the gasket 312 are stacked. Then, the negative electrode can 302, the positive electrode can 301, and the gasket are used to seal the above components. Fig.14A The gasket used for sealing is not shown. The spacer 322 and the gasket 312 are used to protect the inside or fix the position inside the tank when the positive electrode tank 301 and the negative electrode tank 302 are pressed together. The spacer 322 is made of stainless steel or insulating material. The gasket 312 is made of conductive material.

[0394] A stacked structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305 is referred to as a positive electrode 304 .

[0395] Fig. 14B It is a perspective view of the manufactured coin-type secondary battery.

[0396] In the coin-type secondary battery 300, a positive electrode can 301 serving as a positive terminal and a negative electrode can 302 serving as a negative terminal are insulated and sealed by a gasket 303 formed of polypropylene or the like. A positive electrode 304 is formed of a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with the positive electrode current collector 305. A negative electrode 307 is formed of a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with the negative electrode current collector 308. The negative electrode 307 is not limited to a laminated structure, and a lithium metal foil or an alloy foil of lithium and aluminum may be used.

[0397] In the positive electrode 304 and the negative electrode 307 used in the coin-type secondary battery 300 , the active material layer may be formed on one surface of the positive electrode and the negative electrode, respectively.

[0398] As the positive electrode can 301 and the negative electrode can 302, metals such as nickel, aluminum, and titanium, alloys thereof, and alloys of these and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, etc., the positive electrode can 301 and the negative electrode can 302 are preferably covered with nickel, aluminum, etc. The positive electrode can 301 is electrically connected to the positive electrode 304, and the negative electrode can 302 is electrically connected to the negative electrode 307.

[0399] By immersing the negative electrode 307, the positive electrode 304 and the separator 310 in an electrolyte, Fig. 14C As shown, the positive electrode can 301 is placed at the bottom, the positive electrode 304, the separator 310, the negative electrode 307 and the negative electrode can 302 are stacked in order, and the positive electrode can 301 and the negative electrode can 302 are pressed with the gasket 303 interposed therebetween to manufacture the coin-type secondary battery 300.

[0400] By using the structure described in the above embodiment for the above negative electrode, positive electrode, electrolyte solution, etc., a coin-type secondary battery having excellent discharge capacity even in a low-temperature environment can be realized.

[0401] [Cylindrical secondary battery] Next, refer to Fig.15A An example of a cylindrical secondary battery will be described. Fig.15A As shown, the top surface of the cylindrical secondary battery 616 includes a positive electrode cover (battery cover) 601, and the side and bottom surfaces thereof include a battery can (outer can) 602. The positive electrode cover 601 and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0402] Fig. 15B It is a diagram schematically showing a cross section of a cylindrical secondary battery. Fig. 15B The cylindrical secondary battery shown has a positive electrode cover (battery cover) 601 on the top surface and a battery can (outer can) 602 on the side and bottom surfaces. The positive electrode cover and the battery can (outer can) 602 are insulated by a gasket (insulating gasket) 610.

[0403] A battery element is provided inside the hollow cylindrical battery can 602, in which a strip-shaped positive electrode 604 and a strip-shaped negative electrode 606 are wound around a separator 605. Although not shown, the battery element is wound around the central axis. One end of the battery can 602 is closed and the other end is open. As the battery can 602, metals such as nickel, aluminum, titanium, their alloys, and alloys of them and other metals (such as stainless steel, etc.) that are resistant to corrosion by the electrolyte can be used. In addition, in order to prevent corrosion caused by the electrolyte, the battery can 602 is preferably covered with nickel, aluminum, etc. On the inside of the battery can 602, the battery element in which the positive electrode, the negative electrode, and the separator are wound is sandwiched by a pair of opposing insulating plates 608 and insulating plates 609. In addition, an electrolyte (not shown) is injected into the interior of the battery can 602 in which the battery element is provided. As the electrolyte, the same electrolyte as that of a coin-type secondary battery can be used.

[0404] Since the positive electrode and the negative electrode used for the cylindrical storage battery are wound, the active material is preferably formed on both surfaces of the current collector.

[0405] By using the structure described in the above embodiment for the above negative electrode, positive electrode, electrolyte solution, etc., a cylindrical secondary battery having excellent discharge capacity even in a low temperature environment can be realized.

[0406] The positive electrode 604 is connected to the positive terminal (positive electrode current collecting wire) 603, and the negative electrode 606 is connected to the negative terminal (negative electrode current collecting wire) 607. The positive terminal 603 can be made of a metal material such as aluminum. The negative terminal 607 can be made of a metal material such as copper. The positive terminal 603 is resistance-welded to the safety valve mechanism 613, and the negative terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cover 601 through a PTC (Positive Temperature Coefficient) element 611. When the internal pressure of the battery rises to exceed a specified threshold, the safety valve mechanism 613 cuts off the electrical connection between the positive electrode cover 601 and the positive electrode 604. In addition, the PTC element 611 is a thermally sensitive resistance element whose resistance increases when the temperature rises, and limits the current by increasing the resistance to prevent abnormal heating. As a PTC element, barium titanate (BaTiO3)-based semiconductor ceramics, etc. can be used.

[0407] Fig. 15C An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616. The positive electrode of each secondary battery contacts a conductor 624 separated by an insulator 625, and the positive electrodes are electrically connected to each other. The conductor 624 is electrically connected to a control circuit 620 via a wiring 623. In addition, the negative electrode of each secondary battery is electrically connected to the control circuit 620 via a wiring 626. As the control circuit 620, a charge and discharge control circuit for performing charge and discharge, a protection circuit for preventing overcharge and / or overdischarge, etc. can be used.

[0408] Fig.15D An example of a power storage system 615 is shown. The power storage system 615 includes a plurality of secondary batteries 616, and the plurality of secondary batteries 616 are sandwiched between a conductive plate 628 and a conductive plate 614. The plurality of secondary batteries 616 are electrically connected to the conductive plate 628 and the conductive plate 614 through a wiring 627. The plurality of secondary batteries 616 may be connected in parallel or in series, or may be connected in parallel and then in series. By configuring the power storage system 615 including the plurality of secondary batteries 616, a large amount of electric power can be obtained.

[0409] A plurality of secondary batteries 616 may be connected in parallel and then connected in series.

[0410] In addition, a temperature control device may be included between the plurality of secondary batteries 616. When the secondary battery 616 is overheated, it can be cooled by the temperature control device, and when the secondary battery 616 is overcooled, it can be heated by the temperature control device. Therefore, the performance of the power storage system 615 is not easily affected by the external temperature.

[0411] In addition, Fig.15D In FIG. 6 , the power storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. The wiring 621 is electrically connected to the positive electrodes of the plurality of secondary batteries 616 via the conductive plate 628, and the wiring 622 is electrically connected to the negative electrodes of the plurality of secondary batteries 616 via the conductive plate 614.

[0412] [Other structural examples of secondary batteries] An example of the structure of a secondary battery will be described using FIG. 16 and FIG. 17 .

[0413] Fig.16A The secondary battery 913 shown includes a winding body 950 provided with a terminal 951 and a terminal 952 inside a frame 930. The winding body 950 is impregnated with an electrolyte inside the frame 930. The terminal 952 is in contact with the frame 930, and the terminal 951 is not in contact with the frame 930 due to an insulating material or the like. Note that for convenience, although Fig.16A 930 is shown as a separate frame 930 in the figure, but in reality, the winding body 950 is covered by the frame 930, and the terminals 951 and 952 extend outside the frame 930. Considering the gas permeability, a metal material (such as aluminum, etc.) or a metal material and a resin material can be used as the frame 930. As long as it is a sealing part of the frame 930, a resin material can be used.

[0414] In addition, if Fig. 16B As shown, multiple materials can also be used to form Fig.16A For example, in the frame 930 shown in FIG. Fig. 16B In the secondary battery 913 shown, a frame body 930 a and a frame body 930 b are bonded together, and a wound body 950 is provided in a region surrounded by the frame bodies 930 a and 930 b.

[0415] In consideration of gas permeability, the frame body 930a may be made of a metal material (eg, aluminum) or a metal material and an organic resin. In consideration of gas permeability, the frame body 930b may be made of a metal material (eg, aluminum) or a metal material and an organic resin.

[0416] Furthermore, Fig. 16C The structure of the wound body 950 is shown. The wound body 950 includes a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is formed by overlapping the negative electrode 931 and the positive electrode 932 with the separator 933 interposed therebetween to form a laminated sheet, and then winding the laminated sheet. In addition, a plurality of layers of the negative electrode 931, the positive electrode 932, and the separator 933 may be stacked.

[0417] Alternatively, a secondary battery 913 including a wound body 950 a as shown in FIG. 17 may be used. Fig.17A The wound body 950a shown includes a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 includes a negative electrode active material layer 931a. The positive electrode 932 includes a positive electrode active material layer 932a.

[0418] By using the structure described in the above embodiment for the above negative electrode, positive electrode, electrolyte solution, etc., a secondary battery having excellent discharge capacity even in a low-temperature environment can be realized.

[0419] The separator 933 is wider than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap the negative electrode active material layer 931a and the positive electrode active material layer 932a. In addition, from the viewpoint of safety, it is preferable that the negative electrode active material layer 931a is wider than the positive electrode active material layer 932a. In addition, the winding body 950a of the above shape is preferable because of its good safety and productivity.

[0420] like Fig. 17B As shown, the negative electrode 931 is electrically connected to the terminal 951 by ultrasonic bonding, welding or pressing. The terminal 951 is electrically connected to the terminal 911a. In addition, the positive electrode 932 is electrically connected to the terminal 952 by ultrasonic bonding, welding or pressing. The terminal 952 is electrically connected to the terminal 911b.

[0421] like Fig. 17C As shown, the wound body 950a and the electrolyte are covered by the frame 930 to form a secondary battery 913. The frame 930 is preferably provided with a safety valve, an overcurrent protection element, etc. The safety valve is a valve that is opened at a specified internal pressure in the frame 930 to prevent battery rupture.

[0422] like Fig. 17B As shown, the secondary battery 913 may also include a plurality of winding bodies 950a. By using a plurality of winding bodies 950a, a secondary battery 913 with a larger discharge capacity can be realized. Fig.17A and Fig. 17B The other components of the secondary battery 913 shown can be referred to FIG. 16A to FIG. 16C The secondary battery 913 is shown.

[0423] <Laminated secondary battery> then, Fig.18A and Fig.18B 1 is an external view showing an example of a laminated secondary battery. Fig.18A and Fig.18B A positive electrode 503 , a negative electrode 506 , a separator 507 , an outer package 509 , a positive electrode lead electrode 510 , and a negative electrode lead electrode 511 are all shown.

[0424] Fig.19A It is an appearance diagram of a positive electrode 503 and a negative electrode 506. The positive electrode 503 includes a positive electrode current collector 501, and a positive electrode active material layer 502 is formed on the surface of the positive electrode current collector 501. In addition, the positive electrode 503 has an area where the positive electrode current collector 501 is partially exposed (hereinafter referred to as a tab area). The negative electrode 506 includes a negative electrode current collector 504, and a negative electrode active material layer 505 is formed on the surface of the negative electrode current collector 504. In addition, the negative electrode 506 has an area where the negative electrode current collector 504 is partially exposed, namely, the tab area. The area or shape of the tab area of ​​the positive electrode and the negative electrode is not limited to Fig.19A Example shown.

[0425] By using the structure described in the above embodiment for the above negative electrode, positive electrode, electrolyte solution, etc., a laminated secondary battery having excellent discharge capacity even in a low temperature environment can be realized.

[0426] <Method for manufacturing laminated secondary battery> Here, refer to Fig.19B and Fig.19C Yes Fig.18A An example of a method for producing a laminated secondary battery whose appearance is shown in FIG. 1 is described below.

[0427] First, the negative electrode 506, the separator 507, and the positive electrode 503 are stacked. Fig.19B The stacked negative electrode 506, separator 507 and positive electrode 503 are shown. Here, an example using 5 sets of negative electrodes and 4 sets of positive electrodes is shown. In addition, it can also be said that it is a stacked body composed of negative electrodes, separators, and positive electrodes. Next, the tab regions of the positive electrode 503 are joined to each other, and the positive electrode lead electrode 510 is joined to the tab region of the outermost positive electrode. As the joining, ultrasonic welding or the like can be used, for example. Similarly, the tab regions of the negative electrode 506 are joined to each other, and the negative electrode lead electrode 511 is joined to the tab region of the outermost negative electrode.

[0428] Next, the negative electrode 506 , the separator 507 , and the positive electrode 503 are arranged on the outer packaging body 509 .

[0429] Below, as Fig.19C As shown, the outer package 509 is folded along the portion indicated by the dotted line. Then, the outer periphery of the outer package 509 is joined. As the joining method, for example, heat pressing or the like can be used. At this time, in order to inject the electrolyte later, a non-joined area (hereinafter referred to as the introduction port) is provided on a part (or one side) of the outer package 509.

[0430] Next, the electrolyte is introduced into the inner side of the outer packaging body 509 from the introduction port provided in the outer packaging body 509. The electrolyte is preferably introduced under a reduced pressure atmosphere or an inert gas atmosphere. Finally, the introduction port is joined. In this way, the laminated secondary battery 500 can be manufactured.

[0431] (Implementation method 6) In this embodiment, an example of a vehicle equipped with a secondary battery according to one embodiment of the present invention is described.

[0432] As a vehicle, a secondary battery can typically be used in a car. As a car, a new generation of clean energy vehicles such as a hybrid electric vehicle (HV), an electric vehicle (EV) or a plug-in hybrid electric vehicle (also referred to as PHEV or PHV) can be cited, and a secondary battery can be used as one of the power sources installed in the car. Vehicles are not limited to cars. For example, as a vehicle, a tram, a monorail, a ship, a submarine (submersible, unmanned submarine), a flying object (helicopter, unmanned aircraft (drone), airplane, rocket, satellite), an electric bicycle, an electric motorcycle, etc. can be cited, and a secondary battery including one embodiment of the present invention can be applied to these vehicles.

[0433] In the electric vehicle, there are provided first batteries 1301a and 1301b as secondary batteries for main driving, and a second battery 1311 for supplying power to an inverter 1312 for starting an engine 1304. The second battery 1311 is also called a cranking battery (also called a starting battery). The second battery 1311 only needs to have a high output and does not need to have a high capacity. In addition, the capacity of the second battery 1311 is smaller than that of the first batteries 1301a and 1301b.

[0434] The internal structure of the first battery 1301a can be either Fig. 16C or Fig.17A The winding type shown can also be used Fig.18A or Fig.18B The stacked type shown. In addition, the first battery 1301a may also use the all-solid-state battery of Embodiment 6. By using the all-solid-state battery of Embodiment 6 as the first battery 1301a, a high capacity can be achieved, safety is improved, and miniaturization and weight reduction can be achieved.

[0435] In this embodiment, an example of connecting the first battery 1301a and 1301b in parallel is shown, but more than three batteries may be connected in parallel. In addition, as long as sufficient power can be stored in the first battery 1301a, the first battery 1301b may not be provided. By forming a battery pack with multiple secondary batteries, a larger amount of power can be taken out. Multiple secondary batteries may be connected in parallel, in series, or in series after being connected in parallel. Sometimes multiple secondary batteries are referred to as battery packs.

[0436] In order to cut off the power from the plurality of secondary batteries, the vehicle-mounted secondary battery includes a charging plug or a circuit breaker that can cut off the high voltage without using a tool, which is provided in the first battery 1301a.

[0437] In addition, the power of the first battery 1301a, 1301b is mainly used to rotate the engine 1304, and the power is also supplied to the 42V series vehicle-mounted components (electric power steering system 1307, heater 1308, defogger 1309, etc.) through the DCDC circuit 1306. In the case where the rear wheel includes a rear engine 1317, the first battery 1301a is used to rotate the rear engine 1317.

[0438] Furthermore, the second battery 1311 supplies power to 14V series vehicle-mounted components (audio 1313 , power windows 1314 , lights 1315 , etc.) via the DCDC circuit 1310 .

[0439] Next, use Fig. 20A The first battery 1301a is described.

[0440] Fig. 20A An example of using nine rectangular secondary batteries 1300 as a battery pack 1415 is shown. In addition, the nine rectangular secondary batteries 1300 are connected in series and one electrode is fixed using a fixing portion 1413 formed of an insulator and the other electrode is fixed using a fixing portion 1414 formed of an insulator. In this embodiment, an example of fixing using fixing portions 1413 and 1414 is shown, but it can also be stored in a battery storage box (also referred to as a frame). Assuming that the vehicle is vibrated or shaken from the outside (road surface, etc.), it is preferable to use fixing portions 1413, 1414 and a battery storage box to fix multiple secondary batteries. In addition, one electrode is electrically connected to the control circuit unit 1320 via wiring 1421. In addition, the other electrode is electrically connected to the control circuit unit 1320 via wiring 1422.

[0441] Alternatively, a memory circuit including a transistor using an oxide semiconductor may be used as the control circuit portion 1320. A charge control circuit or a battery control system including a memory circuit including a transistor using an oxide semiconductor is sometimes referred to as a BTOS (Battery operating system or Battery oxide semiconductor).

[0442] It is preferred to use a metal oxide used as an oxide semiconductor. For example, as a metal oxide, it is preferred to use an In-M-Zn oxide (the element M is selected from one or more of aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten and magnesium). In particular, the In-M-Zn oxide that can be applied to the metal oxide is preferably CAAC-OS (C-Axis Aligned Crystal Oxide Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). In addition, In-Ga oxide and In-Zn oxide can also be used as metal oxides. CAAC-OS is an oxide semiconductor including a plurality of crystalline regions, and the c-axis of the plurality of crystalline regions is oriented in a specific direction. In addition, the specific direction refers to the thickness direction of the CAAC-OS film, the normal direction of the formed surface of the CAAC-OS film, or the normal direction of the surface of the CAAC-OS film. In addition, the crystalline region is a region having a periodicity of atomic arrangement. Note that when the atomic arrangement is viewed as a lattice arrangement, the crystalline region is also a region where the lattice arrangement is consistent.

[0443] In addition, "CAC-OS" refers to a structure in which the material is separated into a first region and a second region to form a mosaic shape, and the first region is distributed in the film (hereinafter also referred to as a cloud shape). That is, CAC-OS refers to a composite metal oxide having a structure in which the first region and the second region are mixed. Note that it is sometimes difficult to observe a clear boundary between the first region and the second region.

[0444] For example, in the CAC-OS of In-Ga-Zn oxide, based on the EDX mapping image obtained by energy dispersive X-ray spectroscopy (EDX), it can be confirmed that the structure has a region with In as the main component (first region) and a region with Ga as the main component (second region) that are unevenly distributed and mixed.

[0445] When CAC-OS is used for transistors, the complementary effect of the conductivity of the first region and the insulation of the second region can give CAC-OS a switch function (a function of controlling on / off). In other words, a portion of the CAC-OS material has a conductive function and another portion has an insulating function, and the entire material has a semiconductor function. By separating the conductive function and the insulating function, each function can be maximized. Therefore, by using CAC-OS for transistors, a high on-state current (I on ), high field effect mobility (μ) and good switching performance.

[0446] Oxide semiconductors have various structures and various characteristics. The oxide semiconductor of one embodiment of the present invention may include two or more of an amorphous oxide semiconductor, a polycrystalline oxide semiconductor, a-like OS, CAC-OS, nc-OS, and CAAC-OS.

[0447] In addition, the control circuit unit 1320 preferably uses a transistor containing an oxide semiconductor because the transistor can be used in a high temperature environment. In order to simplify the process, the control circuit unit 1320 can also be formed using a unipolar transistor. The operating ambient temperature range of the transistor containing an oxide semiconductor in the semiconductor layer is larger than that of single crystal Si, that is, above -40°C and below 150°C, and the characteristic change when the secondary battery becomes overheated is smaller than that of single crystal Si. The off-state current of the transistor containing an oxide semiconductor is also below the lower limit of the measurement at 150°C, but the temperature dependence of the off-state current characteristics of the single crystal Si transistor is large. For example, at 150°C, the off-state current of the single crystal Si transistor increases, and the switching ratio of the current does not become sufficiently large. The control circuit unit 1320 can improve safety. In addition, by combining with a secondary battery in which the positive electrode active material 100 that can be obtained in embodiments 1, 2, etc. is used for the positive electrode, a synergistic effect of safety can be obtained. The secondary battery and the control circuit unit 1320 using the positive electrode active material 100 obtained in the first and second embodiments, etc., for the positive electrode greatly contribute to reducing accidents such as fires caused by the secondary battery.

[0448] The control circuit unit 1320 using a storage circuit including a transistor using an oxide semiconductor can also be used as an automatic control device for a secondary battery for the causes of instability caused by ten conditions such as micro short circuits. As functions for solving the causes of instability under the ten conditions, there can be cited prevention of overcharging, prevention of overcurrent, control of overheating during charging, cell balancing in a battery pack, prevention of overdischarge, a capacity meter, automatic control of charging voltage and current according to temperature, control of charging current according to the degree of degradation, detection of abnormal behavior of micro short circuits, prediction of abnormalities regarding micro short circuits, etc. The control circuit unit 1320 has at least one of the above functions. In addition, ultra-miniaturization of the automatic control device for the secondary battery can be achieved.

[0449] In addition, "micro short circuit" refers to a very small short circuit inside the secondary battery. It is not a state where the positive and negative electrodes of the secondary battery cannot be charged or discharged due to a short circuit, but a phenomenon in which a short circuit current flows slightly in a very small short circuit portion. Since a large voltage change occurs even in a short and very small portion, this abnormal voltage value will affect subsequent speculation.

[0450] One of the reasons for micro short circuits is believed to be that due to repeated charging and discharging, uneven distribution of positive electrode active materials occurs, local current concentration occurs in part of the positive electrode and part of the negative electrode, and part of the separator becomes inoperative, or side reactions produce side reactants, leading to micro short circuits.

[0451] In addition to micro short circuits, the control circuit unit 1320 detects the terminal voltage of the secondary battery and manages the charge and discharge state of the secondary battery. For example, to prevent overcharging, both the output transistor of the charging circuit and the blocking switch can be turned off at almost the same time.

[0452] then, Fig. 20B Show Fig. 20A An example of a block diagram of a battery pack 1415 is shown.

[0453] The control circuit unit 1320 includes: a switch unit 1324 including at least a switch for preventing overcharging and a switch for preventing overdischarging; a control circuit 1322 for controlling the switch unit 1324; and a voltage measuring unit of the first battery 1301a. In the control circuit unit 1320, the upper limit voltage and the lower limit voltage of the secondary battery used are set to control the upper limit of the current flowing from the outside or the upper limit of the output current flowing to the outside. The range above the lower limit voltage and below the upper limit voltage of the secondary battery is the recommended voltage range. When the voltage is outside this range, the switch unit 1324 functions and serves as a protection circuit. In addition, the control circuit unit 1320 controls the switch unit 1324 to prevent overdischarge and / or overcharge, so it can also be called a protection circuit. For example, when the control circuit 1322 detects a voltage that will become overcharge, the current is shielded by making the switch of the switch unit 1324 in a closed state. In addition, the function of shielding the current according to the increase in temperature can also be set by setting a PTC element in the charge and discharge path. In addition, the control circuit unit 1320 includes an external terminal 1325 (+IN) and an external terminal 1326 (−IN).

[0454] The switch section 1324 can be formed by combining n-channel transistors or p-channel transistors. In addition to switches including Si transistors using single crystal silicon, power transistors such as Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenide), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaOx (gallium oxide; x is a real number greater than 0) can also be used to form the switch section 1324. In addition, the storage element using the OS transistor can be freely configured by stacking it on a circuit using the Si transistor, so it is easy to achieve integration. In addition, the OS transistor can be manufactured using the same manufacturing device as the Si transistor, so it can be manufactured at a low cost. That is, by stacking the control circuit section 1320 using the OS transistor on the switch section 1324 for integration, the switch section 1324 and the control circuit section 1320 can be integrated into one chip. The volume occupied by the control circuit section 1320 can be reduced, so miniaturization can be achieved.

[0455] The first battery 1301a and 1301b mainly supply power to the 42V series (high voltage series) vehicle-mounted equipment, while the second battery 1311 supplies power to the 14V series (low voltage series) vehicle-mounted equipment. In many cases, the second battery 1311 adopts a lead-acid battery because of cost advantages. However, the lead-acid battery has the disadvantages of large self-discharge compared with the lithium-ion secondary battery and easy deterioration due to a phenomenon called sulfation. Although there is an advantage of no need for maintenance when using a lithium-ion secondary battery as the second battery 1311, an abnormality that is difficult to distinguish during manufacturing may occur when it is used for a long time, such as more than three years. In particular, in order to prevent the situation that the second battery 1311 of the starter inverter cannot work, even if the first battery 1301a and 1301b have residual capacity, the second battery 1311 is charged by supplying power from the first battery to the second battery in a manner that always maintains a fully charged state.

[0456] In this embodiment, excellent discharge characteristics can be exhibited even in a low-temperature environment by using the lithium ion secondary battery of one embodiment of the present invention for both the first battery 1301a and the second battery 1311. The second battery 1311 may also be a lead acid battery, an all-solid battery, or an electric double layer capacitor.

[0457] In addition, the regenerative energy caused by the rotation of the tire 1316 is transmitted to the engine 1304 through the transmission 1305, and is charged to the second battery 1311 from the engine controller 1303 and the battery controller 1302 through the control circuit unit 1321. In addition, the first battery 1301a is charged from the battery controller 1302 through the control circuit unit 1320. In addition, the first battery 1301b is charged from the battery controller 1302 through the control circuit unit 1320. In order to efficiently charge the regenerative energy, it is preferable that the first batteries 1301a and 1301b can be charged at a high speed.

[0458] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b, etc. The battery controller 1302 sets the charging conditions according to the charging characteristics of the secondary battery to be used and performs high-speed charging.

[0459] In addition, although not shown in the figure, when connected to an external charger, the charger socket or the charger connection cable is electrically connected to the battery controller 1302. The power supplied from the external charger is charged to the first battery 1301a, 1301b through the battery controller 1302. In addition, some chargers are provided with a control circuit without using the function of the battery controller 1302, but in order to prevent overcharging, it is preferred to charge the first battery 1301a, 1301b through the control circuit unit 1320. In addition, sometimes the connection cable or the charger connection cable is provided with a control circuit. The control circuit unit 1320 is sometimes referred to as an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) provided in the electric vehicle. CAN is one of the serial communication standards used as an in-vehicle LAN. In addition, the ECU includes a microcomputer. In addition, the ECU uses a CPU or a GPU.

[0460] As an external charger installed in a charging station, there are 100V outlet-200V outlet or three-phase 200V and 50kW outlet, etc. In addition, it is also possible to charge by supplying power from an external charging device through a contactless power supply method.

[0461] In order to charge the battery in a short time during high-speed charging, a secondary battery that can withstand charging at a high voltage is desired.

[0462] In addition, when graphene is used as a conductive material and the capacity can be suppressed from decreasing and maintained at a high capacity even if the thickness of the electrode layer is increased and the load is increased, a synergistic effect can be achieved to realize a secondary battery with greatly improved electrical characteristics. In particular, it is very effective for secondary batteries used in vehicles, and a longer driving distance can be achieved without increasing the weight ratio of the secondary battery relative to the total weight of the vehicle, specifically, a vehicle that can travel a distance of more than 500 km per charge.

[0463] Next, an example in which a secondary battery as one embodiment of the present invention is mounted on a vehicle, typically a transportation vehicle, will be described.

[0464] In addition, when Fig.15D , Fig. 17C , Fig. 20A When any of the secondary batteries shown in is installed in a vehicle, a new generation of clean energy vehicles such as hybrid electric vehicles (HV), electric vehicles (EV) or plug-in hybrid electric vehicles (PHV) can be realized. In addition, the secondary battery can also be installed in agricultural machinery, electric bicycles including electric-assisted bicycles, motorcycles, electric wheelchairs, electric karts, ships, submarines, airplanes, rockets, artificial satellites, space probes, planetary probes or spacecraft. The secondary battery of one embodiment of the present invention can be a high-capacity secondary battery. Therefore, the secondary battery of one embodiment of the present invention is suitable for miniaturization and lightweight, and can be suitable for use in transportation vehicles.

[0465] FIG. 21A to FIG. 21D A transport vehicle using one embodiment of the present invention is shown. Fig.21A The car 2001 shown is an electric car using an electric motor as a power source for running. Alternatively, the car 2001 is a hybrid car that can use an electric motor and an engine as a power source for running. When the secondary battery is installed in the vehicle, the example of the secondary battery shown in the embodiment 4 can be set in one or more parts. Fig.21A The automobile 2001 shown includes a battery pack 2200, and the battery pack includes a secondary battery module that connects a plurality of secondary batteries. By using a lithium-ion secondary battery of one embodiment of the present invention for the secondary battery, excellent discharge characteristics can be exhibited even in a low temperature environment. In addition, it is preferred to further include a charging control device electrically connected to the secondary battery module.

[0466] In addition, in the automobile 2001, the secondary battery of the automobile 2001 can be charged by supplying power from an external charging device using a plug-in method or a contactless power supply method. When charging, the charging method or the specifications of the connector can be appropriately performed according to the methods specified by CHAdeMO (a registered trademark in Japan) or the combined charging system "Combined Charging System". As a charging device, a charging station set up in a commercial facility or a home power supply can also be used. For example, by supplying power from the outside using plug-in technology, the power storage device installed in the automobile 2001 can be charged. Charging can be performed by converting AC power into DC power using a conversion device such as an AC / DC converter.

[0467] In addition, although not shown in the figure, the power receiving device can also be installed in the vehicle and the power can be supplied non-contactly from the power transmission device on the ground for charging. When the non-contact power supply method is used, by assembling the power transmission device in the road or the outer wall, charging can be performed not only when the vehicle is parked but also when it is driving. In addition, the non-contact power supply method can also be used to send and receive power between two vehicles. Furthermore, a solar cell can be set on the outside of the vehicle to charge the secondary battery when it is parked or driving. Such non-contact power supply can be achieved using electromagnetic induction or magnetic field resonance.

[0468] exist Fig. 21B In the diagram, a large transport vehicle 2002 including an electrically controlled engine is shown as an example of a transport vehicle. The secondary battery module of the transport vehicle 2002 is, for example, a secondary battery module having a maximum voltage of 170V, in which four secondary batteries with a nominal voltage of 3.0V or more and 5.0V or less are connected in series and 48 cells are connected. The battery pack 2201 has the same characteristics as the battery pack 2201 except for the number of secondary batteries constituting the secondary battery module. Fig.21A The same functions are omitted for brevity. By using a lithium ion secondary battery of one embodiment of the present invention for Fig. 21B The secondary battery can exhibit excellent discharge characteristics even in low temperature environments.

[0469] exist Fig. 21C In the figure, a large transport vehicle 2003 including an electrically controlled engine is shown as an example. The secondary battery module of the transport vehicle 2203 is, for example, a secondary battery module having a maximum voltage of 600V in which more than 100 secondary batteries having a nominal voltage of 3.0V or more and 5.0V or less are connected in series. Therefore, a secondary battery having less uneven characteristics is required. By using a secondary battery in which the positive electrode active material 100 described in embodiments 1 and 2, etc. is used for the positive electrode, a secondary battery having stable battery characteristics can be manufactured, and mass production can be performed at low cost from the perspective of yield. In addition, in addition to the difference in the number of secondary batteries constituting the secondary battery module, the battery pack 2202 has the same Fig.21A The same functions are omitted for brevity. By using a lithium ion secondary battery of one embodiment of the present invention for Fig. 21C The secondary battery can exhibit excellent discharge characteristics even in low temperature environments.

[0470] exist Fig.21D , an aircraft 2004 equipped with an engine burning fuel is shown as an example. Fig.21D The aircraft 2004 shown includes wheels for taking off and landing, so it can be said that the aircraft 2004 is a type of transport vehicle. In the aircraft 2004, a plurality of secondary batteries are connected to form a secondary battery module and a battery pack 2203 including the secondary battery module and a charging control device is included. By using a lithium ion secondary battery of one embodiment of the present invention for Fig.21D The secondary battery can exhibit excellent discharge characteristics even in low temperature environments.

[0471] The secondary battery module of the aircraft 2004 has, for example, eight 4V secondary batteries connected in series and a maximum voltage of 32V. In addition to the number of secondary batteries constituting the secondary battery module of the battery pack 2203, the Fig.21A The functions are the same, so the description is omitted.

[0472] Fig.21E As an example, an artificial satellite 2005 using a secondary battery 2204 is shown. Since the artificial satellite 2005 is used in the extremely low temperature space, it is preferable to include a secondary battery 2204 of one embodiment of the present invention having good low temperature resistance. In addition, the secondary battery 2204 is preferably installed inside the artificial satellite 2005 in a state covered with a heat-insulating member. By using a lithium-ion secondary battery of one embodiment of the present invention Fig.21E The secondary battery can exhibit excellent discharge characteristics even in low temperature environments.

[0473] (Implementation 7) In this embodiment, using Fig.22A and Fig. 22B An example in which the secondary battery of one embodiment of the present invention is installed in a building will be described.

[0474] Fig.22A The house shown includes a power storage device 2612 having a secondary battery module of one embodiment of the present invention and a solar panel 2610. The power storage device 2612 is electrically connected to the solar panel 2610 via wiring 2611 or the like. In addition, the power storage device 2612 can be electrically connected to a ground-mounted charging device 2604. The power obtained by the solar panel 2610 can be charged into the power storage device 2612. In addition, the power stored in the power storage device 2612 can be charged into a secondary battery included in the vehicle 2603 via the charging device 2604. The power storage device 2612 is preferably disposed in an underfloor space portion. By being disposed in the underfloor space portion, the space on the floor can be effectively utilized. Alternatively, the power storage device 2612 can also be disposed on the floor. By using a lithium-ion secondary battery of one embodiment of the present invention for Fig.22A The power storage device can exhibit excellent discharge characteristics even in low temperature environments.

[0475] The power stored in the power storage device 2612 can also be supplied to other electronic devices in the house. Therefore, even when power cannot be supplied from a commercial power source due to a power outage or the like, the electronic devices can be used by using the power storage device 2612 of one embodiment of the present invention as an uninterruptible power supply.

[0476] Fig. 22B An example of a power storage device according to one embodiment of the present invention is shown. Fig. 22B As shown, a power storage device 791 according to one embodiment of the present invention is installed in an underfloor space of a building 799. In addition, a control circuit may be installed in the power storage device 791, thereby improving safety.

[0477] The power storage device 791 is provided with a control device 790 , and the control device 790 is electrically connected to the switchboard 703 , the power storage controller 705 (also referred to as a control device), the display 706 , and the router 709 through wiring.

[0478] Electric power is supplied from the commercial power supply 701 to the switchboard 703 through the lead-in installation portion 710. In addition, both the electric power from the power storage device 791 and the electric power from the commercial power supply 701 are supplied to the switchboard 703, and the switchboard 703 supplies the supplied electric power to the general load 707 and the storage load 708 through the socket (not shown).

[0479] Examples of the general load 707 include electronic devices such as a television and a personal computer, and examples of the power storage load 708 include electronic devices such as a microwave oven, a refrigerator, and an air conditioner.

[0480] The power storage controller 705 has a measuring unit 711, a predicting unit 712, and a planning unit 713. The measuring unit 711 has a function of measuring the power consumption of the general load 707 and the power storage load 708 in a day (e.g., from 0:00 to 24:00). In addition, the measuring unit 711 may also have a function of measuring the power of the power storage device 791 and the power supplied from the commercial power supply 701. In addition, the predicting unit 712 has a function of predicting the required power consumed by the general load 707 and the power storage load 708 in the next day based on the power consumption of the general load 707 and the power storage load 708 in a day. In addition, the planning unit 713 has a function of determining the charging and discharging plan of the power storage device 791 based on the required power predicted by the predicting unit 712.

[0481] The amount of power consumed by the general load 707 and the power storage load 708 measured by the measuring unit 711 can be confirmed using the display 706. Alternatively, it can be confirmed using an electronic device such as a television or a personal computer through the router 709. Furthermore, it can be confirmed using a portable electronic terminal such as a smart phone or a tablet terminal through the router 709. In addition, the required power for each time period (or each hour) predicted by the prediction unit 712 can be confirmed using the display 706, an electronic device, or a portable electronic terminal.

[0482] (Implementation 8) In the present embodiment, as an example of a vehicle equipped with a secondary battery, an example in which a lithium ion secondary battery according to one embodiment of the present invention is installed in a motorcycle or a bicycle is described.

[0483] Fig.23A An example of an electric bicycle using a power storage device according to one embodiment of the present invention is shown. Fig.23A The electric bicycle 8700 shown has excellent discharge characteristics even in a low temperature environment. For example, a power storage device according to one embodiment of the present invention includes a plurality of storage batteries and a protection circuit.

[0484] The electric bicycle 8700 includes a power storage device 8702. The power storage device 8702 supplies power to a motor that assists the rider. In addition, the power storage device 8702 is portable. Fig. 23B The power storage device 8702 taken out of the bicycle is shown. In addition, by using a lithium ion secondary battery of one embodiment of the present invention for the power storage device 8702, excellent discharge characteristics are obtained even in a low temperature environment. Furthermore, the remaining power of the power storage device 8702 can be displayed by the display unit 8703. In addition, the power storage device 8702 includes a control circuit 8704 that can perform charging control or abnormality detection of the secondary battery. The control circuit 8704 is electrically connected to the positive and negative electrodes of the storage battery 8701.

[0485] Fig.23C This is an example of a two-wheeled vehicle using the power storage device according to one embodiment of the present invention. Fig.23C The illustrated scooter 8600 includes a power storage device 8602, a side mirror 8601, and a turn signal lamp 8603. The power storage device 8602 can supply power to the turn signal lamp 8603. By using the lithium ion secondary battery of one embodiment of the present invention for the power storage device 8602, excellent discharge characteristics are obtained even in a low temperature environment.

[0486] In addition, Fig.23C In the scooter 8600 shown, the power storage device 8602 can be accommodated in the under-seat storage section 8604. Even if the under-seat storage section 8604 is small, the power storage device 8602 can be accommodated in the under-seat storage section 8604. By using the lithium ion secondary battery of one embodiment of the present invention for the power storage device 8602, excellent discharge characteristics can be obtained even in a low temperature environment.

[0487] (Implementation method 9) In this embodiment, an example of installing a secondary battery of one embodiment of the present invention in an electronic device is described. As an electronic device equipped with a secondary battery, for example, a television device (also referred to as a television or a television receiver), a display for a computer, a digital camera, a digital video camera, a digital photo frame, a mobile phone (also referred to as a mobile phone, a mobile phone device), a portable game console, a portable information terminal, a sound reproduction device, a large game console such as a pinball machine, etc. can be cited. As a portable information terminal, a notebook personal computer, a tablet terminal, an e-book terminal, a mobile phone, etc. can be cited.

[0488] Fig.24A An example of a mobile phone is shown. The mobile phone 2100 includes an operation button 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like in addition to a display portion 2102 mounted on a housing 2101. In addition, the mobile phone 2100 includes a secondary battery 2107. By using a lithium ion secondary battery of one embodiment of the present invention for the secondary battery 2107, excellent discharge characteristics are achieved even in a low temperature environment.

[0489] The mobile phone 2100 can execute various application programs such as mobile phone, e-mail, article reading and writing, music playing, network communication, computer games, etc.

[0490] In addition to time setting, the operation button 2103 may have various functions such as power switch, wireless communication switch, silent mode setting and cancellation, power saving mode setting and cancellation, etc. For example, by using the operating system incorporated in the mobile phone 2100, the function of the operation button 2103 can be freely set.

[0491] In addition, the mobile phone 2100 can perform short-range wireless communication standardized by the communication system. For example, by communicating with a headset capable of wireless communication, a hands-free call can be made.

[0492] In addition, the mobile phone 2100 has an external connection port 2104, and data can be directly sent to or received from other information terminals through a connector. In addition, charging can also be performed through the external connection port 2104. In addition, the charging operation can also be performed using wireless power supply without using the external connection port 2104.

[0493] The mobile phone 2100 preferably includes a sensor. For example, a fingerprint sensor, a pulse sensor, a body sensor such as a temperature sensor, a touch sensor, a pressure sensor, or an acceleration sensor may be preferably installed as the sensor.

[0494] Fig. 24B An unmanned aerial vehicle 2300 including a plurality of rotors 2302 is shown. The unmanned aerial vehicle 2300 is also referred to as a drone. The unmanned aerial vehicle 2300 includes a secondary battery 2301 of one embodiment of the present invention, a camera 2303, and an antenna (not shown). The unmanned aerial vehicle 2300 can be remotely operated via the antenna. By using a lithium-ion secondary battery of one embodiment of the present invention for a secondary battery installed in the unmanned aerial vehicle 2300, excellent discharge characteristics are obtained even in a low temperature environment.

[0495] Fig.24C An example of a robot is shown. Fig.24C The robot 6400 shown includes a secondary battery 6409, an illumination sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a moving mechanism 6408, a computing device, and the like.

[0496] The microphone 6402 has a function of detecting the user's voice and surrounding sounds, etc. In addition, the speaker 6404 has a function of emitting sound. The robot 6400 can communicate with the user through the microphone 6402 and the speaker 6404.

[0497] The display unit 6405 has the function of displaying various information. The robot 6400 can display the information required by the user on the display unit 6405. The display unit 6405 can also be equipped with a touch panel. In addition, the display unit 6405 can be a detachable information terminal, and by setting it at a fixed position of the robot 6400, it can be charged and send and receive data.

[0498] The upper camera 6403 and the lower camera 6406 have the function of photographing the surrounding environment of the robot 6400. In addition, the obstacle sensor 6407 can detect whether there is an obstacle in the direction of the robot 6400 when it moves forward using the moving mechanism 6408. The robot 6400 can confirm the surrounding environment using the upper camera 6403, the lower camera 6406, and the obstacle sensor 6407 and move safely.

[0499] A secondary battery 6409 according to one embodiment of the present invention and a semiconductor device or an electronic component are provided inside the robot 6400. The secondary battery 6409 installed in the robot 6400 has excellent discharge characteristics even in a low temperature environment by using a lithium ion secondary battery according to one embodiment of the present invention.

[0500] Fig.24D An example of a sweeping robot is shown. The sweeping robot 6300 includes a display unit 6302 disposed on the surface of a frame 6301, a plurality of cameras 6303 disposed on the side, a brush 6304, an operation button 6305, a secondary battery 6306, various sensors, etc. Although not shown in the figure, the sweeping robot 6300 also has wheels, a suction port, etc. The sweeping robot 6300 can walk by itself and can detect garbage 6310 and suck the garbage into the suction port set below.

[0501] The sweeping robot 6300 can determine whether there are obstacles such as walls, furniture or steps by analyzing the image taken by the camera 6303. In addition, when an object such as a wire that may be entangled with the brush 6304 is found through image analysis, the rotation of the brush 6304 can be stopped. By using a lithium ion secondary battery of one embodiment of the present invention for the secondary battery 6306 included in the sweeping robot 6300, it also has excellent discharge characteristics in a low temperature environment. Furthermore, the sweeping robot 6300 includes a semiconductor device or an electronic component.

[0502] Fig.25A An example of a wearable device is shown. A secondary battery is used as a power source of the wearable device. In addition, in order to improve the splash-proof, waterproof or dust-proof performance when the user uses the wearable device in daily life or outdoors, the user not only wants the wearable device to be able to be charged by wire with the connector part exposed for connection, but also wants to be able to be charged wirelessly.

[0503] For example, the secondary battery of one embodiment of the present invention can be installed in Fig.25A The eyeglass-type device 4000 shown has excellent discharge characteristics even in a low temperature environment. The eyeglass-type device 4000 includes a frame 4000a and a display unit 4000b. By installing a secondary battery on the temple portion of the curved frame 4000a, a light-weight, well-balanced eyeglass-type device 4000 with a long continuous use time can be realized. The secondary battery using the positive electrode active material 100 obtained in Embodiments 1 and 2, etc. as the positive electrode has a high energy density, and a space-saving structure that can cope with the miniaturization of the frame can be realized.

[0504] In addition, the secondary battery of one embodiment of the present invention can be mounted on an earphone type device 4001. The earphone type device 4001 includes at least a microphone portion 4001a, a flexible tube 4001b, and an earphone portion 4001c. In addition, a secondary battery can be provided in the flexible tube 4001b or in the earphone portion 4001c. The secondary battery using the positive electrode active material 100 obtained in Embodiments 1 and 2 as a positive electrode has a high energy density and can realize a structure capable of coping with the space saving required for miniaturization of the frame.

[0505] In addition, the secondary battery of one embodiment of the present invention can be mounted on a device 4002 that can be directly mounted on the body. In addition, the secondary battery 4002b can be set in the thin frame 4002a of the device 4002. The secondary battery using the positive electrode active material 100 obtained in Embodiments 1 and 2, etc. for the positive electrode has a high energy density and can realize a space-saving structure that can cope with the miniaturization of the frame.

[0506] In addition, the secondary battery of one embodiment of the present invention can be installed in the device 4003 that can be mounted on clothes. In addition, the secondary battery 4003b can be set in the thin frame 4003a of the device 4003. The secondary battery using the positive electrode active material 100 obtained in the first and second embodiments, etc. for the positive electrode has a high energy density and can realize a space-saving structure that can cope with the miniaturization of the frame.

[0507] In addition, the secondary battery of one embodiment of the present invention can be mounted on a belt-type device 4006. The belt-type device 4006 includes a belt portion 4006a and a wireless power supply and receiving portion 4006b, and the secondary battery can be mounted in the inner area of ​​the belt portion 4006a. The secondary battery using the positive electrode active material 100 obtained in Embodiments 1 and 2 as the positive electrode has a high energy density and can realize a space-saving structure that can cope with the miniaturization of the frame.

[0508] In addition, the secondary battery of one embodiment of the present invention can be mounted on a watch-type device 4005. The watch-type device 4005 includes a display portion 4005a and a strap portion 4005b, and the secondary battery can be set on the display portion 4005a or the strap portion 4005b. The secondary battery using the positive electrode active material 100 obtained in the first and second embodiments, etc. for the positive electrode has a high energy density, and can realize a space-saving structure that can cope with the miniaturization of the frame.

[0509] The display unit 4005a can display various information such as e-mails and incoming phone calls in addition to the time.

[0510] In addition, since the watch-type device 4005 is a wearable device that is directly wrapped around the wrist, it can also be equipped with sensors for measuring the user's pulse, blood pressure, etc. Thus, the user's exercise volume and health-related data can be stored for health management.

[0511] Fig.25B is a perspective view showing the watch-type device 4005 taken off from the wrist.

[0512] in addition, Fig.25C A side view is shown. Fig.25C The internal region includes a secondary battery 913. When the lithium ion secondary battery of one embodiment of the present invention is used as the secondary battery 913, excellent discharge characteristics are obtained even in a low-temperature environment. [Example 1]

[0513] In this example, a test battery including a positive electrode active material and a negative electrode active material according to one embodiment of the present invention was manufactured, and a charge and discharge cycle test was performed.

[0514] <Manufacturing of Positive Electrode Active Material> Reference Fig. 9 The manufacturing process of the positive electrode active material used in this embodiment is described with reference to the manufacturing method shown in FIG. 10 .

[0515] As Fig. 9 For the LiCoO2 of step S14, prepare commercially available lithium cobaltate (CELLSEED C-5H manufactured by Nippon Chemical Industry Co., Ltd.) containing cobalt as a transition metal M and no added elements, and pre-screen it using an automatic sieving machine. When the particle size distribution of CELLSEED C-5H was measured using a laser diffraction particle size distribution measuring device SALD-2200, the median particle size (D50) was 7.0 μm. As the initial heating of step S15, the lithium cobaltate is placed in a sagger and covered with a lid, and heated at 850°C for 2 hours using an RHK simulator (manufactured by NORITAKE CO., LIMITED) as a calcining furnace. Air (compressed air, fully dried) is allowed to flow in the furnace at 10 L / min. The flow rate is adjusted in such a way that the differential pressure gauge of the furnace shows 5 Pa. Specifically, the opening width of the exhaust port is adjusted so that the furnace is in a positive pressure state. After the initial heating, when the furnace was cooled, cooling was performed at a rate of 200°C / time, and the above-mentioned air flow was continued until the temperature reached 200°C.

[0516] In this embodiment, according to Fig. 10A In step S20a shown in FIG. 1 , Mg and F are added as additive elements. Fig. 10A In step S21 shown, LiF is prepared as a F source and MgF2 is prepared as a Mg source. LiF:MgF2 is weighed in a molar ratio of 1:3 and mixed in dehydrated acetone at a rotation speed of 500 rpm for 20 hours. Screening is performed using a sieve with a mesh size of 300 μm to produce an additive element source (A1 source) with a uniform particle size.

[0517] Then, as Fig. 9 In step S31 shown, the magnesium of the A1 source is weighed so that the magnesium of the lithium cobalt oxide is 1 mol% of the cobalt of the lithium cobalt oxide, and the A1 source and the lithium cobalt oxide after the initial heating are stirred at a rotation speed of 3000 rpm for 10 minutes using a picobond (manufactured by Hosokawa Micron Co., Ltd.), thereby obtaining a mixture 903 (step S32). Nobilta is used as a rotor of the picobond. Before the next step S33, the mixture 903 is screened using an automatic sieve machine.

[0518] Next, as step S33, the mixture 903 is heated. The heating conditions are 850°C and 10 hours. During heating, the mixture 903 is placed in a sagger and covered with a lid. The sagger is placed in an RHK simulator (manufactured by Noritake Co., Ltd.) and heated at the above-mentioned heating temperature. Oxygen is made to flow (O2 flows) at 10L / min in the furnace. The flow rate is adjusted in such a way that the differential pressure gauge of the furnace displays 5Pa. Specifically, the opening width of the exhaust port is adjusted so that the furnace is in a positive pressure state. After the initial heating, when the furnace is cooled, it is cooled at a rate of 200°C / time, and the flow of oxygen is continued until the temperature reaches 200°C. In this way, a composite oxide containing Mg and F is obtained (step S34a).

[0519] Next, as step S40, a composite oxide and an additive element source (A2 source) are prepared. Fig. 10C In step S41 shown, nickel hydroxide that has been through a pulverization process is prepared as a nickel source and aluminum hydroxide that has been through a pulverization process is prepared as an aluminum source, and they are used as an additive element source (A2 source). As a pulverization process, nickel hydroxide and aluminum hydroxide are mixed in dehydrated acetone at a rotation speed of 500 rpm for 20 hours. Then, a sieve with a mesh size of 300 μm is used for screening.

[0520] As the A2 source, nickel hydroxide is weighed so that nickel is 0.5 mol% of cobalt and aluminum hydroxide is 0.5 mol% of cobalt, and the above elements and the composite oxide containing Mg and F are stirred at a rotation speed of 3000 rpm for 10 minutes using picobond (manufactured by Hosokawa Micron Co., Ltd.), thereby obtaining a mixture 904 (step S52). Nobilta is used as a rotor for the picobond. Before the next step S53, the mixture 904 is screened using an automatic sieve machine.

[0521] Next, as step S53, the mixture 904 is heated. The heating conditions are 850°C and 2 hours. During heating, the mixture 904 is placed in a sagger and covered with a lid. The sagger is placed in an RHK simulator (manufactured by Noritake Co., Ltd.) and heated at the above-mentioned heating temperature. Oxygen is made to flow (O2 flows) at 10L / min in the furnace. The flow rate is adjusted in such a way that the differential pressure gauge of the furnace displays 5Pa. Specifically, the opening width of the exhaust port is adjusted so that the furnace is in a positive pressure state. After heating, when cooling the furnace, cool it at a rate of 200°C / time, and continue to flow oxygen until the temperature reaches 200°C.

[0522] In this way, lithium cobalt oxide containing Mg, F, Ni and Al is obtained (step S54). The lithium cobalt oxide obtained by the above steps is used as a positive electrode active material of the sample. The median particle size (D50) of the positive electrode active material is not less than 1 μm and not more than 12 μm.

[0523] <Manufacturing of positive electrode> Prepare the above-mentioned lithium cobalt oxide as the positive electrode active material, prepare acetylene black (AB) as the conductive material, and prepare polyvinylidene fluoride (PVDF) as the binder. Prepare PVDF that is dissolved in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Then, mix the positive electrode active material: AB: PVDF = 95:3:2 (weight ratio) to prepare a slurry, and apply the slurry to the positive electrode collector of aluminum. Use NMP as the solvent of the slurry. After applying the slurry to the positive electrode collector, evaporate the solvent.

[0524] Then, in order to increase the density of the positive electrode active material layer on the positive electrode current collector, a pressing process was performed using a roller press. As the pressing process conditions, the linear pressure was 210 kN / m. The upper and lower rollers of the roller press were both at 120°C.

[0525] The positive electrode of each sample was obtained through the above process. The loading amount of positive electrode active material was 10 mg / cm 2 Above and 11mg / cm 2 Adjust within the following range.

[0526] <Manufacturing of negative electrode> Reference Fig.13 The manufacturing method shown illustrates the negative electrode used in this example.

[0527] according to Fig.13 As the graphite particles of this example, graphite (Formula BT1520T, manufactured by Superior Graphite) having an average particle size of 20 μm was prepared. The above graphite was obtained by spheroidizing natural graphite and then coating it with low-crystalline carbon.

[0528] according to Fig.13 As the silicon particles of this embodiment, the specific surface area of ​​12.7715 m 2 / g and an average particle size of 100 nm silicon particles (manufactured by Aldrich, product number 633097). 100 nm silicon particles are referred to as nano silicon particles.

[0529] <Sample 1, Sample 2> according to Fig.13 As the adhesive of this embodiment, polyglutamic acid (manufactured by Nippon Poly-Glu Co., Ltd., denoted as PGA) or polyacrylic acid (manufactured by FUJIFILM Wako Chemical Corporation, denoted as 20CLPAH, PAA) is used. In this embodiment, in order to change the conditions of the adhesive, the whole unit using PGA is referred to as sample 1, and the whole unit using PAA (crosslinking degree 20CL) is referred to as sample 2.

[0530] according to Fig.13 , prepare AB as the conductive material of this embodiment.

[0531] according to Fig.13 In step S60, as sample 1, graphite particles: silicon particles: AB: PGA = 72: 8: 6: 14 (weight ratio) are mixed to produce a mixture 204. In addition, as sample 2, graphite particles: silicon particles: AB: PGA = 72: 8: 6: 14 (weight ratio) are mixed to produce a mixture 204. In step S60, it is preferred to mix in a powder state. The loading amount of the negative electrode active material is 3.8 mg / cm 2 Above and 4.2mg / cm 2 Adjust within the following range.

[0532] according to Fig.13 , prepare deionized water as the solvent.

[0533] according to Fig.13 In step S61, deionized water is added to the mixture 204 corresponding to sample 1 and mixed, thereby obtaining slurry 206. In addition, deionized water is added to the mixture 204 corresponding to sample 2 and mixed, thereby obtaining slurry 206.

[0534] <Comparative Example> In the negative electrode of the comparative example of this embodiment, graphite particles are used as the negative electrode active material, carbon fiber (manufactured by Showa Denko K.K., VGCF (registered trademark)) is used as the conductive material, and CMC and SBR are used as the binder. The mixing ratio is graphite particles: VGCF: CMC: SBR = 97: 1: 1: 1 (weight ratio). The following table shows the conditions of the negative electrodes of sample 1, sample 2, and the comparative example.

[0535] [Table 2]

[0536] according to Fig.13 , prepare copper foil as a negative electrode current collector, and according to step S62, apply the above slurry on the copper foil.

[0537] according to Fig.13 The negative electrode 208 is obtained by drying according to step S63 and pressing according to step S64. In the drying, the first drying (pre-drying) and the second drying (main drying) are performed. As the pre-drying, the mixture is clamped on a heating plate heated to 50°C for 30 minutes. Then, as the main drying, it is dried for 45 minutes using a ventilated dryer at 80°C. A roller press is used in the pressing, and the comparative example is pressed with a linear pressure of 0.5 MPa using a roller heated to 120°C. Note that Sample 1 and Sample 2 are not pressed.

[0538] <SEM observation of samples 1 and 2> After drying according to step S63, SEM observation of sample 1 was performed. SEM was performed using S4800 manufactured by Hitachi High-Technologies Corporation. The acceleration voltage was 5 kV, and an image with a magnification of 2000 was obtained. Fig.26A The SEM image of the top surface of sample 1 is shown. Fig.26B A schematic diagram showing the SEM image. Fig.26B Graphite particles 200 are shown surrounded by solid lines. Fig.33 A SEM image of the top surface of Sample 2 is shown.

[0539] like Fig.26A and Fig.26B As shown, when viewed from the top, a portion of the graphite particle 200 is exposed from the binder 202 containing polyglutamic acid. That is, in the graphite particle 200 including the region not covered by the binder 202a containing polyglutamic acid, it can be considered that there is a region where lithium can be inserted and removed. In addition, the binder 202a containing polyglutamic acid is located between the graphite particles 200, and the polyglutamic acid can make the graphite particles bond to each other.

[0540] In the region where the binder 202a containing polyglutamic acid is located, silicon particles 201 are confirmed, and the aggregation of silicon particles 201 is also confirmed. In addition, AB203a as a conductive material is confirmed in the region where the binder 202a containing polyglutamic acid is located, and the aggregation of AB203a is also confirmed.

[0541] Silicon particles may slide due to expansion and contraction during charge and discharge, but in Sample 1, since the silicon particles 201 are wrapped by the binder 202a containing polyglutamic acid, sliding can be suppressed even if the charge and discharge cycles are repeated. Furthermore, since AB203a is wrapped by the binder 202a containing polyglutamic acid in a manner such that it is located near the silicon particles 201, it is easy to ensure a conductive path.

[0542] Thus, the negative electrode preferably has a region where graphite particles 200 are not covered by the binder, and a region where silicon particles 201 are gathered and covered by the binder. In addition, in the negative electrode, the conductive material is preferably located near the silicon particles 201, and the conductive material is preferably covered by the binder. Note that when the conductive material is in the form of carbon fibers, it may not be covered by the binder.

[0543] <Electrolyte> Next, an electrolyte was prepared. As the electrolyte, 1 mol / L of lithium hexafluorophosphate (LiPF6) was dissolved in a mixed solvent containing FEC (fluoroethylene carbonate) and MTFP (methyl 3,3,3-trifluoropropionate) at a ratio of FEC:MTFP=20:80 (volume ratio). No additives were used.

[0544] <Isolated Body> Next, a separator was prepared and a porous polypropylene film (PP) was used as the separator.

[0545] <Assembly of test battery> The positive electrode manufactured as described above, the negative electrode manufactured as described above, and the separator are placed in a battery can, and the electrolyte manufactured as described above is added dropwise to manufacture a test battery. The test battery of this embodiment is sometimes referred to as a full battery. In the assembled test battery, as described above, the conditions of the binder of the negative electrode, etc. are different, so the test battery including sample 1 is referred to as full battery 1, the test battery including sample 2 is referred to as full battery 2, and the test battery including the comparative example is referred to as a comparative battery.

[0546] <Charge and discharge cycle test 1> Next, the full battery 1, full battery 2, and comparison battery are subjected to charge and discharge cycle tests. First, initial charge and discharge are performed at 25°C, then a charge and discharge cycle test is performed at -40°C, and then the temperature is returned to 25°C to continue the charge and discharge cycle test. Although the temperatures are 25°C and -40°C, these temperatures are the temperatures of the constant temperature layer in which each test battery is configured. The charge and discharge cycle test refers to a test of charging and discharging at a specified temperature, and repeated charging and discharging are sometimes referred to as cycles. Note that the initial charge and discharge is sometimes referred to as aging or adjustment, which is equivalent to the first cycle of the test battery. The following table shows the measurement conditions of the charge and discharge cycle test in this embodiment, and the rate conditions at each temperature are different.

[0547] [Table 3] Temperature [℃] C-ratio Cycle times 25 0.1 1 time 25 0.2 3 times (2nd to 4th time) -40 0.05 10 times (5th to 14th) 25 0.2 3 times (15th to 17th)

[0548] Here, the rate of the charge and discharge cycle test conditions is explained. The rate during discharge is called the discharge rate, which refers to the ratio of the current during discharge to the battery capacity, and is represented by the unit C. In a battery with a rated capacity of X (Ah), the current equivalent to 1C is X (A). In the case of discharging with a current of 2X (A), it can be said to be discharged at 2C, and in the case of discharging with a current of X / 2 (A), it can be said to be discharged at 0.5C. In addition, the rate during charging is called the charging rate. Similar to the charging rate, in the case of charging with a current of 2X (A), it can be said to be charged at 2C, and in the case of charging with a current of X / 2 (A), it can be said to be charged at 0.5C. Sometimes the charging rate and the discharge rate are collectively recorded as the C rate. In addition, under the charge and discharge cycle test conditions of this embodiment, 1C = 200mA / g (unit weight of the positive electrode active material).

[0549] The conditions other than the C rate of the above-mentioned charge and discharge cycle test are as follows: When charging, the test battery is charged with constant current (CC charge) until the upper limit voltage reaches 4.5V, and then constant voltage charge (CV charge) is performed until the C rate reaches 1 / 10 (note, 1 / 5 at -40°C). When discharging, constant current discharge (CC discharge) is performed until the lower limit voltage reaches 2.5V. In addition, a rest period of more than 5 minutes and less than 15 minutes may be set between charging and discharging.

[0550] Fig.27A and Fig.27B The discharge capacity of the result of the charge and discharge cycle test is shown. Fig.27A The discharge capacity per unit weight of lithium cobalt oxide, which is the positive electrode active material, is shown. Fig.27B The discharge capacity per unit weight of graphite particles and silicon particles is shown as the mass of the negative electrode active material. Fig.27B Comparative Examples are not shown.

[0551] The following table shows Fig.27A The discharge capacity of each test battery at -40°C or below is shown in X( Fig.27A The discharge capacity of the 14th cycle in the test), the discharge capacity Y at 25°C ( Fig.27A The discharge capacity of the 15th cycle in the full battery 1 and the discharge capacity of the full battery 2 are both 50% or more, preferably 60% or more, and they exhibit excellent discharge characteristics in a low temperature environment compared to the comparative battery.

[0552] [Table 4]

[0553] The following table shows Fig.27B The discharge capacity of each test battery at -40°C or below is shown in X( Fig.27B The discharge capacity of the 14th cycle in the test), the discharge capacity Y at 25°C ( Fig.27B The discharge capacity of the 15th cycle in the full battery 1 and the discharge capacity of the full battery 2 are both 50% or more, preferably 60% or more, showing excellent discharge characteristics in a low temperature environment.

[0554] [Table 5]

[0555] from Fig.27A As shown in Table 4, compared with the comparative battery, the full battery 1 and the full battery 2 have excellent cycle characteristics at low temperatures and high discharge capacities. Fig.27B As shown in Table 5, full cell 1 and full cell 2 have excellent cycle characteristics at low temperatures and high discharge capacity. That is, it is known that at low temperatures such as -40°C, it is preferred to use a negative electrode active material mixed with graphite particles and silicon particles, and it is more preferred to use a binder containing PGA or PAA. In addition to the above, according to this embodiment, it is known that the low temperature characteristics of the binder containing PAA are better than those of the binder containing PGA.

[0556] When charging and discharging are performed at low temperatures, lithium cobalt oxide containing at least Mg is preferably used as the positive electrode active material. In addition, at low temperatures, a mixed solvent of a fluorinated cyclic carbonate and a fluorinated chain carbonate is preferably used as the electrolyte.

[0557] <Comparison of charge and discharge characteristics based on different degrees of crosslinking of separators and PAA> Next, a test battery having a different separator compared to the full battery in which the PAA (crosslinking degree 20CL) of the full battery 2 is replaced with PAA (crosslinking degree 10CL) is prepared, and a charge and discharge cycle test is performed. The structure using PP as a separator is recorded as the full battery 2_PP, the structure using glass fiber (GFC) as a separator is recorded as the full battery 2_G, the structure using a layer of polyimide as a separator is recorded as the full battery 2_PI1, the structure using two layers of polyimide as a separator is recorded as the full battery 2_PI2, and the structure using three layers of polyimide as a separator is recorded as the full battery 2_PI3. The following table shows the conditions of the above-mentioned full battery.

[0558] [Table 6]

[0559] <Charge and discharge cycle test 2> Charge-discharge cycle tests were conducted on full cell 2_PP, full cell 2_G, full cell 2_PI1, full cell 2_PI2, and full cell 2_PI3. The conditions including the rate conditions in the charge-discharge cycle tests were the same as those in the above charge-discharge cycle test 1.

[0560] Fig.32 The discharge capacity showing the results of the charge-discharge cycle test. Fig.32 The discharge capacity per unit weight of lithium cobaltate as the positive electrode active material is shown.

[0561] The following table shows Fig.32 The discharge capacity X at -40°C or lower ([ Fig.32 the discharge capacity of the 14th cycle in ) of each test battery shown, the discharge capacity Y at 25°C ([ Fig.32 the discharge capacity of the 15th cycle in ) and the value equivalent to discharge capacity X / discharge capacity Y × 100. It can be seen that except for full cell 2_G, the discharge capacity X / discharge capacity Y × 100 of any battery becomes 50% or more, preferably 60% or more, and shows excellent discharge characteristics in a low-temperature environment compared with the comparative battery. It can be seen that polyimide or polypropylene is preferably used for the separator in a low-temperature environment.

[0562] [Table 7] [Example 2]

[0563] In this example, XPS analysis, XRD analysis under a high-voltage charging state, and STEM-EDX analysis were performed on lithium cobaltate containing Mg, F, Ni, and Al.

[0564] [Manufacturing method of LCO1] In this example, according to the description of Embodiment 1 and Fig. 9 and FIG. 10 etc., it is explained that lithium cobaltate 1 with a median particle size (D50) of 12 μm or less can be obtained.

[0565] As Fig. 9 the starting material lithium cobaltate (LiCoO2) shown in step S10 of, commercially available lithium cobaltate (manufactured by Nippon Chemical Industry Co., Ltd., CELLSEED C-5H) not containing additive elements was prepared. In the following description of this specification etc., it is simply denoted as "C-5H". The median particle size (D50) of C-5H is about 7.0 μm, satisfying the condition that the median particle size (D50) is 10 μm or less.

[0566] Next, as heating in step S15, C-5H is placed in a sagger (container), covered with a lid, and then heated in a muffle furnace at 850°C for 2 hours. After the atmosphere in the muffle furnace becomes an oxygen atmosphere, no flow (O2 purge) is performed. In addition, when C-5H is placed in the sagger, the height (also called bulkiness) of the powder is placed in the sagger in a flat manner of less than 10 mm.

[0567] Next, according to Fig. 10A Step S20a shown in the figure is to prepare a source of the added element A1. First, lithium fluoride (LiF) is prepared as a F source, and magnesium fluoride (MgF2) is prepared as a Mg source. LiF and MgF2 are weighed in a ratio of LiF:MgF2 of 1:3 (molar ratio). Next, LiF and MgF2 are mixed in dehydrated acetone and stirred at a rotation speed of 500 rpm for 20 hours. A ball mill is used for mixing, and zirconia balls are used as a pulverizing medium. 20 mL of dehydrated acetone, zirconia balls, and 20 mL of slurry are added. 22 g of the additive element A1 source and about 9 g of the additive element A1 source in total were placed in a mixing ball mill having a container capacity of 45 mL and mixed, and then sieved using a sieve with a mesh size of 300 μm to obtain the additive element A1.

[0568] Next, according to Fig. 9 The step S31 shown is to mix the lithium cobalt oxide obtained by heating in step S15 (lithium cobalt oxide after initial heating) and the source of the additive element A1 obtained by step S20a. Specifically, the lithium cobalt oxide after initial heating and the source of the additive element A1 are weighed in a manner such that the number of atoms of magnesium relative to the number of atoms of cobalt in the lithium cobalt oxide is 1 atomic %, and then the lithium cobalt oxide and the source of the additive element A1 after initial heating are mixed by a dry method. At this time, stirring is performed at a rotation speed of 150 rpm for 1 hour. Then, sieving is performed using a sieve with a mesh size of 300 μm, thereby obtaining a mixture 903 (step S32).

[0569] Next, as step S33, the mixture 903 is heated. The heating conditions are 900° C. and 5 hours. During heating, the sagger containing the mixture 903 is covered with a lid. The atmosphere in the sagger is made to contain oxygen, and the ingress and egress of the oxygen are shielded (purged). A composite oxide containing Mg and F (lithium cobalt oxide containing Mg and F) is obtained by heating (step S34a).

[0570] Next, according to Fig. 10C Step S40 shown in the figure is to prepare the source of the additive element A2. First, nickel hydroxide (Ni(OH)2) is prepared as a Ni source, and aluminum hydroxide (Al(OH)3) is prepared as an Al source. Then, the nickel hydroxide and aluminum hydroxide are stirred in dehydrated acetone at a rotation speed of 500 rpm for 20 hours. A ball mill is used for mixing, and zirconium oxide balls are used as a grinding medium. 20 mL of dehydrated acetone, zirconium oxide balls, and 20 mL of acetone are mixed. 22 g and nickel hydroxide and aluminum hydroxide with a total of about 10 g are respectively placed into a mixing ball mill with a capacity of 45 mL in different containers for mixing. Then, screening is respectively carried out using a sieve with a screen hole size of 300 μm, thereby obtaining an additive element A2 source.

[0571] Next, as step S51, a composite oxide containing Mg and F and the additive element A2 source are mixed by dry mixing. Specifically, mixing is carried out by stirring at a rotational speed of 150 rpm for 1 hour. The mixing ratio is set such that the nickel hydroxide and aluminum hydroxide in the additive element A2 source are respectively 0.5 atomic% with respect to the cobalt in lithium cobaltate. A ball mill is used for mixing, and zirconia balls are used as the grinding medium. The zirconia balls 22 g, Ni source, Al source with a total of about 7.5 g, and the composite oxide (lithium cobaltate containing Mg and F) obtained through step S34 are placed into a mixing ball mill with a capacity of 45 mL for mixing. Finally, screening is carried out using a 300-μm sieve, thereby obtaining a mixture 904 (step S52).

[0572] Next, as step S53, the mixture 904 is heated. The heating conditions are 850 °C for 2 hours. During heating, the crucible containing the mixture 904 is covered with a lid and heated in a muffle furnace. After the atmosphere in the muffle furnace becomes an oxygen atmosphere, no flow (O2 purge) is carried out. Through heating, lithium cobaltate (composite oxide) containing Mg, F, Ni, and Al is obtained (step S54). Thereby, lithium cobaltate 1 (LCO1) is obtained.

[0573] <Manufacturing method of LCO2> Lithium cobaltate 2 (denoted as LCO2) is manufactured under conditions different from those of LCO1. As the manufacturing method of LCO2, in step S33, the heating conditions when heating the mixture 903 are set to 900 °C for 20 hours, and in step S53, the heating conditions when heating the mixture 904 are set to 850 °C for 10 hours. Except for the above heating temperatures, it is manufactured using the same method as LCO1. Thereby, LCO2 is obtained.

[0574] <XRD analysis in high-voltage charging state> An experiment is carried out to investigate the crystal structure of LCO1 in the high-voltage charging state.

[0575] First, assemble a half-cell with LCO1. Prepare LCO1 as a positive electrode active material, prepare acetylene black (AB) as a conductive material, and prepare polyvinylidene fluoride (PVDF) as a binder. Prepare PVDF that is previously dissolved in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Next, mix the positive electrode active material: AB: PVDF = 95:3:2 (weight ratio) to make a slurry, and apply the slurry to the positive electrode current collector of aluminum. Use NMP as a solvent for the slurry.

[0576] Next, after the slurry is applied onto the positive electrode current collector, the solvent is volatilized to form a positive electrode active material layer on the positive electrode current collector.

[0577] Then, in order to increase the density of the positive electrode active material layer on the positive electrode current collector, a pressing process was performed using a roller press. As the pressing process conditions, the linear pressure was 210 kN / m. The upper and lower rollers of the roller press were both at 120°C.

[0578] The following electrolyte is used as the electrolyte for the half-cell: ethylene carbonate (EC) and diethyl carbonate (DEC) are mixed at a ratio of EC:DEC = 3:7 (volume ratio) and 2 wt% of vinylene carbonate (VC) is added as an additive, and 1 mol / L of lithium hexafluorophosphate (LiPF6) is used as the electrolyte (lithium salt) of the electrolyte.

[0579] A polypropylene porous film was used as the separator, and lithium metal was used as the negative electrode (counter electrode).

[0580] <Half-cell charge and discharge test> The half-cell was charged and discharged. As charging, constant current charging was performed at 0.2C until the voltage reached 4.50V, and then constant voltage charging was performed until the current value reached 0.05C. In addition, as discharging, constant current discharge was performed at 0.2C until the voltage reached 3.0V. Note that, as in Example 1, 1C is 200mA / g (unit weight of the positive electrode active material).

[0581] Next, charging in a high voltage charging state was performed. As charging, constant current charging was performed at 0.2C until the voltage reached 4.60V, and then constant voltage charging was performed until the current value reached 0.02C.

[0582] Disassemble the half-cell within 1 hour after the above-mentioned charging is completed. When disassembling, in order to remove the positive electrode including LCO1 in a state of being charged at a high voltage, use an insulating tool to carefully disassemble it in a manner that does not cause a short circuit. In addition, when disassembling, use an argon-filled glove box with a managed dew point and oxygen concentration. The dew point of the glove box is preferably below -70°C, and the oxygen concentration is preferably below 5ppm. In addition, in the case where a long time has passed since the above-mentioned charging, the crystal structure of the positive electrode active material may change due to self-discharge, so it is preferred to disassemble the half-cell as soon as possible and analyze it. It is preferred to disassemble the half-cell within 15 minutes after entering the high-voltage charging state, and more preferably within 5 minutes.

[0583] The LCO 1 obtained by disassembling the half cell was placed on a sealable XRD measurement stage in the glove box, thereby obtaining LCO 1 sealed in the XRD measurement stage by argon.

[0584] Then, XRD measurement was started within 15 minutes. The XRD apparatus and conditions were as follows. XRD device: D8 ADVANCE manufactured by Bruker AXS X-ray source: CuKα1 ray Output: 40kV, 40mA Emission angle: Div. Slit, 0.5° Detector: LynxEye Scanning mode: 2θ / θ continuous scanning Measuring range (2θ): 15° to 75° Step width (2θ): set to 0.01° Counting time: 1 second / step Sample stage rotation: 15rpm

[0585] FIG. 28A to FIG. 28C The XRD measurement data of LCO1 in the high voltage charging state measured under the above conditions are shown. FIG. 28A to FIG. 28C Also shown are a reference distribution of an O3' structure (O3'), a reference distribution of an H1-3 structure (H1-3), and a reference distribution of CoO2 (CoO2).

[0586] Fig.28A The 2θ in XRD measurement is shown to be in the range of 15° or more and 75° or less. Fig.28B and Fig.28C In order to zoom in Fig.28A A portion of the measurement data of LCO1 is shown in a manner in which the magnification of the vertical axis is partially changed.

[0587] exist FIG. 28A to FIG. 28C In the XRD analysis results shown, sample 1 in the high voltage state of 4.6 V has a diffraction peak at 2θ = 19.30° within the range of 2θ = 19.25 ± 0.12° (above 19.13° and below 19.37°), and has a diffraction peak at 2θ = 45.52° within the range of 2θ = 45.47 ± 0.10° (above 45.37° and below 45.57°). In other words, it can be confirmed that it has an O3’ structure.

[0588] <XPS Analysis> Next, XPS analysis was performed on LCO1 and LCO2.

[0589] The measurement conditions of XPS are as follows. Measurement device: QuanteraII manufactured by PHI X-ray source: Monochromatic Al Kα (1486.6 eV) Detection area: Detection depth: About 4 nm to 5 nm (extraction angle is 45°) Measurement spectrum: Wide scan, narrow scan of each detected element

[0590] By analyzing the above XPS measurement results, the XPS analysis results shown in Table 8 were obtained. Table 8 shows the atomic numbers of each element when the total atomic numbers of Li, Co, Ni, Al, O, Mg, F, C, Ca, Na, S, Cl, and Ti in each sample are 100%. Note that the analyzed values are rounded off for presentation in the table. Although the total measurement recorded in Table 8 is sometimes 100.1% or 99.9%, the XPS analysis uses a calculation with a total atomic number of 100.0%.

[0591] [Table 8]

[0592] More Mg and Ni were detected in LCO1 and LCO2, and less Li and Co were detected. It can be considered that this result indicates that the surface layer portion 100a described in Embodiment 2 is formed in LCO1 and LCO2.

[0593] When comparing LCO1 and LCO2, more Ni, Mg, and F were detected in LCO1, and less Li and Co were detected.

[0594] The difference between the manufacturing conditions of LCO1 and LCO2 is that the heating time after mixing the A1 source and the heating time after mixing the A2 source of LCO2 are both longer. Here, from the F in Table 8, the number of F atoms in LCO1 is significantly larger than that in LCO2. In other words, the number of F atoms detected on the surface of LCO2 is significantly smaller than that detected on the surface of LCO1. This is considered to be due to the diffusion of Ni and Mg from the surface layer of the positive electrode active material to the inside.

[0595] Based on the XPS analysis results shown in Table 8, the number of Ni atoms relative to the number of Co atoms (Ni / Co), the number of Mg atoms relative to the number of Co atoms (Mg / Co), and the number of F atoms relative to the number of Co atoms (F / Co) were calculated, thereby obtaining the results shown in Table 9.

[0596] [Table 9]

[0597] In LCO1, the number of Ni atoms relative to the number of Co atoms (Ni / Co) is 0.099, the number of Mg atoms relative to the number of Co atoms (Mg / Co) is 1.092, and the number of F atoms relative to the number of Co atoms (F / Co) is 0.794. In addition, in LCO2, the number of Ni atoms relative to the number of Co atoms (Ni / Co) is 0.048, the number of Mg atoms relative to the number of Co atoms (Mg / Co) is 0.396, and the number of F atoms relative to the number of Co atoms (F / Co) is 0.021.

[0598] In other words, in the XPS analysis of LCO1, the number of Ni atoms relative to the number of Co atoms (Ni / Co) is 0.090 or more, the number of Mg atoms relative to the number of Co atoms (Mg / Co) is 1.000 or more, and the number of F atoms relative to the number of Co atoms (F / Co) is 0.700 or more. In addition, when excessive amounts of Ni, Mg, and F are contained, for example, when an amount exceeding twice the amount detected in the above-mentioned LCO1 is contained, the chargeable and dischargeable capacity of the positive electrode active material decreases.

[0599] From the above results, it can be said that in the XPS analysis of lithium cobaltate with a median particle size (D50) of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less), the atomic number of Ni relative to the atomic number of Co (Ni / Co) is preferably 0.05 or more, more preferably 0.06 or more, further preferably 0.07 or more, 0.08 or more, and even more preferably 0.09 or more. Additionally, it can be said that Ni / Co is preferably 0.200 or less, preferably 0.150 or less, preferably 0.140 or less, preferably 0.130 or less, preferably 0.120 or less, or preferably 0.110 or less.

[0600] In addition, it can be said that in the XPS analysis of lithium cobaltate with a median particle size (D50) of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less), the atomic number of Mg relative to the atomic number of Co (Mg / Co) is preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, more preferably 0.700 or more, more preferably 0.800 or more, more preferably 0.900 or more, and even more preferably 1.000 or more. Additionally, it can be said that Mg / Co is preferably 2.000 or less, preferably 1.500 or less, preferably 1.400 or less, preferably 1.300 or less, or preferably 1.200 or less.

[0601] In addition, it can be said that in the XPS analysis of lithium cobaltate with a median particle size (D50) of 12 μm or less (preferably 10.5 μm or less, more preferably 8 μm or less), the atomic number of F relative to the atomic number of Co (F / Co) is preferably 0.100 or more, more preferably 0.200 or more, more preferably 0.300 or more, more preferably 0.400 or more, more preferably 0.500 or more, more preferably 0.600 or more, and even more preferably 0.700 or more. Additionally, it can be said that F / Co is preferably 1.500 or less, preferably 1.200 or less, preferably 1.100 or less, preferably 1.000 or less, preferably 0.900 or less.

[0602] It is considered that when LCO1 has the above characteristics, high-voltage charging can be performed, and the charge-discharge characteristics are good not only at -40°C.

[0603] <STEM-EDX Analysis> Next, STEM-EDX line analysis was performed on LCO1.

[0604] As a pretreatment before analysis, LCO1 was thinned by the FIB method (micro-sampling method).

[0605] The following equipment and conditions were used for STEM and EDX.

[0606] <<S...

Claims

1. A lithium ion secondary battery, comprising: positive electrode; negative electrode; as well as Electrolyte, The positive electrode comprises lithium cobalt oxide having a median particle size (D50) of 1 μm or more and 12 μm or less, The lithium cobalt oxide contains magnesium in the surface layer. The negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group. Furthermore, the electrolyte solution includes a mixed solvent of a fluorinated cyclic carbonate and a fluorinated chain carbonate.

2. The lithium ion secondary battery according to claim 1, The average particle size of the silicon particles is less than 1 μm.

3. The lithium ion secondary battery according to claim 1, The average particle size of the graphite particles is greater than 5 μm.

4. The lithium ion secondary battery according to claim 1, The average particle size of the silicon particles is smaller than the average particle size of the graphite particles.

5. The lithium ion secondary battery according to claim 1, The weight ratio of the silicon particles is smaller than the weight ratio of the graphite particles.

6. The lithium ion secondary battery according to claim 1, The polymer having carboxyl groups is polyglutamic acid.

7. The lithium ion secondary battery according to claim 1, wherein the lithium cobalt oxide has a layered rock salt type crystal structure belonging to space group R-3m, The surface layer portion includes a base region and an end region having a surface parallel to the (001) plane of the crystal structure, Furthermore, when performing STEM-EDX line analysis, it was detected that the magnesium concentration in the end region of the lithium cobalt oxide was higher than the magnesium concentration in the base region.

8. A lithium ion secondary battery comprising: positive electrode; negative electrode; as well as Electrolyte, The positive electrode comprises lithium cobalt oxide having a median particle size (D50) of 1 μm or more and 12 μm or less, The lithium cobalt oxide contains magnesium and nickel in the surface layer. The negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group. The average particle size of the silicon particles is smaller than the average particle size of the graphite particles, Furthermore, the electrolyte solution includes a mixed solvent of a fluorinated cyclic carbonate and a fluorinated chain carbonate.

9. A lithium ion secondary battery comprising: positive electrode; negative electrode; as well as Electrolyte, The positive electrode comprises lithium cobalt oxide having a median particle size (D50) of 1 μm or more and 12 μm or less, The lithium cobalt oxide contains magnesium and nickel in the surface layer. The negative electrode comprises graphite particles, silicon particles and a polymer having a carboxyl group. The average particle size of the silicon particles is greater than the average particle size of the graphite particles, Furthermore, the electrolyte contains fluoroethylene carbonate and methyl 3,3,3-trifluoropropionate. When the total content of the fluoroethylene carbonate and the methyl 3,3,3-trifluoropropionate is 100 vol%, the volume ratio of the fluoroethylene carbonate and the methyl 3,3,3-trifluoropropionate is x:100-x (note, 5≤x≤30).

10. The lithium ion secondary battery according to claim 8 or 9, wherein the lithium cobalt oxide has a layered rock salt type crystal structure belonging to space group R-3m, The surface layer portion includes a base region and an end region having a surface parallel to the (001) plane of the crystal structure, Furthermore, when STEM-EDX line analysis is performed, the lithium cobalt oxide has a region in the end region where the distribution of the magnesium overlaps with the distribution of the nickel.

11. The lithium ion secondary battery according to claim 8 or 9, wherein the lithium cobalt oxide has a layered rock salt type crystal structure belonging to space group R-3m, The surface layer portion includes a base region and an end region having a surface parallel to the (001) plane of the crystal structure, Furthermore, when STEM-EDX line analysis is performed, the lithium cobalt oxide substantially does not contain the nickel in the base region.

Citation Information

Patent Citations

  • Nonaqueous solvent, nonaqueous electrolyte, and power storage device

    JP2015026608A

  • Electrode and battery

    JP2019165005A

  • Positive electrode active material and method for producing positive electrode active material

    WO2020026078A1